Natural polymer-based fibrous elements containing surfactant and manufacturing method thereof

JP2025036466AActive Publication Date: 2025-03-14PROCTER & GAMBLE CO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024225552
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-28
Filing Date
2024-12-20
Publication Date
2025-03-14
Estimated Expiration
2042-05-25

Smart Images

  • Figure 2025036466000001_ABST
    Figure 2025036466000001_ABST
Patent Text Reader

Abstract

To provide: a fibrous element-forming composition suitable for producing a "melt-blown" spun natural polymer-based fibrous elements; a fibrous structure formed of the fibrous element-forming composition; and a method for manufacturing the fibrous structure.SOLUTION: A fibrous structure includes a plurality of fibrous elements. The plurality of fibrous elements includes one or more fibrous element-forming materials. At least one of the one or more fibrous element-forming materials includes a modified polysaccharide and one or more active agents. At least one or more of the active agents includes a surfactant. The surfactant and the modified polysaccharide are present within the plurality of fibrous elements at a weight ratio of from 0.15: 1 to 6: 1. The modified polysaccharide has a solubility parameter of greater than 14.00 to less than 16.25 as determined according to Fedors Method.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a natural polymer-based fibrous element comprising a modified polymer derived from a natural polymer and a surfactant, more particularly to a natural polymer-based fibrous element comprising a modified polysaccharide, such as an acetylated polysaccharide, such as acetylated starch, and a surfactant, such as an anionic surfactant, a method for making such a natural polymer-based fibrous element, a fibrous structure made from such a natural polymer-based fibrous element, and a method for making such a fibrous structure. [Background technology]

[0002] Polyvinyl alcohol (PVOH) is a synthetic polymer produced from polyvinyl acetate and is the go-to filament-forming material (e.g., structurant) for making fibrous elements, such as filaments and / or fibers, especially in the process of making nonwovens (fibrous structures). PVOH is available in a wide range of weight average molecular weights. PVOH is easily processed by extrusion (e.g., continuous extrusion) and / or batch processing. PVOH is strong yet flexible due to its Tg of about 80-85°C. It also exhibits excellent miscibility across a wide range of surfactants. Many of the PVOH grades are biodegradable.

[0003] With the current interest in natural materials and products, formulators are exploring the possibility of replacing PVOH with natural polymers, such as polysaccharides, such as starch. However, current polysaccharides, such as starch, are less compatible with surfactants, such as high concentrations of surfactants, than PVOH. Furthermore, to make polysaccharides, such as starch, perform more similarly to PVOH, they need to be more compatible with surfactants, especially high concentrations of surfactants, have less hydrogen bonding, a lower Tg, and / or have more hydrophobic properties, such as polysaccharides, especially starch.

[0004] Derivatives of starch can provide starch with properties more similar to PVOH. For example, acetylated starch is one promising starch derivative. Acetylated starch is known in the art. Such known acetylated starches are made with various degrees of substitution (DS) ranging from 0.1 to 3. Furthermore, the Food & Drug Administration currently requires that acetylated starch used in, for example, food products have less than 2.5% acetyl groups (DS less than 0.1).

[0005] There is a need for natural polymer-based materials, such as polysaccharide-based materials, such as starch-based materials, such as starch derivatives, such as modified polysaccharides and / or modified starches, that exhibit properties such as Tg, hydrophobicity, less hydrogen bonding, and / or better miscibility with surfactants, particularly higher concentrations of surfactants than is currently achievable, that can be used as an alternative to, for example, PVOH, fibrous elements made from such natural polymer-based materials, such as water soluble fibrous elements, fibrous structures made from such natural polymer-based fibrous elements, and methods of making natural polymer-based materials, natural polymer-based fibrous elements, and fibrous structures.

[0006] Fibrous elements, i.e. crosslinked water-insoluble fibrous elements, and fibrous structures containing such fibrous elements have been made using starch and / or starch derivatives, such as ethoxylated starch, but such fibrous elements and fibrous structures have been limited to low surfactant concentrations (surfactant to starch weight ratios less than 1:1). Furthermore, because the polyvinyl alcohol of the aqueous fibrous element-forming composition is miscible with high surfactant concentrations and high solids concentrations (e.g., greater than 15% by weight, and / or greater than 20% by weight, and / or at least 25% by weight), aqueous fibrous element-forming compositions with high surfactant content (surfactant to polyvinyl alcohol weight ratios greater than 1:1) are made and then spun into water-soluble fibrous elements, unlike polyvinyl alcohol, especially those with a certain degree of hydrolysis (about 84-87% hydrolysis), which has not been successful to date with starch. Indeed, similarly, when unmodified starch (regardless of amylose to amylopectin ratio) is utilized at high surfactant concentrations (e.g., surfactant to starch weight ratios greater than 0.15:1, and / or greater than 0.20:1, and / or greater than 0.25:1, and / or greater than 0.5:1, and / or greater than 1:1) and high solids concentrations (greater than 15% by weight, and / or greater than 20% by weight, and / or at least 25% by weight), an immiscible aqueous fiber element forming composition results, making conversion to a fiber element, e.g., a water soluble fiber element, difficult, if not impossible.

[0007] Since unmodified polysaccharides, i.e. unmodified starch, have not been successful, starch derivatives have been explored. Formulators have tried commercially available starch derivatives for food applications, such as acetylated starch with up to 2.5% acetyl groups (DS less than 0.1), but they too are not miscible with high concentrations of surfactants (e.g., surfactant to acetylated starch weight ratios greater than 0.15:1, and / or greater than 0.20:1, and / or greater than 0.25:1, and / or greater than 0.5:1, and / or greater than 1:1), resulting in phase separation of the surfactant and the acetylated starch, which leads to failed or unsatisfactory spinning of the fiber elements. Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above, there is a need for natural polymer-based materials, such as modified polysaccharides, e.g. starch derivatives, suitable in combination with high concentrations of surfactants to produce spun natural polymer-based fibrous elements, e.g. "meltblown" spun natural polymer-based fibrous elements, having weight ratios of surfactant to natural polymer-based material of greater than 0.15:1, and / or greater than 0.20:1, and / or greater than 0.25:1, and / or greater than 0.5:1, and / or greater than 1:1, fibrous structures made from such natural polymer-based fibrous elements, and methods of making the same. [Means for solving the problem]

[0009] The present invention meets the above-mentioned needs by providing natural polymer-based materials suitable for combining with high concentrations of surfactant to produce spun natural polymer-based fibrous elements, such as "meltblown" spun natural polymer-based fibrous elements, having a weight ratio of surfactant to natural polymer-based material, such as modified polysaccharides, such as starch derivatives, such as acetylated starch, of greater than 0.15:1, and / or greater than 0.20:1, and / or greater than 0.25:1, and / or greater than 0.5:1, and / or greater than 1:1, and / or less than about 6:1, or less than about 5.5:1, or less than about 5:1, fibrous structures made from such natural polymer-based fibrous elements, methods of making same, and fibrous element-forming compositions comprising a natural polymer-based fibrous element-forming material, such as a modified polysaccharide, such as a starch derivative, such as acetylated starch, and a surfactant, that can be spun into the natural polymer-based fibrous elements of the present invention.

[0010] To solve this problem, it is necessary to chemically modify natural polymers, such as polysaccharides, such as starch, so that the natural polymers can be used as natural polymer-based fiber element-forming materials. Such natural polymer-based fiber element-forming materials, such as modified polysaccharides, such as starch derivatives, such as acetylated starch, can be combined with surfactants, such as high concentrations of surfactants, to form aqueous natural polymer-based fiber element-forming compositions suitable for spinning natural polymer-based fiber elements according to the present invention. The type and level of chemical modification of a specific natural polymer, such as a polysaccharide, such as starch, can be estimated by calculating the solubility parameter using the "Fedors method" as described in Robert F. Fedors' A Method for Estimating Both the Solubility Parameters and Molar Volumes of Liquids. POLYMER ENGINEERING AND SCIENCE, FEBRUARY, 1974, Vol. 14, No. 2, 147 (hereinafter referred to as the "Fedors method" described herein), which describes in relevant part that when a miscible filament-forming material / surfactant aqueous formulation with high surfactant and high solids concentration is present, the solubility parameter is consistent with that of other filament-forming materials, such as PVOH (solubility parameter number 14-16). Furthermore, the weight average molecular weight of the natural polymer, such as a polysaccharide, such as starch, affects its miscibility in a high surfactant / high solids formulation. Therefore, the characteristics, weight average molecular weight, level of chemical modification, and type of chemical modification of the natural polymer, such as polysaccharide, such as starch, of the present invention provide a natural polymer-based fiber element forming material that forms a miscible aqueous formulation with the surfactant at high surfactant and high solids concentration so that the natural polymer-based fiber element forming material can be spun into a natural polymer-based fiber element according to the present invention. For example, unmodified starch, such as unmodified amiocarpus starch, exhibits a solubility parameter number of 17.2, while acetylated starch with a DS of 0.3 exhibits a solubility parameter number of 16.2, and acetylated starch with a DS of 0.7 exhibits a solubility parameter number of 14.7.

[0011] In one embodiment of the present invention, there is provided a fiber element, e.g. a natural polymer-based fiber element, e.g. a water-soluble natural polymer-based fiber element, comprising one or more fiber element-forming materials, e.g. one or more natural polymer-based fiber element-forming materials, e.g. one or more water-soluble natural polymer-based fiber element-forming materials, comprising a modified polysaccharide, e.g. a modified starch, e.g. an acetylated starch, and one or more active agents, at least one of which comprises a surfactant, wherein the surfactant and the one or more natural polymer-based fiber element-forming materials, e.g. modified polysaccharides, are present in the natural polymer-based fiber element in a weight ratio of about 0.15:1 to about 6:1, and / or about 0.20:1 to about 5.5:1, and / or about 0.25:1 to about 5:1.

[0012] In another embodiment of the present invention, there is provided a fibrous structure, e.g. a water-soluble fibrous structure, comprising a plurality of fibrous elements, e.g. a plurality of natural polymer-based fibrous elements which may be intertwined with one another, e.g. a plurality of water-soluble natural polymer-based fibrous elements, wherein the plurality of fibrous elements, e.g. the natural polymer-based fibrous elements, comprise one or more fibrous element-forming materials, e.g. one or more natural polymer-based fibrous element-forming materials, e.g. one or more water-soluble natural polymer-based fibrous element-forming materials, at least one of the one or more fibrous element-forming materials comprises a fibrous element-forming material comprising a modified polysaccharide, e.g. a modified starch, e.g. an acetylated starch, and one or more active agents present, e.g. in the plurality of fibrous elements and releasable from the plurality of fibrous elements, at least one of the active agents comprising a surfactant, wherein the surfactant and the one or more fibrous element-forming materials, e.g. the natural polymer-based fibrous element-forming materials, e.g. the modified polysaccharide, are present with the plurality of fibrous elements in a weight ratio of about 0.15:1 to about 6:1, and / or about 0.20:1 to about 5.5:1, and / or about 0.25:1 to about 5:1.

[0013] In another embodiment of the present invention, a package is provided that includes one or more of the fibrous structures of the present invention.

[0014] In yet another embodiment of the present invention, there is provided a method of making one or more fiber elements, e.g., one or more natural polymer based fiber elements, e.g., one or more water soluble natural polymer based fiber elements, comprising the steps of: a. providing a fiber element forming composition, e.g., an aqueous fiber element forming composition, comprising a fiber element forming material, e.g., a natural polymer-based fiber element forming material, e.g., a water-soluble natural polymer-based fiber element forming material, comprising a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch, and one or more active agents comprising at least one surfactant, wherein the surfactant and the one or more natural polymer-based fiber element forming materials, e.g., the modified polysaccharide, together with the plurality of fiber elements, are present in a weight ratio of about 0.15:1 to about 6:1, and / or about 0.20:1 to about 5.5:1, and / or about 0.25:1 to about 5:1; b. spinning the fiber element-forming composition into one or more natural polymer-based fiber elements, such as one or more water-soluble natural polymer-based fiber elements.

[0015] In yet another embodiment of the present invention, there is provided a method of making a fibrous structure, e.g., a water soluble fibrous structure, comprising the steps of: a. providing a fiber element forming composition, e.g., an aqueous fiber element forming composition, comprising one or more fiber element forming materials, e.g., one or more natural polymer-based fiber element forming materials, e.g., one or more water-soluble natural polymer-based fiber element forming materials, including a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch, and one or more active agents, at least one of which comprises a surfactant, wherein the surfactant and the one or more natural polymer-based fiber element forming materials, e.g., the modified polysaccharide, are present in the fiber element forming composition in a weight ratio of about 0.15:1 to about 6:1, and / or about 0.20:1 to about 5.5:1, and / or about 0.25:1 to about 5:1; b. spinning the fiber element-forming composition into a plurality of fiber elements, e.g., a plurality of natural polymer-based fiber elements, e.g., a plurality of water-soluble natural polymer-based fiber elements, comprising the natural polymer-based fiber element-forming material and the surfactant; c. optionally mixing a plurality of particles, e.g., water soluble and / or water insoluble particles, e.g., water soluble and / or water insoluble active agent-containing particles, with the plurality of fiber elements, e.g., natural polymer based fiber elements; and d. collecting a plurality of optionally intertwined fiber elements, e.g., natural polymer-based fiber elements, from step (b) and / or the mixture of particles and natural polymer-based fiber elements from optional step (c) to form a fibrous structure, e.g., a water-soluble fibrous structure.

[0016] In yet another embodiment, there is provided a fiber element forming composition comprising a polar solvent, one or more fiber element forming materials, e.g., one or more natural polymer-based fiber element forming materials, e.g., one or more water soluble natural polymer-based fiber element forming materials, including a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch, and one or more active agents, at least one of the active agents comprising a surfactant, wherein the surfactant and the one or more natural polymer-based fiber element forming materials are present in the fiber element forming composition in a weight ratio of about 0.15:1 to about 6:1, and / or about 0.20:1 to about 5.5:1, and / or about 0.25:1 to about 5:1.

[0017] In yet another embodiment of the present invention, the fiber element, e.g., a natural polymer-based fiber element, e.g., a water-soluble natural polymer-based fiber element, has a degree of substitution (DS) of from about 0.1 to about 1.0, and / or from about 0.2 to about 0.9, and / or from about 0.2 to about 0.8, and / or from about 0.3 to about 0.7, and / or from about 0.3 to about 0.5, and a weight average molecular weight (MW) of from about 25,000 to about 450,000 g / mol, and / or from about 35,000 to about 400,000 g / mol, and / or from about 50,000 to about 400,000 g / mol, as measured according to the weight average molecular weight test method described herein. one or more fiber element forming materials, such as one or more natural polymers, having a weight average molecular weight (Mw) of from about 0 g / mol, and / or from about 60,000 to about 400,000 g / mol, and / or from about 65,000 to about 350,000 g / mol, and / or from about 70,000 to about 300,000 g / mol, and / or from about 90,000 to about 300,000 g / mol, and / or from about 120,000 to about 250,000 g / mol, and / or from about 130,000 to about 250,000 g / mol, and / or from about 150,000 to about 250,000 g / mol; and a fiber element forming composition comprising one or more water-soluble natural polymer-based fiber element forming materials, such as modified polysaccharides, such as modified starches, such as acetylated starch, and further comprising one or more active agents, such as one or more surfactants, such as a surfactant mixture comprising linear alkylbenzene sulfonates and alkyl sulfates, and exhibiting a viscosity of about 0.01 Pa·s to about 1.2 Pa·s and / or about 0.02 Pa·s to about 1.0 Pa·s when measured according to the rotational rheometer test method described herein, such as A fiber element is provided which is derived from an aqueous fiber element-forming composition, the fiber element-forming composition comprising the surfactant mixture and the one or more fiber element-forming materials, such as one or more natural polymer-based fiber element-forming materials, such as modified polysaccharides, such as modified starches, such as acetylated starch, in a weight ratio of from about 0.15:1 to about 6:1, and / or from about 0.20:1 to about 5.5:1, and / or from about 0.25:1 to about 5:1, and / or from about 0.5:1 to about 2:1, and the fiber element-forming composition further comprising from about 55% by weight to about 85% by weight of water.

[0018] In yet another embodiment of the present invention, there is provided a fibrous structure, e.g., a water-soluble fibrous structure, comprising a plurality of fibrous elements, e.g., a plurality of natural polymer-based fibrous elements, e.g., a plurality of water-soluble natural polymer-based fibrous elements, wherein the plurality of fibrous elements have a DS of about 0.1 to about 1.0, and / or about 0.2 to about 0.9, and / or about 0.2 to about 0.8, and / or about 0.3 to about 0.7, and / or about 0.3 to about 0.5, and a weight average molecular weight of about 25,000 to about 450,000 g / mol, and / or about 35,000 to about 400,000 g / mol, as measured according to the weight average molecular weight test method described herein. one or more fiber element forming materials having a weight average molecular weight (Mw) of about 0 g / mol, and / or about 50,000 to about 400,000 g / mol, and / or about 60,000 to about 400,000 g / mol, and / or about 65,000 to about 350,000 g / mol, and / or about 70,000 to about 300,000 g / mol, and / or about 90,000 to about 300,000 g / mol, and / or about 120,000 to about 250,000 g / mol, and / or about 130,000 to about 250,000 g / mol, and / or about 150,000 to about 250,000 g / mol. , for example, one or more natural polymer-based fiber element forming materials, for example, one or more water-soluble natural polymer-based fiber element forming materials, for example, modified polysaccharides, for example, modified starches, for example, acetylated starch, and the plurality of fiber elements further comprises one or more active agents, for example, one or more surfactants, for example, a surfactant mixture including a linear alkylbenzene sulfonate and an alkyl sulfate, and the plurality of fiber elements has a viscosity of from about 0.01 Pa·s to about 1.2 Pa·s and / or from about 0.02 Pa·s to about 1 Pa·s when measured according to the rotational rheometer test method described herein. The fiber element forming composition is derived from a fiber element forming composition, e.g., an aqueous fiber element forming composition, having a viscosity of 0.0 Pa·s, the fiber element forming composition comprising the surfactant mixture and one or more natural polymer-based fiber element forming materials, e.g., modified polysaccharides, e.g., modified starches, e.g., acetylated starch, in a weight ratio of from about 0.15:1 to about 6:1, and / or from about 0.20:1 to about 5.5:1, and / or from about 0.25:1 to about 5:1, and / or from about 0.5:1 to about 2:1, and the fiber element forming composition further comprising from about 55% by weight to about 85% by weight of water.

[0019] In yet another embodiment of the present invention, there is provided a fiber element forming composition, e.g., an aqueous fiber element forming composition, e.g., a natural polymer-based fiber element forming composition, comprising a polar solvent, one or more fiber element forming materials, e.g., one or more natural polymer-based fiber element forming materials, e.g., a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch, and one or more active agents, e.g., one or more surfactants, e.g., a surfactant mixture comprising a linear alkylbenzene sulfonate and an alkyl sulfate, such that the natural polymer-based fiber element forming composition exhibits a viscosity of about 0.01 Pa·s to about 1.2 Pa·s and / or about 0.02 Pa·s to about 1.0 Pa·s when measured according to the rotational rheometer test method described herein.

[0020] In yet another embodiment of the present invention, there is provided a method of making a textile element, e.g., a natural polymer based textile element, e.g., a water soluble natural polymer based textile element, comprising the steps of: a. providing a fiber element forming composition, e.g., a water-soluble fiber element forming composition, comprising one or more fiber element forming materials, e.g., one or more natural polymer-based fiber element forming materials, e.g., a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch, and a surfactant mixture, e.g., a surfactant mixture comprising linear alkylbenzene sulfonate and alkyl sulfate, wherein the fiber element forming composition comprises the surfactant mixture and the one or more natural polymer-based fiber element forming materials in a weight ratio of about 0.15:1 to about 6:1, and / or about 0.20:1 to about 5.5:1, and / or about 0.25:1 to about 5:1, and / or about 0.5:1 to about 2:1; b. spinning the fiber element forming composition into one or more fiber elements, e.g., one or more natural polymer-based fiber elements, comprising one or more fiber element forming materials, e.g., one or more natural polymer-based fiber element forming materials, and the surfactant mixture.

[0021] In yet another embodiment of the present invention, there is provided a fiber element comprising one or more fiber element forming materials including an acetylated starch having a degree of substitution (DS) of about 0.3 to about 0.7 and a weight average molecular weight of about 50,000 to about 250,000 g / mol, further comprising a surfactant mixture including a linear alkylbenzene sulfonate and an alkyl sulfate, an aqueous composition comprising the surfactant mixture and the acetylated starch in a weight ratio of about 0.5:1 to about 2:1, and the aqueous composition further comprising about 55% to about 85% by weight of water.

[0022] In yet another embodiment of the present invention, a fibrous structure comprising a plurality of fibrous elements according to the present invention, the fibrous structure comprising a surfactant mixture and acetylated starch in a weight ratio of about 0.5:1 to about 2:1.

[0023] In yet another embodiment of the present invention, there is provided a method of making a fiber element, the method comprising the steps of: a. providing a fiber element forming composition comprising one or more fiber element forming materials including an acetylated starch and a surfactant mixture including a linear alkyl benzene sulfonate and an alkyl sulfate, the surfactant mixture and the acetylated starch being in a weight ratio of about 0.5:1 to about 2:1; b. spinning the fiber element forming composition into one or more fiber elements comprising the acetylated starch and the surfactant mixture.

[0024] In yet another embodiment of the present invention, there is provided a fiber element forming composition comprising a polar solvent, one or more fiber element forming materials comprising acetylated starch, and a surfactant mixture comprising a linear alkylbenzene sulfonate and an alkyl sulfate, such that the fiber element forming composition exhibits a viscosity of about 0.01 Pa·s to about 1.2 Pa·s when measured according to a rotational rheometer test method.

[0025] The present invention provides natural polymer-based fiber elements, fiber structures comprising a plurality of natural polymer-based fiber elements, fiber element-forming compositions comprising natural polymer-based fiber element-forming materials, natural polymer-based fiber element-forming materials, and methods of making the same. [Brief description of the drawings]

[0026] [Figure 1] 1 is a scanning electron microscope photograph of a cross-section of one embodiment of a fibrous structure according to the present invention. [Diagram 2] 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present invention. [Diagram 3] 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present invention. [Figure 4] 4 is a scanning electron micrograph of a cross-section of another embodiment of a fibrous structure in accordance with the present invention. [Diagram 5] FIG. 2 is a schematic diagram of an example of a process for producing a fiber element of the present invention. [Figure 6] FIG. 6 is a schematic diagram of an example die, including an enlarged view, used in the process of FIG. 5. [Figure 7] 1 is a schematic diagram of one embodiment of a process for producing a fibrous structure according to the present invention. [Figure 8] 2 is a schematic diagram of another embodiment of a process for producing a fibrous structure according to the present invention. [Figure 9] 2 is a schematic diagram of another embodiment of a process for producing a fibrous structure according to the present invention. [Figure 10A] 1 is a schematic diagram of an embodiment of an expandable fiber structure product according to the present invention. [Figure 10B] FIG. 10B is a cross-sectional view taken along line 10B-10B in FIG. 10A. [Figure 11] FIG. 2 is a schematic diagram of an embodiment of an instrumental configuration for use in measuring solubility according to the present invention. [Figure 12] FIG. 12 is a schematic diagram of FIG. 11 during dissolution testing. [Figure 13] FIG. 13 is a schematic diagram of the top view of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] definition "Fibrous structure" as used herein refers to a structure comprising one or more fibrous elements and, optionally, one or more particles. In one embodiment, a fibrous structure according to the present invention refers to an association of fibrous elements and, optionally, particles, which together form a structure, such as a monolithic structure, capable of performing a function. Multiple fibrous elements may be intertwined with each other.

[0028] The fibrous structure of the present invention may be homogeneous or layered. If layered, the fibrous structure may comprise at least two, and / or at least three, and / or at least four, and / or at least five layers, such as one or more layers of fiber elements, one or more layers of particles if present, and / or one or more mixed layers of fiber elements / particles if particles are present.

[0029] In one embodiment, the fibrous structure has a basis weight of 5000 g / m2 as measured according to the basis weight test method described herein. 2 and a multi-ply fibrous structure exhibiting a basis weight of less than 100 mm.

[0030] In one embodiment, the fibrous structure of the present invention is a "monolithic fibrous structure."

[0031] As used herein, a "monolithic fibrous structure" is an arrangement comprising a plurality of fibrous elements that are intertwined or otherwise bonded to each other to form a fibrous structure. In addition to a plurality of fibrous elements, a single fibrous structure may further comprise one or more particles and / or particles bonded to the plurality of fibrous elements. A monolithic fibrous structure of the present invention may be one or more plies within a multi-ply fibrous structure. In one embodiment, a monolithic fibrous structure of the present invention may comprise three or more different fibrous elements. In another embodiment, a monolithic fibrous structure of the present invention may comprise two different fibrous elements, such as a co-formed fibrous structure, on top of which a different fibrous element is deposited to form a fibrous structure comprising three or more different fibrous elements.

[0032] As used herein, a "fiber element" refers to an elongated particle having a length that is significantly greater than its average diameter, i.e., a length to average diameter ratio of at least about 10. A fiber element can be a filament or a fiber. In one embodiment, a fiber element is a single fiber element, rather than a yarn that includes multiple fiber elements.

[0033] The fiber elements of the present invention can be spun from a filament-forming composition, also referred to as a fiber element-forming composition, via a suitable spinning process operation, such as meltblowing, spunbonding, electrospinning, and / or rotary spinning.

[0034] The fiber elements of the present invention may be monocomponent and / or multicomponent. For example, the fiber elements may comprise bicomponent fibers and / or filaments. The bicomponent fibers and / or filaments may be of any configuration, such as side-by-side, sheath-core, islands-in-the-sea, etc.

[0035] As used herein, "filament" means an elongated particle as defined above exhibiting a length of 2 inches or more, and / or 3 inches or more, and / or 4 inches or more, and / or 6 inches or more.

[0036] Filaments are typically considered to be essentially continuous or substantially continuous. Filaments are relatively longer than fibers. Non-limiting examples of filaments include meltblown filaments and / or spunbond filaments. Non-limiting examples of polymers that can be spun into filaments include natural polymers such as starch, starch derivatives, cellulose (e.g., rayon and / or lyocell), cellulose derivatives, hemicellulose, and hemicellulose derivatives, as well as synthetic polymers including, but not limited to, thermoplastic polymer filaments such as polyester, nylon, polyolefins (e.g., polypropylene filaments, and polyethylene filaments), and biodegradable thermoplastic fibers such as polylactic acid filaments, polyhydroxyalkanoate filaments, polyesteramide filaments, and polycaprolactone filaments.

[0037] As used herein, "fiber" means an elongated particle as defined above exhibiting a length of less than 2 inches and / or less than 1.5 inches and / or less than 1 inch.

[0038] Typically, the fibers are considered to be discontinuous in nature. Non-limiting examples of fibers include staple fibers made by spinning the filaments or filament tows of the present invention and then chopping the filaments or filament tows into pieces less than 2 inches to produce fibers.

[0039] In one embodiment, one or more fibers can be formed from the filaments of the present invention, such as when the filaments are cut into shorter lengths (such as lengths less than 5.08 cm). Thus, in one embodiment, the present invention also includes fibers made from the filaments of the present invention, such as fibers that include one or more filament-forming materials and one or more additives (such as activators). Thus, references herein to filaments of the present invention also include fibers made from such filaments, unless otherwise specified. Fibers are typically considered to be essentially discontinuous, as opposed to filaments, which are typically considered to be essentially continuous.

[0040] As used herein, "filament-forming composition" and / or "fiber element-forming composition" refers to a composition suitable for making one or more fiber elements of the present invention, for example by meltblowing and / or spunbonding, for example by spinning a fiber element from a multi-row capillary meltblowing die. The filament-forming composition includes one or more fiber element-forming materials, e.g., filament-forming materials, that exhibit properties that make it suitable for spinning into a fiber element. In one embodiment, the fiber element-forming material includes a polymer. In addition to the one or more fiber element-forming materials, the fiber element-forming composition may include one or more additives, e.g., one or more active agents. Furthermore, the fiber element-forming composition may include one or more polar solvents, e.g., water, in which one or more, e.g., all, of the fiber element-forming materials and / or one or more, e.g., all, of the active agents are dissolved and / or dispersed prior to spinning a fiber element, e.g., a filament derived from the fiber element-forming composition.

[0041] In one embodiment, the fiber elements, e.g., filaments, of the invention made from the fiber element-forming composition of the invention are such that one or more additives, e.g., one or more active agents, may be present in the fiber element rather than on the fiber element, e.g., a coating composition comprising one or more active agents. The one or more active agents in such a coating composition, if present, may be the same as or different from the active agents in the fiber element and / or active agent-containing particles. The total concentration of fiber element-forming materials and the total concentration of active agents present in the fiber element-forming composition may be any suitable amount, so long as a fiber element of the invention can be produced therefrom.

[0042] In one embodiment, one or more additives, such as an active agent, may be present in the fiber element and one or more additional additives, such as an active agent, may be present on the surface of the fiber element. In another embodiment, the fiber elements of the present invention may include one or more additives, such as an active agent, that are originally present in the fiber element when fabricated, but that bloom on the surface of the fiber element before and / or when exposed to the intended use conditions of the fiber element, and / or that are released from the fiber element when exposed to the intended use conditions, e.g., upon dissolution.

[0043] As used herein, "fiber element-forming material" and / or "filament-forming material" and / or "fiber-forming material" refers to a material, e.g., a polymer, or a monomer capable of producing a polymer, that exhibits suitable properties for making fiber elements. In one embodiment, the fiber element-forming material includes one or more natural polymer-based polymers, such as anionic, cationic, zwitterionic, and / or nonionic polymers. In another embodiment, the polymer may include a hydroxyl polymer, e.g., a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch. In yet another embodiment, the natural polymer-based fiber element-forming material, e.g., a modified polysaccharide, is a polar solvent-soluble, e.g., water-soluble, natural polymer-based material.

[0044] As used herein, "mixed" and / or "mixing" refers to a state or form in which particles are mixed with fiber elements, e.g., filaments. The mixture of fiber elements, e.g., filaments, and particles, e.g., active agent-containing particles, can be present in and / or throughout the composite structure, or within a plane or region of the composite structure. In one example, commingled fiber elements, e.g., filaments and particles, can form at least a surface of the composite structure. In one example, the particles can be uniformly distributed in and / or throughout the composite structure, and / or within a plane and / or region of the composite structure. In one example, the particles may be uniformly distributed in and / or throughout the composite structure, which avoids and / or prevents particles within the composite structure from sag and / or moving freely and / or migrating to other regions within the composite structure, resulting in zones of higher concentration of particles and zones of lower or zero concentration of particles within the composite structure. In one example, a μCT cross-section of a composite structure can show whether particles are uniformly distributed in and / or throughout the composite structure.

[0045] As used herein, "additive" refers to any material present in a fiber element of the present invention that is not a fiber element forming material. In one embodiment, the additive comprises an active agent. In another embodiment, the additive comprises a processing aid. In yet another embodiment, the additive comprises a filler. In one embodiment, the additive comprises any material present in the fiber element, the absence of which would not impair the fiber element structure of the fiber element (in other words, the absence of which would not impair the solid form of the fiber element). In another embodiment, the additive, e.g., an active agent, comprises a non-polymeric material.

[0046] In other examples, the additive may include a plasticizer for the fiber element. Non-limiting examples of suitable plasticizers for the present invention include polyols, copolyols, polycarboxylic acids, polyesters, and dimethicone copolyols. Examples of useful polyols include, but are not limited to, glycerin, diglycerin, propylene glycol, ethylene glycol, butylene glycol, pentylene glycol, cyclohexanedimethanol, hexanediol, 2,2,4-trimethylpentane-1,3-diol, polyethylene glycol (200-600), pentaerythritol, sugar alcohols such as sorbitol, mannitol, lactitol, and other monohydric and polyhydric low molecular weight alcohols (e.g., C2-C8 alcohols); monosaccharides, disaccharides, and oligosaccharides such as fructose, glucose, sucrose, maltose, lactose, high fructose corn syrup solids, and dextrins, and ascorbic acid.

[0047] In one embodiment, the plasticizer includes glycerin, and / or propylene glycol, and / or glycerol derivatives such as propoxylated glycerol, hi yet another embodiment, the plasticizer is selected from the group consisting of glycerin, ethylene glycol, polyethylene glycol, propylene glycol, glycidol, urea, sorbitol, xylitol, maltitol, sugars, ethylene bisformamide, amino acids, and mixtures thereof.

[0048] In other examples, the additives may include rheology modifiers, such as shear modifiers and / or extensional modifiers. Non-limiting examples of rheology modifiers include, but are not limited to, polyacrylamides, polyurethanes, polyethylene oxides, polyvinylpyrrolidones, polyvinylcaprolactams, polyvinylimidazoles, high molecular weight polysaccharides, polyvinyl alcohols, polyacrylates, and mixtures thereof that may be used in the fibrous elements of the present invention. Non-limiting examples of rheology modifiers are commercially available from Dow Chemical Company (Midland, MI).

[0049] In yet another example, the additive may include one or more colors and / or dyes that are incorporated into the fiber elements of the present invention to provide a visual signal when the fiber element is exposed to intended use conditions and / or when an active agent is released from the fiber element and / or when the morphology of the fiber element changes.

[0050] In yet another embodiment, the additive may include one or more release agents and / or lubricants. Non-limiting examples of suitable release agents and / or lubricants include fatty acids, fatty acid salts, fatty alcohols, fatty esters, sulfonated fatty acid esters, fatty amine acetates, fatty amides, silicones, aminosilicones, fluoropolymers, and mixtures thereof. In one embodiment, the release agents and / or lubricants may be applied to the fibrous elements, in other words, after the fibrous elements are formed. In one embodiment, one or more release agents / lubricants may be applied to the fibrous elements before collecting the fibrous elements in a collecting device to form a fibrous structure. In another embodiment, one or more release agents / lubricants may be applied to the fibrous structures formed from the fibrous elements of the present invention before contacting one or more of the fibrous structures, such as in a stack of fibrous structures. In yet another embodiment, one or more release agents / lubricants may be applied to the fibrous elements and / or fibrous structures of the present invention before the fibrous elements and / or fibrous structures contact a surface (e.g., a surface of an apparatus used in a processing system) to facilitate release of the fibrous elements and / or fibrous structures and / or to prevent plies of the fibrous elements and / or fibrous structures of the present invention from sticking together, even unintentionally. In one embodiment, the release agent / lubricant comprises particles.

[0051] In yet other examples, the additive may include one or more antiblocking and / or detackifying agents. Non-limiting examples of suitable antiblocking and / or detackifying agents include starch, starch derivatives, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, mica, and mixtures thereof.

[0052] In one embodiment, it has been unexpectedly discovered that the inclusion of silica in the fibrous structure of the present invention results in a stable foam having a higher foam height than without the silica.

[0053] As used herein, "intended use conditions" refers to the temperature, physical, chemical, and / or mechanical conditions to which the fiber elements, particles, and / or fiber structures of the present invention are exposed when used for one or more of their designed applications. For example, if the fiber elements, particles, and / or fiber structures comprising the fiber elements are designed to be used in a washing machine for laundry care purposes, the intended use conditions include the temperature, chemical, physical, and / or mechanical conditions present in the washing machine, including any wash water, during the laundry washing operation. In another example, if the fiber elements, particles, and / or fiber structures comprising the fiber elements are designed to be used by humans as a shampoo for hair care purposes, the intended use conditions include the temperature, chemical, physical, and / or mechanical conditions present in a shampoo of human hair. Similarly, when the fibrous structure comprising fibrous elements, and / or particles, and / or fibrous elements is designed to be used in a dishwashing operation, either by hand or in a dishwasher, the intended conditions of use include the temperature, chemical, physical, and / or mechanical conditions present in the dishwashing water and / or in the dishwasher during the dishwashing operation.

[0054] As used herein, "active agent" refers to an additive that produces an intended effect in the environment outside the fiber elements, and / or particles, and / or fiber structures comprising the fiber elements of the present invention, for example, when the fiber elements, and / or particles, and / or fiber structures are exposed to the intended conditions of use of the fiber elements, and / or particles, and / or fiber structures comprising the fiber elements. In one embodiment, the active agent includes additives that treat surfaces, such as hard surfaces (i.e., kitchen counters, bathtubs, toilets, urinals, sinks, floors, walls, teeth, cars, windows, mirrors, dishes) and / or soft surfaces (i.e., fabrics, hair, skin, carpets, crops, plants). In another embodiment, the active agent includes additives that produce a chemical reaction (i.e., foaming, effervescence, coloring, warming, cooling, foaming, disinfecting and / or purifying and / or chlorinating (such as water purification and / or water disinfection and / or water chlorinating)). In yet another example, the active agent includes an additive that treats the environment (i.e., deodorizes, purifies, fragrances the air). In one example, the active agent is formed in situ, such as during the formation of the fiber elements and / or particles that contain the active agent, for example, the fiber elements and / or particles may include a water-soluble polymer (e.g., starch) and a surfactant (e.g., an anionic surfactant). The water-soluble polymer and surfactant can create a polymer complex, or coacervate, that functions as the active agent used to treat the surface of the fabric.

[0055] "Treating" as used herein with respect to the treatment of a surface means that the active agent provides a benefit to the surface or environment. Treatment includes regulating and / or rapidly improving the appearance, cleanliness, odor, purity, and / or feel of the surface or environment. In one embodiment, treatment with respect to the treatment of a keratinous tissue (e.g., skin and / or hair) surface means regulating and / or rapidly improving the cosmetic appearance and / or feel of the keratinous tissue. For example, "regulating the condition of the skin, hair, or nails (keratinous tissue)" can include thickening of the skin, hair, or nails (e.g., building up of the epidermal and / or dermal and / or subcutaneous (e.g., subcutaneous fat or muscle) layers of the skin, and building up of the stratum corneum of the nails and hair shafts, if applicable), increasing the convolution of the dermal-epidermal junction (also known as the interpapillary ridge), reducing elastosis, sagging, and deformation of the skin or hair, to reduce atrophy of the skin, hair, or nails. prevention of loss of elasticity of the skin or hair (loss, damage, and / or inactivation of functional skin elastin), such as loss of elasticity of the skin or hair, such as loss of elasticity of the skin (loss of, damage to, and / or inactivation of functional skin elastin), such as loss of elasticity of the skin or hair, loss of elasticity of the skin or hair, such as loss of elasticity of the skin or hair (loss of elasticity of the skin, such as loss of elasticity of the skin or hair), loss of elasticity of the skin or hair, such as loss of elasticity of the skin or hair

[0056] In another embodiment, treating refers to removing stains and / or odors from fabric articles (e.g., clothing, towels, linens) and / or hard surfaces (e.g., counters and / or tableware such as pots and pans).

[0057] As used herein, "fabric care active" means an active that, when applied to a fabric, provides a benefit and / or improvement to the fabric. Non-limiting examples of benefits and / or improvements to fabrics include cleaning (e.g., by surfactants), stain removal, stain reduction, wrinkle removal, color recovery, static control, wrinkle resistance, permanent press, abrasion reduction, abrasion resistance, pill removal, pilling resistance, stain removal, stain resistance (including stain release), shape retention, shrink reduction, softness, fragrance, antibacterial, antiviral, anti-odor, and odor elimination.

[0058] As used herein, "dishwashing active" means an active that, when applied to tableware, glassware, pots, pans, utensils, and / or cooksheets, provides a benefit and / or improvement to the tableware, glassware, plastic articles, pots, pans, and / or cooksheets. Non-limiting examples of benefits and / or improvements to tableware, glassware, plastic articles, pots, pans, utensils, and / or cooksheets include food and / or soil removal, cleaning (e.g., surfactant) stain removal, stain reduction, grease removal, water stain removal and / or water stain prevention, glass and metal care, sanitizing, shine, and polishing.

[0059] As used herein, "hard surface active" means an active that, when applied to floors, counters, sinks, windows, mirrors, showers, baths, and / or toilets, provides a benefit and / or improvement to the floors, counters, sinks, windows, mirrors, showers, baths, and / or toilets. Non-limiting examples of benefits and / or improvements to floors, counters, sinks, windows, mirrors, showers, baths, and / or toilets include food and / or soil removal, cleaning (e.g., with surfactants), stain removal, stain reduction, grease removal, water stain removal and / or water stain prevention, soap scum removal, sanitizing, brightening, polishing, and freshening.

[0060] As used herein, "particles", e.g., active agent-containing particles, refer to powders, granules, and / or aggregates. The shape of the particles may be spherical, rod-shaped, dish-shaped, tubular, square, rectangular, disk-shaped, star-shaped, fibrous, and may have regular or irregular random shapes. The particles of the present invention, at least those particles of at least 44 μm, can be measured by the particle size distribution test method described herein. For particles less than 44 μm, different test methods, e.g., light scattering methods, can be used to determine the particle size of less than 44 μm, e.g., perfume microcapsules typically ranging in size from about 15 μm to about 44 μm and / or about 25 μm.

[0061] In one aspect, the particles may comprise recycled fibrous structural material, specifically, the fibrous material is recycled by grinding the fibers into finely divided solids and reincorporating the finely divided solids into aggregates, granules, or other particulate forms. In another aspect, the particles may comprise recycled fibrous structural material, specifically, the fibrous material is incorporated into a fluid paste, suspension, or solution and then processed to form aggregates, granules, or other particulate forms. In another aspect, the fluid paste, suspension, or solution containing recycled fibrous material may be applied directly to a fibrous layer in the process of making a new fibrous article.

[0062] In one embodiment, the particles exhibit a D50 of less than 500 μm, and / or less than 450 μm, and / or less than 400 μm, and / or less than 350 μm to about 100 μm, or to about 150 μm, or to about 200 μm, when measured according to the Particle Size Distribution test method described herein.

[0063] In one embodiment, the particles, which may be discrete particles and / or agglomerates (discrete particles bonded together), may exhibit a D50 particle size of from about 100 μm to about 5000 μm, and / or from about 100 μm to about 2000 μm, and / or from about 250 μm to about 1200 μm, and / or from about 250 μm to about 850 μm, when measured according to the Particle Size Distribution Test Method described herein.

[0064] In one example, the particles, which may be discrete particles and / or agglomerates (discrete particles bonded together), may exhibit a D10 of 250 μm when measured according to the Particle Size Distribution Test Method described herein.

[0065] In another example, the particles and / or agglomerates (discrete particles bonded together) may exhibit a D90 of 1200 μm and / or 850 μm when measured according to the Particle Size Distribution Test Method described herein.

[0066] In one example, the particles and / or agglomerates (discrete particles bonded together) may exhibit a D10 greater than 44 μm, and / or greater than 90 μm, and / or greater than 150 μm, and / or greater than 212 μm, and / or greater than 300 μm when measured according to the Particle Size Distribution Test Method described herein.

[0067] In one example, the particles and / or agglomerates (discrete particles bonded together) may exhibit a D90 of less than 1400 μm, and / or less than 1180 μm, and / or less than 850 μm, and / or less than 600 μm, and / or less than 425 μm when measured according to the Particle Size Distribution Test Method described herein.

[0068] In one example, the particles and / or agglomerates (discrete particles bonded together) may exhibit any combination of the D10, D50, and / or D90 identified above, so long as D50, if present, is greater than D10, and D90, if present, is greater than D10 and D50, if present.

[0069] In one embodiment, the particles and / or agglomerates (discrete particles bonded together) particles may exhibit any combination of D10 and D90 identified above, so long as D90 is greater than D10.

[0070] In one example, the particles and / or agglomerates (discrete particles bonded together) may exhibit a D10 greater than 212 μm and a D90 less than 1180 μm when measured according to the Particle Size Distribution Test Method described herein.

[0071] In one example, the particles and / or agglomerates (discrete particles bonded together) may exhibit a D10 greater than 90 μm and a D90 less than 425 μm when measured according to the Particle Size Distribution Test Method described herein.

[0072] As used herein, "effervescent system" refers to a mixture of one or more effervescent acids and / or effervescent acid particles and one or more effervescent salts and / or effervescent salt particles. In one embodiment, the selection of a particular effervescent acid, e.g., effervescent acid particles, and / or effervescent salt, e.g., effervescent salt particles, and their ratios depend at least in part on the requirement of the amount of gas, e.g., CO2 release. In one embodiment, the effervescent acid, e.g., effervescent acid particles, such as citric acid, may be added in an amount of about 10% to about 60% by weight based on the weight of the effervescent system, and the effervescent salt, e.g., alkali metal salt, e.g., sodium bicarbonate, may also be added in an amount of about 10% to about 60% by weight based on the weight of the effervescent component.

[0073] As used herein, "effervescent acid" or "effervescent acid particles" refers to an acid and / or acid particles that, when combined with an effervescent salt or effervescent salt particles, produces effervescence, e.g., a gas such as CO2. Non-limiting examples of effervescent acids and / or effervescent acid particles suitable for use in the effervescent compositions of the present invention include, but are not limited to, tartaric acid, citric acid, fumaric acid, adipic acid, malic acid, oxalic acid, sulfamic acid, and mixtures thereof. In one embodiment, the effervescent acid and / or effervescent acid particles include citric acid, or a mixture of citric acid and tartaric acid. The effervescent acid and / or effervescent acid particles may be anhydrous.

[0074] As used herein, "effervescent salt" or "effervescent salt particles" refers to salts and / or salt particles that produce effervescence, e.g., gas such as CO2, when combined with an effervescent acid and / or an effervescent acid particle. Non-limiting examples of suitable effervescent salts and / or effervescent salt particles include, but are not limited to, alkali metal salts and / or carbonates and / or bicarbonates, such as sodium carbonate, calcium carbonate, magnesium carbonate, ammonium carbonate, potassium carbonate, sodium bicarbonate, calcium bicarbonate, and mixtures thereof. The effervescent salts and / or effervescent salt particles may be anhydrous.

[0075] As used herein, "weight ratio" refers to the ratio between two materials on a dry basis. For example, the weight ratio of fiber element forming material to active agent in a fiber element and / or a plurality of fiber elements is the ratio of the weight (g or %) of the fiber element forming material on a dry weight basis in the fiber element and / or a plurality of fiber elements to the weight (g or %) of an additive, such as an active agent, on a dry weight basis in the fiber element and / or a plurality of fiber elements. In another example, the weight ratio of particles to fiber elements in a fiber structure is the ratio of the weight (g or %) of particles on a dry weight basis in the fiber structure to the weight (g or % (same units as the weight of particles)) of fiber elements on a dry weight basis in the fiber structure.

[0076] As used herein, "water-soluble material" and / or "water-soluble fibrous structure" and / or "water-soluble fibrous element-forming material" and / or "water-soluble particle" refers to a material that is miscible with water, in other words, a material that is capable of forming a stable homogeneous solution (does not separate for more than 5 minutes after forming a homogeneous liquid) with water at ambient conditions.

[0077] As used herein, "ambient conditions" means approximately 23°C ± 1.0°C and a relative humidity of 50% ± 2%.

[0078] "Weight average molecular weight" means the weight average molecular weight determined according to the Weight Average Molecular Weight Test Method described herein.

[0079] As used herein with respect to fiber elements, "length" means the length along the longest axis of the fiber element from one end to the other. If the fiber element has internal twists, curls, or bends, the length is the length along the entire path of the fiber element from one end to the other.

[0080] As used herein with respect to fiber elements, "diameter" is measured according to the diameter test method described herein. In one embodiment, fiber elements of the present invention exhibit a diameter of less than 100 μm, and / or less than 75 μm, and / or less than 50 μm, and / or less than 25 μm, and / or less than 20 μm, and / or less than 15 μm, and / or less than 10 μm, and / or less than 6 μm, and / or greater than 1 μm, and / or greater than 3 μm.

[0081] As used herein, "triggering conditions" refers, in one embodiment, to anything as an action or event that acts as a stimulus and initiates or causes a change in the fiber elements and / or particles and / or fiber structures of the present invention (e.g., loss or change in the physical structure of the fiber elements and / or the physical structure of the fiber structures and / or release of additives such as active agents). In another embodiment, the triggering conditions may be present in an environment (such as water) when the fiber elements and / or particles and / or fiber structures of the present invention are added to the water. In other words, no change occurs in the water apart from the fact that the fiber elements and / or fiber structures of the present invention have been added to the water.

[0082] As used herein with respect to morphological changes of fiber elements and / or particles, "morphological changes" means that the fiber elements undergo a change in their physical structure. Non-limiting examples of morphological changes of the fiber elements and / or particles of the present invention include dissolving, melting, expanding, contracting, shattering, bursting, lengthening, shortening, and combinations thereof. The fiber elements and / or particles of the present invention may completely or substantially lose their physical structure, or may change in morphology, or may retain or substantially retain their physical structure when exposed to the intended conditions of use.

[0083] "Weight on a dry fibrous element basis" and / or "weight on a dry particle basis" and / or "weight on a dry fibrous structure basis" refers to the weight of the fibrous element, particle, and / or fibrous structure, respectively, measured immediately after the fibrous element, particle, and / or fibrous structure, respectively, has been conditioned for 2 hours in a conditioned room at a temperature of 23° C.±1.0° C. and a relative humidity of 50%±10%. In one embodiment, weight on a dry fibrous element basis and / or weight on a dry particle basis and / or weight on a dry fibrous structure basis means that the fibrous element, particle, and / or fibrous structure contains less than 20% by weight, and / or less than 15% by weight, and / or less than 10% by weight, and / or less than 7% by weight, and / or less than 5% by weight, and / or less than 3% by weight to about 0% by weight or more than 0% by weight moisture, e.g., water, e.g., free water, based on the dry weight of the fibrous element, particle, and / or fibrous structure, when measured according to the Moisture Content Test Method described herein.

[0084] As used herein, for example, with respect to the total concentration of one or more active agents present within a fiber element, and / or particle, and / or fiber structure, "total concentration" means the sum of all weight or weight percent of the test material (e.g., active agent). In other words, the fiber elements and / or particles and / or fiber structures may comprise 25% by weight of anionic surfactant based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, 15% by weight of nonionic surfactant based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, 10% by weight of a chelating agent based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, and 5% by weight of fragrance based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, so that the total concentration of active agents present in the fiber elements and / or particles and / or fiber structures is greater than 50% by weight, i.e. 55% by weight, based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure.

[0085] "Solids" or "total solids" refers to any components other than water or solvent in a formulation that do not evaporate. As used herein, "high solids" refers to solids and / or total solids present in a concentration of greater than 15% by weight, and / or greater than 20% by weight, and / or at least 25% by weight, and / or at least 35% by weight, and / or at least 40% by weight, and / or at least 50% by weight up to about 100% by weight, or up to about 90% by weight, or up to about 80% by weight, or up to about 70% by weight, or up to about 60% by weight, and all ranges between these values.

[0086] "High surfactant" as in "high surfactant concentration" refers to the ratio of surfactant to fiber element forming material, e.g., natural polymer-based fiber element forming material, e.g., modified polysaccharides, e.g., modified starch (starch derivatives), e.g., acetylated starch (starch acetate), in the fiber element forming composition and / or fiber element of the present invention. Such surfactant present in the fiber element forming composition and / or fiber element is distinct and independent from any surfactant that may be present in particles, such as active agent-containing particles, present in the fiber structure and / or product of the present invention. In one embodiment, the weight ratio range of surfactant to fiber element forming material is from about 1:2 to about 5:1, and / or from about 1:1 to about 4:1, and / or from about 2:1 to about 3:1, and / or about 2:1.

[0087] As used herein, "fibrous structure product" refers to a solid form, such as a rectangular solid, that includes a plurality of fibrous elements and a plurality of particles, sometimes referred to as a sheet, in this case one or more of the fibrous structures of the present invention. The fibrous structure product includes one or more actives, such as foaming agents, fabric care actives, dishwashing actives, hard surface actives, and mixtures thereof, present in the fibrous structure and / or in the fibrous elements and / or particles of the fibrous structure product. In one embodiment, the fibrous structure product of the present invention includes one or more surfactants, one or more enzymes (such as in the form of granular enzymes), one or more fragrances, and / or one or more suds suppressors. In another embodiment, the fibrous structure product of the present invention includes a builder and / or a chelating agent. In another embodiment, the fibrous structure product of the present invention includes a bleaching agent (such as an encapsulated bleaching agent).

[0088] As used herein, "different morphology" or "different" means, with respect to a material, e.g., an entire fiber element, and / or a fiber element forming material within the fiber element, and / or an active agent within the fiber element, that one material, e.g., a fiber element, and / or a fiber element forming material, and / or an active agent, is chemically, physically, and / or structurally different from another material, e.g., a fiber element, and / or a fiber element forming material, and / or an active agent. For example, a fiber element forming material in the form of a filament is different from the same fiber element forming material in the form of a fiber. Similarly, a starch polymer is different from a cellulose polymer. However, the same material with different molecular weights, such as starches with different molecular weights, are not different materials from each other for the purposes of the present invention.

[0089] As used herein, a "random mixture of polymers" means that two or more different fiber element forming materials are randomly combined to form a fiber element. As a result, two or more different fiber element forming materials that are regularly combined to form a fiber element, such as a sheath-core bicomponent fiber element, are not random mixtures of different fiber element forming materials for purposes of the present invention.

[0090] As used herein with respect to fibrous elements and / or particles, "associate," "associated," "association," and / or "associating" refers to combining fibrous elements and / or particles by direct or indirect contact such that a fibrous structure is formed. In one embodiment, fibrous elements and / or particles that are joined may be adhered to one another by, for example, adhesive and / or thermal bonding. In another embodiment, fibrous elements and / or particles may be adhered to one another by being deposited on the same fibrous structure producing belt and / or patterned belt.

[0091] As used herein, "aperture" refers to an opening or void or depression in a fibrous structure that is distinct from the surrounding fibrous structure. In one embodiment, an aperture may include any feature where the fibrous structure is locally disrupted. In one embodiment, an aperture may include a localized depression or localized disruption of the basis weight, thickness, or caliper of the fibrous structure. In another embodiment, an aperture may be an opening in a fibrous structure that is substantially or completely through both generally planar surfaces of the fibrous structure, through one of the generally planar surfaces of the fibrous structure, or even through none of the planar surfaces of the fibrous structure. In another embodiment, an aperture may be an opening in a fibrous structure where there is a complete opening, a partial opening, or even no apparent opening. In yet another embodiment, an aperture may include an embossed feature in a fibrous structure. In yet another embodiment, an aperture is an internal feature of a fibrous structure and / or a multi-ply fibrous structure, for example, the opening feature may be on an internal ply of a multi-ply fibrous structure. In yet another embodiment, the openings include openings or voids or depressions in the fibrous structure that are non-random and / or designed and / or created openings, voids or depressions, rather than random holes that exist between the fibrous elements of the fibrous structure due to the assembly and entanglement of the fibrous elements on the collection device.

[0092] As used herein, "machine direction" or "MD" means the direction parallel to the direction in which a fibrous structure flows through a fibrous structure manufacturing equipment and / or a machine making a fibrous structure product.

[0093] As used herein, "cross machine direction" or "CD" means the coplanar direction of a fibrous structure and / or fibrous structure product comprising the fibrous structure that is perpendicular to the machine direction.

[0094] As used herein, a "ply" or "multiple plies" refers to an individual fibrous structure, optionally arranged in a substantially continuous face-to-face relationship with another ply to form a multi-ply fibrous structure. It is also contemplated that a single fibrous structure may be effectively formed into two or multiple "plies", for example, by folding over itself.

[0095] As used herein, the articles "a" and "an," such as, for example, "an anionic surfactant" or "a fiber," are understood to mean one or more of the materials claimed or described.

[0096] All percentages and ratios are calculated on a weight basis unless otherwise indicated. All percentages and ratios are calculated based on the total composition unless otherwise indicated.

[0097] Unless otherwise specified, all component or composition concentrations refer to the active level of that component or composition and are exclusive of impurities, e.g., residual solvents or by-products, that may be present in commercial sources.

[0098] Fiber Structure The fibrous structures of the present invention include a plurality of natural polymer-based fibrous elements, e.g., a plurality of natural polymer-based filaments, and, optionally, one or more particles, e.g., one or more active agent-containing particles, e.g., water-soluble active agent-containing particles.

[0099] In one embodiment, the fibrous elements and / or particles may be disposed within a fibrous structure to provide the fibrous structure with two or more regions containing different active agents, for example, one region of the fibrous structure may contain a bleaching agent and / or a surfactant, and another region of the fibrous structure may contain a softening agent.

[0100] Various non-limiting examples of fibrous structures and / or fibrous structure products according to the present invention are discussed below. Although the non-limiting examples described below illustrate particles that are part of the fibrous structure and / or fibrous structure product, the fibrous structure and / or fibrous structure product may not include such particles and may contain only fibrous elements, such as natural polymer-based fibrous elements.

[0101] As shown in Figure 1, an example of a fibrous structure 10 according to the present invention includes a first layer 12 including a plurality of fibrous elements 14, e.g., natural polymer based fibrous elements, in this case filaments, e.g., natural polymer based filaments, a second layer 16 including a plurality of fibrous elements 14, e.g., natural polymer based fibrous elements, in this case filaments, e.g., natural polymer based filaments, and a plurality of particles 18, e.g., active agent-containing particles, located between the first layer 12 and the second layer 16. A similar fibrous structure can be formed by depositing a plurality of particles, e.g., active agent-containing particles, on a surface of a first ply of a fibrous structure including a plurality of fibrous elements, e.g., natural polymer based fibrous elements, and then bonding a second ply of a fibrous structure including a plurality of fibrous elements, e.g., natural polymer based fibrous elements, such that the particles are located between the first ply and the second ply.

[0102] As shown in FIG. 2, another example of a fibrous structure 10 of the present invention includes a first layer 12 including a plurality of fibrous elements 14, e.g., natural polymer-based fibrous elements, in this case filaments, e.g., natural polymer-based filaments, which includes one or more pockets 20 (also called recesses) that may be in a non-random repeating pattern. One or more of the pockets 20 may contain one or more particles 18, e.g., active agent-containing particles. The fibrous structure 10 further includes a second layer 16 coupled to the first layer 12 such that the particles 18, e.g., active agent-containing particles, are captured in the pockets 20. As above, a similar fibrous structure can be formed by depositing a plurality of particles, e.g., active agent-containing particles, in the pockets of a first ply of a fibrous structure including a plurality of fibrous elements, e.g., natural polymer-based fibrous elements, and then combining a second ply of a fibrous structure including a plurality of fibrous elements, e.g., natural polymer-based fibrous elements, such that the particles, e.g., active agent-containing particles, are captured in the pockets of the first ply. In one example, the pocket may be separated from the fibrous structure to create a separate pocket.

[0103] As shown in Figure 3, an example of a multi-ply fibrous structure 22 of the present invention includes a first ply 24 of a fibrous structure according to Figure 2 above, and a second ply 26 of a fibrous structure, e.g., a fibrous structure according to the present invention, joined to the first ply 24, e.g., by an edge seam (not shown), the second ply 26 including a plurality of fibrous elements 14, e.g., natural polymer based fibrous elements, in this case filaments, e.g., natural polymer based filaments, and a plurality of particles 18, e.g., active agent-containing particles, distributed in this case randomly in the x-, y-, and z-axis directions across one or both plies and / or throughout the multi-ply fibrous structure. In other words, the particles, e.g., active agent-containing particles, e.g., water-soluble active agent-containing particles, are intermingled with the fibrous elements, e.g., natural polymer based fibrous elements, of one or both fibrous structure plies.

[0104] As shown in FIG. 4, an example fibrous structure 10 of the present invention includes a plurality of fibrous elements 14, e.g., natural polymer-based fibrous elements, in this case filaments, e.g., natural polymer-based filaments, and a plurality of particles 18, e.g., active agent-containing particles, dispersed in this case randomly throughout the fibrous structure 10 in the x-, y-, and z-axis directions.

[0105] Even if the fiber elements and / or fiber structures of the present invention are in solid form, the filament-forming composition used to make the fiber elements of the present invention may be in liquid form.

[0106] In one embodiment, the fibrous structure comprises a plurality of identical or substantially identical (in terms of composition) fibrous elements, such as natural polymer-based fibrous elements, and / or particles, such as active agent-containing particles, according to the present invention. In another embodiment, the fibrous structure may comprise two or more different fibrous elements, such as natural polymer-based fibrous elements, and / or particles, such as active agent-containing particles, according to the present invention. Non-limiting examples of differences between the fiber elements and / or particles can be physical differences such as differences in diameter, length, texture, shape, stiffness, elasticity; chemical differences such as crosslinking level, solubility, melting point, Tg, active agent, filament-forming material, color, concentration of active agent, basis weight, density, concentration of filament-forming material, presence of any coating on the fiber elements, biodegradable or not, hydrophobic or not, contact angle, etc.; differences in whether the fiber elements and / or particles lose their physical structure when exposed to the intended conditions of use; differences in whether the morphology of the fiber elements and / or particles changes when exposed to the intended conditions of use; and differences in the rate at which the fiber elements and / or particles release one or more of their active agents when exposed to the intended conditions of use. In one example, two or more fiber elements, e.g., natural polymer-based fiber elements, and / or particles, e.g., active agent-containing particles, within a fibrous structure may include different active agents. This may be the case when different actives, such as an anionic surfactant (eg, a shampoo active) and a cationic surfactant (eg, a hair conditioner active), are not compatible with each other.

[0107] In another example, the fibrous structure may exhibit different regions, e.g., regions of different basis weight, density, and / or thickness. In yet another example, the fibrous structure may include a texture on one or more of its surfaces. The surface of the fibrous structure may include a pattern, such as a non-random repeating pattern. The fibrous structure may be embossed with an embossed pattern. In another example, the fibrous structure may include apertures. The apertures may be arranged in a non-random repeating pattern.

[0108] In another embodiment of the invention, the fibrous structure includes one or more apertures and is therefore a perforated fibrous structure. In one embodiment, the fibrous structure includes a plurality of apertures. The apertures may be arranged in a pattern, e.g., a repeating pattern, such as a non-random repeating pattern, and / or a non-repeating pattern.

[0109] The openings in the perforated fibrous structures of the present invention can be of virtually any shape and size. In one embodiment, the openings in the perforated fibrous structures are generally circular or elliptical spaced openings in a regular pattern. In one embodiment, the fibrous structure includes two or more openings spaced apart from each other by a distance of about 0.2 mm to about 100 mm and / or about 0.5 mm to about 10 mm.

[0110] Perforation of fibrous structures, such as soluble fibrous structures, such as water-soluble fibrous structures, can be achieved by any number of techniques. For example, apertures can be achieved by various processes involving bonding and stretching, such as those described in U.S. Pat. Nos. 3,949,127 and 5,873,868. In one embodiment, apertures can be formed by forming a plurality of spaced apart melt-stabilized regions, and then ring-rolling the web to stretch the web and form apertures in the melt-stabilized regions, as described in U.S. Pat. Nos. 5,628,097 and 5,916,661, both of which are incorporated herein by reference. In another embodiment, apertures can be formed during construction of a multi-layered fibrous structure by the methods described in U.S. Pat. Nos. 6,830,800, 6,863,960, 8,241,543, and 10,792,229, both of which are incorporated herein by reference. Non-limiting examples of processes for imparting apertures to the fibrous structures of the present invention include embossing, lodging, rotary knife perforation, pinning, die cutting, die punching, needle punching, knurling, crush cutting, shear cutting, pneumatic forming, hydroforming, laser cutting, and tufting. In one embodiment, the fibrous structures of the present invention include apertures imparted by pinning. In another embodiment, the fibrous structures of the present invention include apertures imparted by lodging. In another embodiment, the fibrous structures of the present invention include apertures imparted by rotary knife perforation. In yet another embodiment, the fibrous structures of the present invention may include apertures imparted to the fibrous structures by different types of perforation processes.

[0111] In one embodiment, apertures can be imparted to the fibrous structure while it is being formed on a collecting device, such as a patterned belt, having features, e.g., recesses and / or protrusions, that impart apertures to the fibrous structure when the fibrous elements contact the collecting device during formation.

[0112] In one embodiment, the fibrous structure may include separate regions of fibrous elements that are distinct from other portions of the fibrous structure.

[0113] Non-limiting examples of applications for the fibrous structures of the present invention include, but are not limited to, washer dryer substrates, washing machine substrates, bath towels, hard surface cleaning and / or polishing substrates, floor cleaning and / or polishing substrates, components in batteries, baby wipes, adult wipes, feminine hygiene wipes, toilet paper wipes, window cleaning substrates, oil containment and / or cleaning substrates, insect control substrates, swimming pool chemical substrates, food, breath fresheners, deodorants, garbage disposal bags, packaging films and / or wraps, wound dressings, pharmaceutical delivery, building insulation, crop and / or plant covers and / or beds, starch substrates, skin care substrates, hair care substrates, air care agents, water treatment substrates and / or filters, toilet bowl cleaning substrates, candy substrates, pet food, livestock bedding, tooth whitening substrates, carpet cleaning substrates, and other suitable applications for the active agents of the present invention.

[0114] The fibrous structures of the present invention may be used as is or may be coated with one or more active agents.

[0115] In one example, the article, e.g., the fibrous structure of the present invention, may exhibit an average disintegration time of less than 360 seconds, and / or less than 200 seconds, and / or less than 100 seconds, and / or less than 60 seconds, and / or less than 30 seconds, and / or less than 10 seconds, and / or less than 5 seconds, and / or less than 2.0 seconds, and / or less than 1.5 seconds, and / or about 0 seconds, and / or greater than 0 seconds, when measured according to the dissolution test method described herein.

[0116] In one example, an article, such as a fibrous structure of the present invention, may exhibit an average dissolution time of less than 3600 seconds, and / or less than 3000 seconds, and / or less than 2400 seconds, and / or less than 1800 seconds, and / or less than 1200 seconds, and / or less than 600 seconds, and / or less than 400 seconds, and / or less than 300 seconds, and / or less than 200 seconds, and / or less than 175 seconds, and / or less than 100 seconds, and / or less than 50 seconds, and / or more than 1 second when measured according to the dissolution test method described herein.

[0117] In another embodiment, the articles, e.g., fibrous structures of the present invention, exhibit an average dissolution time, when measured according to the dissolution test methods described herein, of less than 24 hours, and / or less than 12 hours, and / or less than 6 hours, and / or less than 1 hour (3600 seconds), and / or less than 30 minutes, and / or less than 25 minutes, and / or less than 20 minutes, and / or less than 15 minutes, and / or less than 10 minutes, and / or less than 5 minutes, and / or greater than 1 second, and / or greater than 5 seconds, and / or greater than 10 seconds, and / or greater than 30 seconds, and / or greater than 1 minute.

[0118] In one example, an article, such as a fibrous structure of the present invention, may exhibit an average disintegration time per gsm of sample of about 1.0 seconds / gsm (s / gsm) or less, and / or about 0.5 s / gsm or less, and / or about 0.2 s / gsm or less, and / or about 0.1 s / gsm or less, and / or about 0.05 s / gsm or less, and / or about 0.03 s / gsm or less, when measured according to the dissolution test method described herein.

[0119] In one example, an article, such as a fibrous structure of the present invention, may exhibit an average dissolution time per gsm of sample of about 10 seconds / gsm (s / gsm) or less, and / or about 5.0 s / gsm or less, and / or about 3.0 s / gsm or less, and / or about 2.0 s / gsm or less, and / or about 1.8 s / gsm or less, and / or about 1.5 s / gsm or less, when measured according to the dissolution test method described herein.

[0120] In one embodiment, the fibrous structure of the present invention exhibits a thickness of greater than 0.01 mm, and / or greater than 0.05 mm, and / or greater than 0.1 mm to about 100 mm, or to about 50 mm, or to about 20 mm, or to about 10 mm, or to about 5 mm, or to about 2 mm, or to 0.5 mm, or to about 0.3 mm, when measured according to the Thickness Test Method described herein.

[0121] In one embodiment, the fibrous structure of the present invention comprises a plurality of fibrous elements, e.g., natural polymer-based fibrous element forming materials, at a total concentration of less than 80% by weight of the dry fibrous elements, and one or more active agents, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, at a total concentration of more than 20% by weight of the dry fibrous elements.

[0122] In one embodiment, the fibrous structure of the present invention comprises a plurality of fibrous elements, e.g., natural polymer-based fibrous element forming materials, comprising one or more fibrous element forming materials, e.g., natural polymer-based fibrous element forming materials, at a total concentration of less than 70% by weight of the dry fibrous elements, and one or more active agents, comprising a surfactant or surfactant mixture and optionally an additional non-surfactant active agent, at a total concentration of more than 30% by weight of the dry fibrous elements.

[0123] In one embodiment, the fibrous structure of the present invention comprises a plurality of fibrous elements, e.g., natural polymer-based fibrous element forming materials, comprising one or more fibrous element forming materials, e.g., natural polymer-based fibrous element forming materials, at a total concentration of less than 60% by weight of the dry fibrous elements, and one or more active agents, comprising a surfactant or surfactant mixture and optionally an additional non-surfactant active agent, at a total concentration of more than 40% by weight of the dry fibrous elements.

[0124] In one embodiment, the fibrous structure of the present invention comprises a plurality of fibrous elements, e.g., natural polymer-based fibrous element forming materials, at a total concentration of about 50% by weight of the dry fibrous elements, and one or more active agents, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, at a total concentration of about 50% by weight of the dry fibrous elements.

[0125] In one embodiment, the fibrous structure of the present invention comprises a plurality of fibrous elements, e.g., natural polymer-based fibrous element forming materials, comprising one or more fibrous element forming materials, e.g., natural polymer-based fibrous element forming materials, at a total concentration of less than 40% by weight of the dry fibrous elements, and one or more active agents, comprising a surfactant or surfactant mixture and optionally additional non-surfactant active agents, at a total concentration of more than 60% by weight of the dry fibrous elements.

[0126] In one embodiment, the fibrous structure of the present invention comprises a plurality of fibrous elements, e.g., natural polymer-based fibrous elements, comprising one or more fibrous element-forming materials, natural polymer-based fibrous element-forming materials, at a total concentration of less than 30% by weight of the dry fibrous elements, and one or more active agents, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, at a total concentration of more than 70% by weight of the dry fibrous elements.

[0127] In one embodiment, the fibrous structure of the present invention comprises a plurality of fibrous elements, e.g., natural polymer-based fibrous elements, comprising a fibrous element-forming material, e.g., a natural polymer-based fibrous element-forming material, such as a modified polysaccharide, e.g., a modified starch, e.g., acetylated starch, and a plurality of fibrous elements, e.g., natural polymer-based fibrous elements, comprising one or more active agents, e.g., a surfactant or surfactant mixture, e.g., a linear alkylbenzene sulfonate and an alkyl sulfate, wherein the surfactant or surfactant mixture and the fibrous element-forming material, e.g., the natural polymer-based material, e.g., acetylated starch, are present in the fibrous structure in a weight ratio of surfactant or surfactant mixture to natural polymer-based fibrous element-forming material, e.g., acetylated starch, of about 0.15:1 to about 6:1, and / or about 0.20:1 to about 5.5:1, and / or about 0.25:1 to about 5:1, and / or about 0.5:1 to about 2:1.

[0128] In one embodiment, the surfactant and / or surfactant mixture present in the fibrous structure and / or fibrous elements and / or particles of the present invention may comprise a surfactant suitable for beauty and / or personal care applications such as hand washes, facial cleansers, body washes, shampoos, and other hair cleansing and / or conditioning applications. Non-limiting examples of surfactants suitable for cosmetic and / or personal care applications include, but are not limited to, ammonium lauryl sulfate, ammonium laureth sulfate, triethylamine lauryl sulfate, triethylamine laureth sulfate, triethanolamine lauryl sulfate, triethanolamine laureth sulfate, monoethanolamine lauryl sulfate, monoethanolamine laureth sulfate, diethanolamine lauryl sulfate, diethanolamine laureth sulfate, lauryl monoglyceride sodium sulfate, sodium lauryl sulfate, sodium laureth sulfate, potassium lauryl sulfate, potassium laureth sulfate, sodium lauryl sarcosinate, sodium lauroyl sarcosinate, lauryl sarcosine, cocoyl sarcosine, ammonium cocoyl sulfate, ammonium lauroyl sulfate, sodium cocoyl sulfate, sodium lauroyl sulfate, potassium cocoyl sulfate, potassium lauryl sulfate, triethanolamine lauryl sulfate, triethanolamine lauryl sulfate, monoethanolamine cocoyl sulfate, monoethanolamine lauryl sulfate, sodium tridecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sodium cocoyl isethionate, and combinations thereof. In one embodiment, the surfactant and / or surfactant mixture comprises one or more sulfate-free surfactants and / or 100% sulfate-free surfactants.

[0129] In one embodiment, the fibrous structure and / or fibrous element and / or particle comprising a plurality of fibrous elements of the present invention further comprises a coating composition, e.g., a coating composition comprising one or more active agents, present on the exterior surface of the fibrous structure and / or fibrous element and / or particle.

[0130] In one embodiment, the fibrous structure and / or fibrous elements and / or particles of the present invention comprise a natural polymeric material, such as a modified polysaccharide, such as a modified starch, such as an acetylated starch, and two or more different active agents, at least one of which is a surfactant or a mixture of surfactants.

[0131] In one embodiment, the fibrous structure and / or fibrous elements and / or particles of the present invention exhibit a moisture content of from 0% to about 20% and / or from greater than 0% to less than 15% when measured according to the Moisture Content Test Method.

[0132] The fibrous structures, fibrous elements, and fibrous element-forming compositions of the present invention may or may not include a stretching aid, in other words, in one embodiment, the fibrous elements of the present invention can be spun from the fibrous element-forming composition without the need for a stretching aid.

[0133] Textile elements The fiber elements, e.g., natural polymer-based fiber elements, may be water-soluble or water-insoluble. In one embodiment, the fiber elements, e.g., natural polymer-based fiber elements, include one or more filament-forming materials, e.g., natural polymer-based fiber element-forming materials. In another embodiment, the fiber elements, e.g., natural polymer-based fiber elements, include one or more active agents. In yet another embodiment, the fiber elements, e.g., natural polymer-based fiber elements, include one or more filament-forming materials, e.g., natural polymer-based fiber element-forming materials, and one or more active agents. In another embodiment, the fiber elements, e.g., natural polymer-based fiber elements, are water-soluble natural polymer-based fiber elements.

[0134] The fibrous elements, e.g., natural polymer-based fibrous elements, e.g., filaments and / or fibers, e.g., natural polymer-based filaments and / or natural polymer-based fibers, of the present invention comprise one or more filament-forming materials, e.g., natural polymer-based fibrous element-forming materials. In addition to the filament-forming materials, the fibrous elements, e.g., natural polymer-based fibrous elements, may further comprise one or more active agents releasable from the fibrous elements, e.g., when the fibrous elements and / or fibrous structures comprising the fibrous elements are exposed to intended use conditions. In one embodiment, the total concentration of one or more filament-forming materials, e.g., natural polymer-based fibrous element-forming materials, present in the fibrous elements, e.g., natural polymer-based fibrous elements, and / or a plurality of fibrous elements, is less than 80% by weight based on the dry fibrous elements and / or the dry fibrous structures, and the total concentration of one or more active agents present in the fibrous elements, e.g., natural polymer-based fibrous elements and / or a plurality of fibrous elements, is more than 20% by weight based on the dry fibrous elements and / or the dry fibrous structures.

[0135] In one embodiment, the fibrous element, e.g., natural polymer-based fibrous element, and / or a plurality of fibrous elements of the present invention comprises about 100% by weight, and / or more than 95% by weight, and / or more than 90% by weight, and / or more than 85% by weight, and / or more than 75% by weight, and / or more than 50% by weight of one or more filament-forming materials, e.g., natural polymer-based fibrous element-forming materials, e.g., modified polysaccharides, e.g., modified starch, e.g., acetylated starch, based on the dry fibrous element and / or on the dry fibrous structure.

[0136] In another embodiment, the fibrous element, e.g., natural polymer-based fibrous element, and / or a plurality of fibrous elements of the present invention comprises one or more filament-forming materials, e.g., natural polymer-based fibrous element-forming materials, e.g., modified polysaccharides, e.g., modified starches, e.g., acetylated starch, and one or more active agents, at least one of which comprises a surfactant, e.g., a surfactant mixture comprising two or more surfactants, such as linear alkylbenzene sulfonate and alkyl sulfate, and the total concentration of the filament-forming materials, e.g., natural polymer-based fibrous element-forming materials, present in the fibrous element, e.g., natural polymer-based fibrous element, and / or a plurality of fibrous elements, is between about 5% and less than 80% by weight, based on the dry fibrous element and / or on the dry fibrous structure, and the total concentration of the active agents, including the surfactant or surfactant mixture and optionally one or more additional non-surfactant active agents, present in the fibrous element, e.g., natural polymer-based fibrous element, and / or a plurality of fibrous elements, is between more than 20% and about 95% by weight, based on the dry fibrous element and / or on the dry fibrous structure.

[0137] In one embodiment, the fibrous element of the present invention, e.g., a natural polymer based fibrous element, and / or a plurality of fibrous elements, comprises at least 10% by weight, and / or at least 15% by weight, and / or at least 20% by weight, and / or less than 80% by weight, and / or less than 75% by weight, and / or less than 65% by weight, and / or less than 60% by weight, and / or less than 55% by weight, and / or less than 50% by weight, and / or less than 45% by weight, and / or less than 40% by weight of a filament forming material, e.g., a natural polymer, based on the dry fibrous element and / or on the dry fibrous structure. The system comprises a fiber element forming material and more than 20% by weight, and / or at least 35% by weight, and / or at least 40% by weight, and / or at least 45% by weight, and / or at least 50% by weight, and / or at least 60% by weight, and / or less than 95% by weight, and / or less than 90% by weight, and / or less than 85% by weight, and / or less than 80% by weight, and / or less than 75% by weight of a surfactant or surfactant mixture and optionally one or more additional non-surfactant active agents, based on the dry fiber elements and / or on the dry fiber structure.

[0138] In one embodiment, the fibrous element of the present invention, e.g., a natural polymer based fibrous element, and / or a plurality of fibrous elements, comprises at least 5% by weight, and / or at least 10% by weight, and / or at least 15% by weight, and / or at least 20% by weight, and / or less than 50% by weight, and / or less than 45% by weight, and / or less than 40% by weight, and / or less than 35% by weight, and / or less than 30% by weight, and / or less than 25% by weight of filament forming material, e.g., natural polymer, based on the dry fibrous element and / or on the dry fibrous structure. The natural polymer-based fiber element forming material comprises more than 50% by weight, and / or at least 55% by weight, and / or at least 60% by weight, and / or at least 65% by weight, and / or at least 70% by weight, and / or less than 95% by weight, and / or less than 90% by weight, and / or less than 85% by weight, and / or less than 80% by weight, and / or less than 75% by weight of an active agent comprising a surfactant or a surfactant mixture and optionally one or more additional non-surfactant active agents, based on the dry fiber element and / or on the dry fiber structure. In one embodiment, the fiber element, e.g., the natural polymer-based fiber element and / or a plurality of fiber elements of the present invention comprises more than 80% by weight, based on the dry fiber element and / or on the dry fiber structure, of an active agent comprising a surfactant or a surfactant mixture and optionally one or more additional non-surfactant active agents.

[0139] In one embodiment, the fiber element of the present invention, e.g. a natural polymer-based fiber element and / or a plurality of fiber elements, comprises a modified polysaccharide in a total concentration of less than 80% by weight of the dry fiber element and a surfactant in a total concentration of more than 20% by weight of the dry fiber element.

[0140] In one embodiment, the fiber element of the present invention, e.g. a natural polymer-based fiber element and / or a plurality of fiber elements, comprises a modified polysaccharide in a total concentration of less than 70% by weight of the dry fiber element and a surfactant in a total concentration of more than 30% by weight of the dry fiber element.

[0141] In one embodiment, the fiber element of the present invention, e.g. a natural polymer-based fiber element and / or a plurality of fiber elements, comprises a modified polysaccharide in a total concentration of less than 60% by weight of the dry fiber element and a surfactant in a total concentration of more than 40% by weight of the dry fiber element.

[0142] In one embodiment, the fiber element of the present invention, e.g., a natural polymer-based fiber element and / or a plurality of fiber elements, comprises a modified polysaccharide in a total concentration of about 50% by weight of the dry fiber element and a surfactant in a total concentration of about 50% by weight of the dry fiber element.

[0143] In one embodiment, the fiber element of the present invention, e.g. a natural polymer-based fiber element and / or a plurality of fiber elements, comprises a modified polysaccharide in a total concentration of less than 40% by weight of the dry fiber element and a surfactant in a total concentration of more than 60% by weight of the dry fiber element.

[0144] In one embodiment, the fiber element, e.g., a natural polymer-based fiber element and / or a plurality of fiber elements, comprises a modified polysaccharide in a total concentration of less than 30% by weight of the dry fiber element and a surfactant in a total concentration of more than 70% by weight of the dry fiber element.

[0145] In one embodiment, the fibrous element of the invention, e.g. the natural polymer based fibrous element and / or plurality of fibrous elements, comprises a modified polysaccharide and a surfactant or surfactant mixture present in the dry fibrous element in a weight ratio of modified polysaccharide to surfactant of less than or equal to 1. The surfactant system and / or surfactant mixture may comprise one or more surfactants selected from the group consisting of anionic surfactants, cationic surfactants, nonionic surfactants, zwitterionic surfactants, amphoteric surfactants, and mixtures thereof.

[0146] In one embodiment, the fibrous element, e.g., natural polymer-based fibrous element and / or plurality of fibrous elements of the present invention comprises a modified polysaccharide present in the dry fibrous element in a weight ratio of modified polysaccharide to surfactant of less than or equal to 1, and one or more active agents comprising a surfactant or surfactant mixture and optionally a non-surfactant active agent. The surfactant and / or surfactant mixture may comprise one or more surfactants selected from the group consisting of anionic surfactants, cationic surfactants, non-ionic surfactants, zwitterionic surfactants, amphoteric surfactants, and mixtures thereof, and the non-surfactant active agent may be selected from the group consisting of skin care actives, medicaments, lotions, fabric care actives, dishwashing actives, carpet care actives, surface care actives, hair care actives, air care actives, dental care actives, and mixtures thereof.

[0147] In another embodiment, the one or more filament-forming materials, e.g., natural polymer based fiber element forming materials, and the active agent, including a surfactant or surfactant mixture and optionally one or more additional non-surfactant active agents, are present in the fiber element, e.g., natural polymer based fiber element, and / or a plurality of fiber elements, in a weight ratio of filament-forming materials, e.g., natural polymer based fiber element forming materials, to active agent and total concentration of active agent, e.g., surfactant or surfactant mixture, of 4.0 or less, and / or 3.5 or less, and / or 3.0 or less, and / or 2.5 or less, and / or 2.0 or less, and / or 1.85 or less, and / or less than 1.7, and / or less than 1.6, and / or less than 1.5, and / or less than 1.3, and / or less than 1.2, and / or less than 1, and / or less than 0.7, and / or less than 0.5, and / or less than 0.4, and / or less than 0.3, and / or greater than 0.1, and / or greater than 0.15, and / or greater than 0.2.

[0148] In one embodiment, a fiber element, e.g., a natural polymer-based fiber element, and / or a plurality of fiber elements of the present invention comprises one or more fiber element forming materials, e.g., a natural polymer-based fiber element forming material, and one or more active agents comprising a surfactant or surfactant mixture, with a weight ratio of fiber element forming material to active agent being 1 or less.

[0149] In yet another embodiment, the fibrous element, e.g., natural polymer-based fibrous element, and / or plurality of fibrous elements of the present invention comprises about 10% and / or about 15% to less than 80% by weight of a filament-forming material, e.g., a natural polymer-based fibrous element-forming material, e.g., a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch, based on the dry fibrous element and / or on the dry fibrous structure, and from more than 20% to about 90% or about 85% by weight of an active agent, e.g., a surfactant or surfactant mixture, based on the dry fibrous element and / or on the dry fibrous structure. The fibrous element may further comprise a plasticizer (e.g., glycerin) and / or a pH adjuster (e.g., citric acid).

[0150] In yet another embodiment, the fibrous element, e.g., natural polymer-based fibrous element and / or plurality of fibrous elements, of the present invention comprises from about 10% and / or from about 15% to less than 80% by weight of a filament-forming material, e.g., a natural polymer-based filament-forming material, e.g., a modified polysaccharide, e.g., a modified starch, e.g., an acetylated starch, based on the dry fibrous element and / or on the dry fibrous structure, and from more than 20% to about 90% and / or to about 85% by weight of an active agent, based on the dry fibrous element and / or on the dry fibrous structure, the weight ratio of the filament-forming material to the active agent, e.g., a surfactant or surfactant mixture, being 4.0 or less. The fibrous element, e.g., natural polymer-based fibrous element and / or plurality of fibrous elements may further comprise a plasticizer, e.g., glycerin, and / or a pH adjuster, e.g., citric acid.

[0151] In yet another embodiment of the present invention, the fibrous element, e.g., the natural polymer-based fibrous element, and / or the plurality of fibrous elements, comprises one or more filament-forming materials, e.g., natural polymer-based fibrous element-forming materials, and one or more active agents selected from the group consisting of enzymes, bleaching agents, builders, chelating agents, sensates, dispersants, and mixtures thereof, which are releasable and / or released when the fibrous element and / or the fibrous structure comprising the fibrous element is exposed to the intended use conditions. In one embodiment, the fibrous element, e.g., the natural polymer-based fibrous element, and / or the plurality of fibrous elements, comprises a total concentration of ... based on the dry fibrous element and / or on the dry fibrous structure, of less than 95% by weight, based on the dry fibrous element and / or on the dry fibrous structure, of less than 90% by weight, based on the dry fibrous element and / or on the dry fibrous structure, of less than 80% by weight, based on the dry fibrous element and / or on the dry fibrous structure, of less than and a surfactant or mixture of surfactants and optionally one or more additional active agents selected from the group consisting of enzymes, bleaching agents, builders, chelating agents, fragrances, antimicrobial agents, antibacterial agents, antifungal agents, and mixtures thereof, at a total concentration of greater than 5% and / or greater than 10% and / or greater than 20% and / or greater than 35% and / or greater than 50% and / or greater than 65% by weight based on the fiber structure up to about 95% or up to about 90% or up to about 80% by weight. In one embodiment, the active agent comprises one or more enzymes. In another embodiment, the active agent comprises one or more bleaching agents. In yet another embodiment, the active agent comprises one or more builders. In yet another embodiment, the active agent comprises one or more chelating agents. In yet another embodiment, the active agent comprises one or more fragrances. In yet another embodiment, the active agent comprises one or more antimicrobial agents, antibacterial agents, and / or antifungal agents.

[0152] In yet another embodiment of the present invention, the textile elements of the present invention, such as natural polymer-based textile elements, can safely contain active agents that would otherwise pose health and / or safety concerns if released into the air. For example, the textile elements, such as natural polymer-based textile elements, can be used to inhibit enzymes within the textile elements from becoming airborne.

[0153] In one embodiment, the fiber elements of the present invention, such as natural polymer-based fiber elements, can be meltblown fiber elements. In another embodiment, the fiber elements of the present invention, such as natural polymer-based fiber elements, can be spunbond fiber elements. In another embodiment, the fiber elements, such as natural polymer-based fiber elements, can be hollow fiber elements before and / or after the one or more active agents thereof are released.

[0154] The textile elements of the present invention, such as natural polymer-based textile elements, may be hydrophilic or hydrophobic. To change the inherent hydrophilicity or hydrophobicity of the textile elements, such as natural polymer-based textile elements, they may be surface- and / or internally treated.

[0155] In one embodiment, the fiber elements of the invention, such as the natural polymer-based fiber elements and / or fiber elements, exhibit a diameter of less than 100 μm, and / or less than 75 μm, and / or less than 50 μm, and / or less than 25 μm, and / or less than 10 μm, and / or less than 5 μm, and / or less than 1 μm, when measured according to the Diameter Test Method described herein. In another embodiment, the fiber elements of the invention, such as the natural polymer-based fiber elements and / or fiber elements, exhibit a diameter of more than 1 μm, when measured according to the Diameter Test Method described herein. The diameter of the fiber elements of the invention may be used to control the release rate of one or more active agents present in the fiber elements and / or the rate of loss and / or change of the physical structure of the fiber elements.

[0156] A fiber element, such as a natural polymer-based fiber element, may include two or more different active agents, including a surfactant or surfactant mixture and optionally an additional non-surfactant active agent. In one embodiment, the fiber element includes two or more different active agents, where the two or more different active agents are compatible with each other. In another embodiment, the fiber element includes two or more different active agents, where the two or more different active agents are incompatible with each other.

[0157] In one example, a fiber element, such as a natural polymer-based fiber element, may include an active agent comprising a surfactant or surfactant mixture within the fiber element and an active agent on an exterior surface of the fiber element, such as an active agent coating on the fiber element. The active agent on the exterior surface of the fiber element may be the same as or different from the active agent present within the fiber element. If different, the active agents may be compatible or incompatible with each other.

[0158] In one example, the one or more active agents, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, may be uniformly or substantially uniformly distributed throughout the fiber element, e.g., a natural polymer-based fiber element. In another example, the one or more active agents, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, may be distributed as distinct regions within the fiber element. In yet another example, at least one active agent, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, is uniformly or substantially uniformly distributed throughout the fiber element, e.g., a natural polymer-based fiber element, and at least one other active agent is distributed as one or more distinct regions within the fiber element. In yet another example, at least one active agent, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, is distributed as one or more distinct regions within the fiber element, and at least one other active agent is distributed as one or more distinct regions within the fiber element that are different from the first distinct region.

[0159] In one embodiment, the fiber element, e.g., natural polymer based fiber element and / or plurality of fiber elements of the present invention, has a DS of about 0.1 to about 1.0, and / or about 0.2 to about 0.9, and / or about 0.2 to about 0.8, and / or about 0.3 to about 0.7, a DS of about 25,000 to about 450,000 g / mol, and / or about 35,000 to about 400,000 g / mol, and / or a β of about 35,000 to about 350 one or more fiber element forming materials, for example one or more natural polymer-based fiber element forming materials, for example modified polysaccharides, for example modified starches, for example acetylated starches, having a weight average molecular weight of about 45,000 to about 300,000 g / mol, and / or about 50,000 to about 300,000 g / mol, and / or about 50,000 to about 250,000 g / mol; the fiber element further comprises a mixture or blend of surfactants including linear alkylbenzene sulfonates and alkyl sulfates, the fiber element being derived from a fiber element-forming composition exhibiting a viscosity of from about 0.01 Pa·s to about 1.2 Pa·s and / or from about 0.02 Pa·s to about 1.0 Pa·s when measured according to a rotational rheometer test method, the fiber element-forming composition comprising the surfactant mixture and one or more natural polymeric fiber element-forming materials, such as acetylated starch, in a weight ratio of from about 0.15:1 to about 6:1, and / or from about 0.20:1 to about 5.5:1, and / or from about 0.25:1 to about 5:1, and / or from about 0.5:1 to about 2:1, e.g., 2:1, and the aqueous composition further comprises from about 55% to about 85% by weight water, e.g., about 55% by weight water.

[0160] In one embodiment, the surfactant and / or surfactant mixture present in the fiber element of the present invention may comprise surfactants suitable for beauty and / or personal care applications such as hand washes, facial cleansers, body washes, shampoos, and other hair cleaning and / or conditioning applications. Non-limiting examples of surfactants suitable for cosmetic and / or personal care applications include, but are not limited to, ammonium lauryl sulfate, ammonium laureth sulfate, triethylamine lauryl sulfate, triethylamine laureth sulfate, triethanolamine lauryl sulfate, triethanolamine laureth sulfate, monoethanolamine lauryl sulfate, monoethanolamine laureth sulfate, diethanolamine lauryl sulfate, diethanolamine laureth sulfate, lauryl monoglyceride sodium sulfate, sodium lauryl sulfate, sodium laureth sulfate, potassium lauryl sulfate, potassium laureth sulfate, sodium lauryl sarcosinate, sodium lauroyl sarcosinate, lauryl sarcosine, cocoyl sarcosine, ammonium cocoyl sulfate, ammonium lauroyl sulfate, sodium cocoyl sulfate, sodium lauroyl sulfate, potassium cocoyl sulfate, potassium lauryl sulfate, triethanolamine lauryl sulfate, triethanolamine lauryl sulfate, monoethanolamine cocoyl sulfate, monoethanolamine lauryl sulfate, sodium tridecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sodium cocoyl isethionate, and combinations thereof. In one embodiment, the surfactant and / or surfactant mixture comprises one or more sulfate-free surfactants and / or 100% sulfate-free surfactants.

[0161] In one embodiment, a plurality of fiber elements of the present invention exhibit an average diameter of less than 50 μm as measured according to the Diameter Test Method.

[0162] In one embodiment, the plurality of fiber elements includes two or more different fiber element forming materials, for example natural polymer-based fiber element forming materials.

[0163] In one embodiment, a plurality of fiber elements of the present invention comprises two or more different active agents, at least one of which is a surfactant or mixture of surfactants.

[0164] In one embodiment, a plurality of fiber elements of the present invention further comprises a coating composition, for example a coating composition comprising one or more active agents, present on an exterior surface of the plurality of fiber elements.

[0165] In one embodiment, a plurality of fibrous elements of the present invention exhibits a moisture content of from about 0% to about 20% and / or from greater than about 0% to less than about 15% when measured according to the Moisture Content Test Method.

[0166] The fiber elements of the present invention are made from a fiber element forming composition, e.g., a filament forming composition, that includes one or more fiber element forming materials, e.g., a natural polymer-based fiber element forming material, one or more active agents, including a surfactant or surfactant mixture and optionally additional non-surfactant active agents, and optionally a polar solvent, such as water, that solubilizes the fiber element forming materials and the active agents. In one embodiment, the fiber element forming composition includes a polar solvent, e.g., water, one or more fiber element forming materials, at least one of which is a modified polysaccharide, and one or more active agents, at least one of which includes a surfactant, and the surfactant and the modified polysaccharide are present in the fiber element forming composition in a weight ratio of about 0.25:1 to about 5:1.

[0167] In one embodiment, the surfactant and / or surfactant mixture present in the fiber element forming composition of the present invention may comprise a surfactant suitable for beauty and / or personal care applications such as hand washes, facial cleansers, body washes, shampoos, and other hair cleansing and / or conditioning applications. Non-limiting examples of surfactants suitable for cosmetic and / or personal care applications include, but are not limited to, ammonium lauryl sulfate, ammonium laureth sulfate, triethylamine lauryl sulfate, triethylamine laureth sulfate, triethanolamine lauryl sulfate, triethanolamine laureth sulfate, monoethanolamine lauryl sulfate, monoethanolamine laureth sulfate, diethanolamine lauryl sulfate, diethanolamine laureth sulfate, lauryl monoglyceride sodium sulfate, sodium lauryl sulfate, sodium laureth sulfate, potassium lauryl sulfate, potassium laureth sulfate, sodium lauryl sarcosinate, sodium lauroyl sarcosinate, lauryl sarcosine, cocoyl sarcosine, ammonium cocoyl sulfate, ammonium lauroyl sulfate, sodium cocoyl sulfate, sodium lauroyl sulfate, potassium cocoyl sulfate, potassium lauryl sulfate, triethanolamine lauryl sulfate, triethanolamine lauryl sulfate, monoethanolamine cocoyl sulfate, monoethanolamine lauryl sulfate, sodium tridecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sodium cocoyl isethionate, and combinations thereof. In one embodiment, the surfactant and / or surfactant mixture comprises one or more sulfate-free surfactants and / or 100% sulfate-free surfactants.

[0168] In one embodiment, a method of making a fiber element of the present invention, such as a natural polymer based fiber element and / or a plurality of fiber elements, comprises the steps of: a. providing a fiber element forming composition comprising one or more fiber element forming materials, such as a natural polymer-based fiber element forming material, such as a modified polysaccharide, such as a modified starch, such as acetylated starch, and one or more active agents, including a surfactant or a surfactant mixture including linear alkylbenzene sulfonate and alkyl sulfate, wherein the weight ratio of the surfactant or surfactant mixture to the natural polymer-based fiber element forming material is about 0.5:1 to about 2:1, the fiber element forming composition comprising the surfactant or surfactant mixture and the natural polymer-based fiber element forming material, such as acetylated starch; b. spinning the fiber element forming composition, for example from a multi-row capillary die, into one or more fiber elements, for example a natural polymer-based fiber element and / or a plurality of fiber elements, comprising a natural polymer-based fiber element forming material, such as acetylated starch, and a surfactant or surfactant mixture.

[0169] In one embodiment, the fiber element forming composition includes a polar solvent such as water, one or more fiber element forming materials, such as a natural polymer-based fiber element forming material, including acetylated starch, and a surfactant or surfactant mixture including a linear alkylbenzene sulfonate and an alkyl sulfate. The fiber element forming composition may exhibit a viscosity of about 0.01 Pa·s to about 1.2 Pa·s and / or about 0.02 Pa·s to about 1.0 Pa·s when measured according to a rotational rheometer test method.

[0170] Fiber element forming material The fiber element forming material is any suitable natural polymer-based material, e.g., modified natural polymer or monomer, capable of producing a modified natural polymer exhibiting suitable properties for producing fiber elements, e.g., natural polymer-based fiber elements, e.g., filaments, e.g., natural polymer-based filaments, such as by a spinning process.

[0171] In one embodiment, the fiber element forming material may include a polar solvent soluble natural polymer-based material, such as an alcohol soluble natural polymer-based material and / or a water soluble natural polymer-based material.

[0172] In another embodiment, the material forming the fiber elements may include a non-polar solvent soluble natural polymer-based material.

[0173] In yet another embodiment, the fibrous element forming material may comprise water-soluble natural polymer-based materials and may be free of water-insoluble materials (less than 5% by weight, and / or less than 3% by weight, and / or less than 1% by weight, and / or 0% by weight, based on the dry fibrous element and / or dry fibrous structure).

[0174] In yet another embodiment, the fiber element forming material may be a film-forming natural polymer-based material. In yet another embodiment, the fiber element forming material may be chemically, enzymatically, and / or physically modified.

[0175] Non-limiting examples of natural polymer-based fiber element forming materials may exhibit a weight average molecular weight of at least 10,000 g / mol, and / or at least 20,000 g / mol, and / or at least 40,000 g / mol, and / or at least 80,000 g / mol, and / or at least 100,000 g / mol, and / or at least 1,000,000 g / mol, and / or at least 3,000,000 g / mol, and / or at least 10,000,000 g / mol, and / or at least 20,000,000 g / mol up to about 40,000,000 g / mol, or up to about 30,000,000 g / mol.

[0176] In one embodiment, the natural polymer-based fiber element forming material of the present invention comprises a polysaccharide, such as a modified polysaccharide, such as a modified starch, for example acetylated starch.

[0177] As used herein, "polysaccharides" refers to natural polysaccharides and polysaccharide derivatives and / or modified polysaccharides. Suitable water-soluble polysaccharides include, but are not limited to, starch, starch derivatives, chitosan, chitosan derivatives, cellulose derivatives, hemicellulose, hemicellulose derivatives, gums, arabinans, galactans, and mixtures thereof. The water-soluble polysaccharides may exhibit a weight average molecular weight of about 10,000 g / mol to about 40,000,000 g / mol, and / or greater than 100,000 g / mol, and / or greater than 1,000,000 g / mol, and / or greater than 3,000,000 g / mol, and / or greater than about 3,000,000 g / mol to about 40,000,000 g / mol.

[0178] The polysaccharide may comprise a non-cellulosic, and / or non-cellulosic derivative, and / or non-cellulosic copolymer water soluble polysaccharide, which may be selected from the group consisting of starch, starch derivatives, chitosan, chitosan derivatives, hemicellulose, hemicellulose derivatives, gums, arabinans, galactans, dextran, and mixtures thereof.

[0179] Starches of natural origin are generally mixtures of linear amylose and branched amylopectin polymers of D-glucose units. Amylose is a substantially linear polymer of D-glucose units linked by (1,4)-α-D bonds. Amylopectin is a highly branched polymer of D-glucose units linked at the branch points by (1,4)-α-D and (1,6)-α-D bonds. Starches of natural origin, such as corn starch (64-80% amylopectin), waxy maize (93-100% amylopectin), rice (83-84% amylopectin), potato (about 78% amylopectin), and wheat (73-83% amylopectin), typically contain relatively high concentrations of amylopectin. In one embodiment, the naturally occurring starches of the present invention are high amylopectin and / or high amylose native starches derived from agricultural sources, which offer the advantages of being in abundant supply, easily replenished, and relatively inexpensive compared to starches derived from other sources.

[0180] As used herein, "starch" includes unmodified starches, modified starches, synthetic starches and mixtures thereof of any natural origin, as well as mixtures of amylose or amylopectin fractions, where the starches may be modified by physical, chemical, or biological processes, or a combination thereof. The choice of unmodified or modified starches for the present invention may depend on the desired end product. In one embodiment of the present invention, the starches or starch mixtures useful in the present invention have an amylopectin content of about 20% to about 100%, more typically about 40% to about 90%, and even more typically about 60% to about 85%, by weight of the starch or mixture thereof. In another embodiment of the present invention, the starches or starch mixtures useful in the present invention have an amylopectin content of about 90% to about 100%, and / or about 95% to about 99%, by weight of the starch or mixture thereof.

[0181] Suitable starches of natural origin may include, but are not limited to, corn starch, potato starch, sweet potato starch, wheat starch, sago starch, tapioca starch, rice starch, soy protein, arrowroot starch, amioca starch, bracken starch, lotus starch, waxy corn starch, and high amylose corn starch. Starches of natural origin, particularly corn starch and wheat starch, are preferred starch polymers in terms of economy and availability.

[0182] In one embodiment, further to the above, if present, the natural polymer-based material comprises a modified polysaccharide having a solubility parameter, as determined by the Fedors method described herein, of greater than 14.00 and less than 16.25, and / or greater than 14.50 and less than 16.25, and / or greater than 14.50 and less than 16.00, and / or greater than 15.00 and less than 15.50.

[0183] In one embodiment, further to the above, if present, the natural polymer-based material has a molecular weight of from greater than 50,000 g / mol to less than 40,000,000 g / mol, and / or from greater than 50,000 g / mol to less than 20,000,000 g / mol, and / or from greater than 50,000 g / mol to less than 10,000,000 g / mol, and / or less than 50,000 g / mol, as measured according to the Weight Average Molecular Weight Test Method. The modified polysaccharides include those exhibiting a weight average molecular weight of from greater than 5,000,000 g / mol to less than 5,000,000 g / mol, and / or from greater than 50,000 g / mol to less than 1,000,000 g / mol, and / or from greater than 100,000 g / mol to less than 750,000 g / mol, and / or from greater than 125,000 g / mol to less than 600,000 g / mol, and / or from about 150,000 to about 400,000 g / mol.

[0184] In one embodiment, further to the above, when present, the natural polymer-based material comprises a modified polysaccharide exhibiting a charge density of from -0.1 to +0.1 meq / g and / or about 0 meq / g as measured by the Charge Density Test Method.

[0185] In one embodiment, further to the above, when present, the natural polymer-based material comprises a modified polysaccharide selected from the group consisting of non-ionic modified polysaccharides, acetyl-substituted polysaccharides, and mixtures thereof. In one embodiment, the modified polysaccharide comprises a non-ionic modified polysaccharide. In one embodiment, the modified polysaccharide comprises an acetyl-substituted polysaccharide, such as acetylated starch.

[0186] In one embodiment, the modified polysaccharide is an acetyl-substituted polysaccharide, such as acetylated starch, exhibiting a DS of at least 0.3-1.0, and / or at least 0.3-0.7, and / or at least 0.4-0.6, and / or about 0.5.

[0187] In one embodiment, the modified polysaccharide is derived from starch, such as acid-thinning starch, and / or enzymatically degraded starch, and / or waxy starch, such as waxy maize starch, and / or amiocarpus starch.

[0188] In one embodiment, the natural polymer based material comprises a modified polysaccharide, such as a modified starch, such as an acetylated starch (starch acetate), for example an acetylated starch having a DS of about 0.3 to about 0.7, that exhibits a biodegradability of at least 5%, and / or at least 10%, and / or at least 15%, and / or at least 20%, and / or at least 25%, and / or at least 30%, and / or at least 35%, and / or at least 40%, and / or at least 45%, and / or at least 50%, and / or at least 55%, and / or at least 60%, and / or at least 75%, and / or at least 80% to about 100%, or to about 90%, and / or at least 5% to about 100%, and / or at least 40% to about 90% on day 28 of the test period as determined by the OECD 301B Ready Biodegradable CO Evolution Test Method.

[0189] In one embodiment, the natural polymer based material comprises a modified polysaccharide, such as a modified starch, such as an acetylated starch (starch acetate), that exhibits a biodegradability of at least 5%, and / or at least 10%, and / or at least 15%, and / or at least 20%, and / or at least 25%, and / or at least 30%, and / or at least 35%, and / or at least 40%, and / or at least 45%, and / or at least 50%, and / or at least 55%, and / or from at least 60% to about 100%, or up to about 90%, and / or from at least 5% to about 100%, and / or from at least 30% to about 90% at day 60 of the test period, as determined by the OECD 301B Ready Biodegradable CO Evolution Test Method.

[0190] In one embodiment, the natural polymer based material comprises a modified polysaccharide, such as a modified starch, such as an acetylated starch (starch acetate), that exhibits a biodegradability of at least 5%, and / or at least 10%, and / or at least 15%, and / or at least 20%, and / or at least 25%, and / or at least 30%, and / or at least 35%, and / or at least 40%, and / or at least 45%, and / or at least 50%, and / or at least 55%, and / or at least 60%, and / or at least 65%, and / or at least 70%, and / or at least 75%, and / or at least 80% to about 100%, or to about 90%, and / or at least 5% to about 100%, and / or at least about 50% to about 90% at day 90 of the test period as determined by the OECD 301B Ready Biodegradable CO Evolution Test Method.

[0191] Non-Limiting Examples of Fiber Element Forming Materials A fiber element-forming material, such as a natural polymer-based fiber element-forming material, such as a modified polysaccharide, such as a modified starch, in this case acetylated starch (some of which are suitable for use in the present invention and others are not), was prepared as follows.

[0192] Non-limiting Examples 1-7 First, Amioca starch (starting weight average molecular weight (Mw) of 10,000,000 ("10 7 ") g / mol ~ 1,000,000,000 ("10 9 ") g / mol range and average 100,000,000 ("10 8 ") g / mol) is decomposed by acid thinning as follows:

[0193] a. Starch Mw decomposition (acid thinning) To prepare examples 1-7, 1 kg of Mw degraded amioca starch is prepared in a 20 L jacketed Buchi-glas reactor. Amioca starch is added to a 0.5 M sulfuric acid solution to obtain a 20 wt% dispersion at about 23°C. The temperature of the dispersion is then increased to 70°C, and the resulting suspension is stirred at 70°C for 105 minutes. The suspension is then cooled to 35°C. After cooling to 35°C, NaOH is added to the suspension to adjust the pH to 7.5±0.5. The resulting Mw degraded starch is centrifuged and washed with a 70% ethanol / deionized water mixture until the Mw degraded starch is essentially free of Na2SO4. Finally, the Mw degraded starch is dried in an oven at 40°C under reduced pressure. The Mw of each Mw degraded starch was measured using GPC. The Mw of each Mw degraded starch is listed in Table 1 below.

[0194] [Table 1]

[0195] B acetylation of starch Each Mw degraded starch (samples 1 to 7) was then acetylated by an acetylation reaction to produce acetylated starch (starch acetate). The acetylation reaction conditions are shown in Table 2 below.

[0196] [Table 2]

[0197] For each individual sample, 120 g (0.63 moles, 84.9% dry content) of Mw degraded starch was added to 160 g (1.57 moles) of acetic anhydride (Ac2O) and stirred at about 23°C for 30 minutes. Then, 22.6 g (0.28 moles, 50% aqueous solution) of sodium hydroxide (NaOH) was added dropwise. The temperature of the mixture was raised to 125°C (samples 1-3) and 80°C (samples 4-7). The mixture was stirred at the respective elevated temperatures for 180 minutes (samples 1-4 and 7) and 300 minutes (samples 5-6). The mixture was then cooled. The resulting acetylated starch (starch acetate) was precipitated in ethanol and washed with a mixture of water / ethanol = 1 / 9 until the pH of the washings was neutral. The acetylated starch was then finally dried at 40°C under reduced pressure.

[0198] The resulting acetylated starches (starch acetates) (samples 1-7) are characterized as shown in Table 3 below. The sulfur content is determined using a Thermo Scientific FlashEA 1112 CHNS / O Automatic Elemental Analyzer equipped with a MAS200R autosampler. The sodium content is determined by ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy, Perkin Elmer) after microwave digestion with nitric acid. Salt content: The amount of sodium sulfate was calculated from the sulfur content. Then, a computation was made of how much sodium was bound to sodium sulfate. The excess sodium was assigned to the amount of sodium acetate.

[0199] The degree of substitution (DS) of starch acetate in Table 3 is determined by adding a known amount of starch acetate (150-200 mg) to 10 mL of acetone / deionized water mixture (1:1 by volume) over 24 hours at about 23°C. 5 mL of 1N NaOH in ethanol is then added and the mixture is stirred for another 24 hours at about 23°C. The excess alkali is titrated potentiometrically with Y mL of 0.1N aqueous HCl to the equivalence point. The degree of substitution (DS) and weight percent of the substitution can be calculated by the following formulas. The percent water content is determined using a Mettler Toledo HR-83 or HR-83P Moisture Balance using approximately 3.5 g of sample heated to 160°C with a standard drying program with a switch-off criterion of 1 mg / 50 seconds. The degree of substitution formula relates to polyglucosides. For other polymers, replace 162 g / mol with the corresponding monomer molecular weight. Activity%=100%-Water content%

[0200]

number

[0201] [Table 3] 1 Na2SO4 calculated from S content; NaOAc (sodium acetate)-Na2SO4 calculated from Na content

[0202] c. Determining the suitability of the fiber element forming material In one embodiment, for a fiber element forming material, such as a natural polymer-based fiber element forming material, such as a modified polysaccharide, such as a modified starch, such as acetylated starch (starch acetate), to be suitable for use as a fiber element forming material in the present invention, for example in the presence of a surfactant in the fiber element and / or fiber element forming composition, the fiber element forming material must exhibit compatibility as determined by the fiber element forming material compatibility test method described herein.

[0203] The starch acetates (samples 1-7) were subjected to the fiber element forming material compatibility test method described herein. The results for starch acetate are shown in Table 4 below. As shown in Table 4, starch acetate samples 1-3 and 7 passed the fiber element forming material compatibility test method described herein and are therefore suitable for forming the fiber element of the present invention and / or the fiber element forming composition of the present invention. Also, as shown in Table 4, starch acetate samples 4-6 did not pass the fiber element forming material compatibility test method described herein and are therefore not suitable for forming the fiber element of the present invention and / or the fiber element forming composition of the present invention.

[0204] In addition to and / or instead of DS and Mw, high salt content concentrations can adversely affect the miscibility of starch acetate.

[0205] [Table 4]

[0206] Non-limiting Example 8 First, Amioca starch (starting weight average molecular weight (Mw) of 10,000,000 ("10 7 ") g / mol ~ 1,000,000,000 ("10 9 ") g / mol range and average 100,000,000 ("10 8 ") g / mol) is decomposed by acid thinning as follows.

[0207] a. Starch Mw decomposition (acid thinning) A 30 L jacketed Buchi-glas reactor is used to prepare 8 kg of Mw degraded amioca starch. Amioca starch is added to a 0.27 M sulfuric acid solution to obtain a 40 wt% dispersion at about 23°C. The temperature of the dispersion is then increased to 50°C and the resulting suspension is stirred at 50°C for 36 hours. The suspension is then cooled to 25°C. After cooling to 25°C, NaOH is added to the suspension to adjust the pH to 7.5±0.5. The resulting Mw degraded starch is filtered and dried in an oven at 50°C under reduced pressure (60 mbar).

[0208] B acetylation of starch The Mw degraded starch is then acetylated by an acetylation reaction to produce acetylated starch (starch acetate).

[0209] Add 9 liters of deionized water and 2.5 kg of Mw degraded starch from step a to a 30 L jacketed Büchi-glas reactor. Cool to 10°C and stir the resulting slurry to disperse. Adjust to pH 9 using NaOH. Pump in 1.88 kg of acetic anhydride (Ac2O) and 3.6 kg of 25% NaOH solution over 1 hour. Maintain pH 8-9 during addition. After addition is complete, set temperature to 25°C. Stir for 4 hours. As the acetylation reaction continues, the pH will gradually decrease. Add NaOH periodically to maintain pH 8-9. Add 6 liters of ethanol to precipitate the acetylated starch (starch acetate). Allow to settle overnight. Aspirate off the supernatant and add 6 liters of ethanol. Stir to disperse and filter. Dry the starch acetate under reduced pressure (60 mbar) at 50°C.

[0210] Activator Active agents are a class of additives that are designed and intended to have an effect on something other than the textile elements and / or particles and / or textile structures themselves, for example, to have an effect on the environment outside the textile elements and / or particles and / or textile structures. Active agents may be any suitable additive that produces the intended effect under the intended conditions of use of the textile elements. For example, active agents may be selected from the group consisting of: personal cleansing and / or conditioning agents, such as hair care agents (e.g., shampoos and / or hair dyes), hair conditioning agents, skin care agents, sunscreens, and skin conditioning agents; laundry care and / or conditioning agents, such as fabric care agents, fabric conditioning agents, fabric softeners, fabric anti-wrinkle agents, fabric care anti-static agents, fabric care stain removal agents. cleaning agents, soil release agents, dispersants, foam suppressors, foam boosters, defoamers, and fabric refreshing agents; liquid and / or powder dishwashing agents (for hand dishwashing and / or automatic dishwashing applications), hard surface care agents, and / or conditioning agents and / or polishing agents; other cleaning and / or conditioning agents, such as antimicrobial agents, antibacterial agents, antifungal agents, fabric tinting agents, fragrances, bleaching agents (e.g., oxygen bleach, hydrogen peroxide, percarbonate bleach, perborate bleach, chlorine bleach, ), bleaching activators, chelating agents, builders, lotions, brighteners, air care agents, carpet care agents, dye transfer inhibitors, clay stain removers, anti-redeposition agents, polymeric stain release agents, polymeric dispersants, alkoxylated polyamine polymers, alkoxylated polycarboxylate polymers, amphiphilic graft copolymers, dissolution aids, buffer systems, water softeners, water hardeners, pH adjusters, enzymes, flocculants, foaming agents, preservatives, cosmetic agents, make-up removers, foaming agents, adhesion aids, core cells bate formers, clays, thickeners, latex, silica, drying agents, odor control agents, antiperspirants, cooling agents, warming agents, absorbent gelling agents, anti-inflammatory agents, dyes, pigments, acids, and bases; liquid treatment actives; agricultural actives; industrial actives; ingestible actives, such as pharmaceutical agents, oral care agents, such as tooth whitening agents, dental care agents, mouthwashes, and periodontal and gum care agents, edible agents, edible agents, vitamins, minerals; water treatment agents, such as water clarifiers and / or water disinfectants, and mixtures thereof.

[0211] Non-limiting examples of suitable cosmetic, skin care, skin conditioning, hair care, and hair conditioning agents are described in the CTFA Cosmetic Ingredient Handbook, Second Edition, The Cosmetic, Toiletries, and Fragrance Association, Inc. 1988, 1992.

[0212] One or more classes of chemicals may be useful for one or more of the active agents listed above.For example, surfactants may be used for any number of the above active agents.Similarly, bleaching agents may be used for fabric care, hard surface cleaning, dishwashing, and even dental whitening.Therefore, those skilled in the art will understand that active agents are selected based on the desired target application of fiber elements and / or particles and / or the fiber structures made therefrom.

[0213] For example, when the fiber elements and / or particles and / or fibrous structures made therefrom are used for hair care and / or conditioning, one or more suitable surfactants, e.g., lathering surfactants, can be selected to provide a desired benefit to the consumer when the fiber elements and / or particles and / or fibrous structures in which they are incorporated are exposed to the intended conditions of use.

[0214] In one embodiment, when the fibrous elements and / or particles and / or fibrous structures made therefrom are designed or intended for use in washing clothes in a laundry operation, one or more suitable surfactants, and / or enzymes, and / or builders, and / or perfumes, and / or foam suppressors, and / or bleaching agents can be selected to provide a desired benefit to the consumer when the fibrous elements and / or particles and / or fibrous structures in which the fibrous elements and / or particles are incorporated are exposed to the intended conditions of use. In another embodiment, when the fibrous elements and / or particles and / or fibrous structures made therefrom are designed or intended for use in washing clothes in a laundry operation and / or cleaning dishes in a dishwashing operation, the fibrous elements and / or particles and / or fibrous structures can include a laundry detergent composition or a dishwashing detergent composition or an active agent used in such compositions.

[0215] In one embodiment, the active agent comprises a non-fragrance active agent. In another embodiment, the active agent comprises a non-surfactant active agent, such as one or more non-surfactant active agents selected from the group consisting of skin care active agents, pharmaceutical agents, lotions, fabric care active agents, dishwashing active agents, carpet care active agents, surface care active agents, hair care active agents, air care active agents, dental care active agents, and mixtures thereof. In yet another embodiment, the active agent comprises a non-ingestible active agent, i.e., an active agent other than an ingestible active agent.

[0216] Surfactants Non-limiting examples of suitable surfactants include anionic surfactants, cationic surfactants, nonionic surfactants, zwitterionic surfactants, amphoteric surfactants, and mixtures thereof. Co-surfactants may also be included in the fiber elements and / or particles. For fiber elements and / or particles designed for use as laundry detergents and / or dishwashing detergents, the total concentration of surfactants should be sufficient to provide cleaning, including stain and / or odor removal, and generally ranges from about 0.5% to about 95%. Furthermore, surfactant systems including two or more surfactants designed for use in fiber elements and / or particles for laundry detergents and / or dishwashing detergents may include an all-anionic surfactant system, a mixed surfactant system including a mixture of anionic-nonionic surfactants or a mixture of nonionic-cationic surfactants, or a low foaming nonionic surfactant.

[0217] The surfactants described herein may be linear or branched. In one embodiment, suitable linear surfactants include those derived from agrochemical oils such as coconut oil, palm kernel oil, soybean oil, or other vegetable-based oils.

[0218] In one embodiment, the surfactant present in the fiber element forming composition, fiber elements, particles, and / or fiber structures produced therefrom, for example for use as a hair care active, may be selected from the group consisting of sodium lauryl sulfate, sodium laureth sulfate, linear alkylbenzene sulfonate, sodium lauroyl sarcosinate such as Hamposyl L-30, sodium lauroyl glycinate, lauryl betaine, lauryl hydroxysultaine, sodium lauryl isethionate, cocamide monoethanolamine, decyl glucoside, disodium cocoyl glutamate (DSCG), and mixtures thereof.

[0219] a. Anionic surfactants The anionic surfactants for use as active agents in the present invention have the general formula (I):

[0220] [ka] wherein R1 is a saturated or unsaturated, linear or branched alkyl or alkenyl chain having 5 to 20 carbon atoms and / or 7 to 17 carbon atoms and / or 9 to 13 carbon atoms, and M is independently H, ammonium, triethanolammonium (TEA), sodium, or potassium, and mixtures thereof.

[0221] In one embodiment, when the fibrous elements and / or particles and / or fibrous structures made therefrom contain glutamate surfactants, the fibrous elements and / or particles and / or fibrous structures made therefrom are substantially free (less than 5% by weight, or less than 3% by weight, or less than 1% by weight, or less than 0.5% by weight, or less than 0.1% by weight) or free (0% by weight) of alkyl sulfate and alkyl ether sulfate surfactants.

[0222] Glutamate surfactants include sodium cocoyl glutamate, disodium cocoyl glutamate, potassium cocoyl glutamate, dipotassium cocoyl glutamate, ammonium cocoyl glutamate, diammonium cocoyl glutamate, sodium lauroyl glutamate, disodium lauroyl glutamate, potassium lauroyl glutamate, dipotassium lauroyl glutamate, sodium capryloyl glutamate, disodium capryloyl glutamate, potassium capryloyl glutamate, dipotassium capryloyl glutamate, sodium undecylenoyl glutamate, disodium undecylenoyl glutamate, potassium undecylenoyl glutamate, dipotassium undecylenoyl glutamate, hydrogenated tallow oil disodium glutamate, stearyl glutamate, glyceryl ...

[0043] The compound may be selected from the group consisting of sodium lauroyl glutamate, disodium stearoyl glutamate, potassium stearoyl glutamate, dipotassium stearoyl glutamate, sodium myristoyl glutamate, disodium myristoyl glutamate, potassium myristoyl glutamate, dipotassium myristoyl glutamate, cocoyl / hydrogenated sodium tallow oil glutamate, cocoyl / palmoyl / sodium saffloweroyl glutamate, hydrogenated sodium tallow oil glutamate, sodium olivoyl glutamate, disodium olivoyl glutamate, sodium palmoyl glutamate, disodium palmoyl glutamate, TEA-cocoyl glutamate, hydrogenated TEA-tallow oil glutamate, TEA-lauroyl glutamate, and mixtures thereof.

[0223] The fiber elements and / or particles and / or fiber structures made therefrom may be selected from the group consisting of sodium cocoyl glutamate, disodium cocoyl glutamate, potassium cocoyl glutamate, dipotassium cocoyl glutamate, ammonium cocoyl glutamate, diammonium cocoyl glutamate, sodium lauroyl glutamate, disodium lauroyl glutamate, potassium lauroyl glutamate, dipotassium lauroyl glutamate, sodium capryloyl glutamate, disodium capryloyl glutamate , potassium capryloyl glutamate, dipotassium capryloyl glutamate, sodium stearoyl glutamate, disodium stearoyl glutamate, potassium stearoyl glutamate, dipotassium stearoyl glutamate, sodium myristoyl glutamate, disodium myristoyl glutamate, potassium myristoyl glutamate, dipotassium myristoyl glutamate, TEA-cocoyl glutamate, and mixtures thereof.

[0224] The fiber elements and / or particles and / or fiber structures made therefrom may comprise at least one glutamate surfactant selected from the group consisting of sodium cocoyl glutamate, disodium cocoyl glutamate, potassium cocoyl glutamate, dipotassium cocoyl glutamate, ammonium cocoyl glutamate, diammonium cocoyl glutamate, TEA-cocoyl glutamate, and mixtures thereof.

[0225] In one embodiment, non-limiting examples of surfactants for use as, for example, hair care actives may be selected from the group consisting of ammonium lauryl sulfate, ammonium laureth sulfate, triethylamine lauryl sulfate, triethylamine laureth sulfate, triethanolamine lauryl sulfate, triethanolamine laureth sulfate, monoethanolamine lauryl sulfate, monoethanolamine laureth sulfate, diethanolamine lauryl sulfate, diethanolamine laureth sulfate, lauryl monoglyceride sodium sulfate, sodium lauryl sulfate, sodium laureth sulfate, potassium lauryl sulfate, potassium laureth sulfate, sodium lauryl sarcosinate, sodium lauroyl sarcosinate, lauryl sarcosine, cocoyl sarcosine, ammonium cocoyl sulfate, ammonium lauroyl sulfate, sodium cocoyl sulfate, sodium lauroyl sulfate, potassium cocoyl sulfate, potassium lauryl sulfate, triethanolamine lauryl sulfate, triethanolamine lauryl sulfate, monoethanolamine cocoyl sulfate, monoethanolamine lauryl sulfate, sodium tridecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sodium cocoyl isethionate, and mixtures thereof.

[0226] The total concentration of one or more glutamate surfactants present in the fiber element forming composition, the fiber elements and / or particles, and / or the fiber structures made therefrom may be from about 20% to about 95% by weight, and / or from about 25% to about 90% by weight, and / or from about 30% to about 70% by weight, based on the fiber element forming composition or the fiber elements and / or particles and / or fiber structures.

[0227] The one or more surfactants of the one or more active agents may also include a co-surfactant by weight of the fiber element forming composition, the co-surfactant being selected from the group consisting of non-glutamate anionic surfactants, nonionic surfactants, zwitterionic surfactants, amphoteric surfactants, and mixtures thereof.

[0228] When present in the fiber element forming composition, fiber elements and / or particles, and / or fiber structures made therefrom, the total concentration of the one or more co-surfactants may be from about 2% to about 30% by weight, and / or from about 5% to about 25% by weight, and / or from about 7% to about 20% by weight, based on the fiber element forming composition, fiber elements and / or particles, and / or fiber structures.

[0229] Non-limiting examples of non-glutamate anionic surfactants, present alone or in combination with glutamate or other surfactants, may include anionic surfactants selected from the group consisting of isethionate surfactants, sarcosinate surfactants, glycinate surfactants, alanitate surfactants, sulfosuccinate surfactants, sulfonate surfactants, sulfoacetate surfactants, glucose carboxylate surfactants, alkyl ether carboxylate surfactants, taurate surfactants, and mixtures thereof. Each of the anionic surfactants listed above is described in more detail below.

[0230] Non-limiting examples of non-glutamate anionic surfactants, present alone or in combination with one or more glutamate surfactants or other surfactants, can include anionic surfactants selected from the group consisting of lactate surfactants, lactylate surfactants, and mixtures thereof.Non-limiting examples of lactate surfactants include sodium lactate.Non-limiting examples of lactylate surfactants include sodium lauroyl lactylate, sodium cocoyl lactylate, and mixtures thereof.

[0231] The one or more active agents may be represented by the general formula (II):

[0232] [ka] wherein R1 is a saturated or unsaturated, linear or branched alkyl or alkenyl chain having 6 to 30 carbon atoms, 8 to 22 carbon atoms, and / or 9 to 18 carbon atoms; R2 and R3 are each independently H or (C1-C4) alkyl, such as methyl, and mixtures thereof; M + is an alkali metal, such as lithium, sodium, potassium, or M + is an alkaline earth metal, e.g. magnesium, or M + is an ammonium or substituted ammonium cation).

[0233] The isethionate surfactant may be selected from the group consisting of sodium lauroyl isethionate, sodium lauroyl methyl isethionate, sodium oleoyl isethionate, sodium oleoyl methyl isethionate, sodium stearoyl isethionate, sodium stearoyl methyl isethionate, sodium myristoyl isethionate, sodium myristoyl methyl isethionate, sodium palmitoyl isethionate, sodium palmitoyl methyl isethionate, sodium cocoyl isethionate, sodium cocoyl methyl isethionate, a blend of stearic acid and sodium cocoyl isethionate, ammonium cocoyl isethionate, ammonium cocoyl methyl isethionate, and mixtures thereof.

[0234] The isethionate surfactant may be selected from the group consisting of sodium lauroyl isethionate, sodium lauroyl methyl isethionate, sodium oleoyl isethionate, sodium stearoyl isethionate, sodium myristoyl isethionate, sodium palmitoyl isethionate, sodium cocoyl isethionate, ammonium cocoyl isethionate, and mixtures thereof.

[0235] The isethionate surfactant may be selected from the group consisting of sodium lauroyl isethionate, sodium lauroyl methyl isethionate, sodium stearoyl isethionate, sodium myristoyl isethionate, sodium cocoyl isethionate, ammonium cocoyl isethionate, and mixtures thereof.

[0236] The isethionate surfactant may be selected from the group consisting of sodium lauroyl isethionate, sodium cocoyl isethionate, ammonium cocoyl isethionate, and mixtures thereof.

[0237] Corresponding commercial products are available, for example, from the company Innospec under the trade name "Iselux®" and from Clariant or Uniquema under the trade name "Hostapon®" or "Arlatone®". Examples of other commercially available fatty acyl isethionates that may be used are the Hostapon® surfactants from Clariant, such as for sodium cocoyl isethionate, Hostapon® SCI-85C, Hostapon® SCI-78C, or a blend of stearic acid and sodium cocoyl isethionate, Hostapon® SCI-65C. Examples of other commercially available fatty acyl isethionates that can be used are the "Jordapon®" surfactants from BASF, such as Jordapon® CI Prill or Jordapon® CI 65, and sodium cocoyl isethionate from Yongan Daily Chemical Co., such as YA-SCI-85® or YA-SCI-65®.

[0238] Sarcosinate surfactants have the following general formula (III):

[0239] [ka] where R is a saturated or unsaturated, linear or branched alkyl or alkenyl, for example an alkyl chain having 7 to 17 and / or 9 to 13 carbon atoms; M + is H to form -COOH, or M + is a sodium, potassium, ammonium, or triethanolammonium cation.

[0240] The one or more active agents may include a sarcosinate surfactant, which may be selected from the group consisting of sodium lauroyl sarcosinate, sodium cocoyl sarcosinate, sodium myristoyl sarcosinate, TEA cocoyl sarcosinate, ammonium cocoyl sarcosinate, ammonium lauroyl sarcosinate, dilinoleyl bis-lauroyl glutamate / dimer lauroyl sarcosinate, disodium lauroamphodiacetate, lauroyl sarcosinic acid, isopropyl lauroyl sarcosinate, potassium cocoyl sarcosinate, potassium lauroyl sarcosinate, sodium cocoyl sarcosinate, sodium lauroyl sarcosinate, sodium myristoyl sarcosinate, sodium oleoyl sarcosinate, sodium palmitoyl sarcosinate, TEA cocoyl sarcosinate, TEA lauroyl sarcosinate, TEA oleoyl sarcosinate, TEA palm kernel sarcosinate, and mixtures thereof.

[0241] The sarcosinate surfactant may be selected from the group consisting of sodium lauroyl sarcosinate, sodium myristoyl sarcosinate, sodium cocoyl sarcosinate, and mixtures thereof.

[0242] The one or more active agents may include a glycinate surfactant, which may be selected from the group consisting of sodium cocoyl glycinate, sodium lauroyl glycinate, and mixtures thereof.

[0243] The one or more active agents may include an alaninate surfactant, which may be selected from the group consisting of sodium cocoyl alaninate, sodium lauroyl alaninate, sodium N-dodecanoyl-1-alaninate, and mixtures thereof.

[0244] The one or more active agents may include a sulfosuccinate surfactant, which may be selected from the group consisting of disodium N-octadecyl sulfosuccinate, disodium lauryl sulfosuccinate, diammonium lauryl sulfosuccinate, sodium lauryl sulfosuccinate, disodium laureth sulfosuccinate, tetrasodium N-(1,2-dicarboxyethyl)-N-octadecyl sulfosuccinate, diamyl ester of sodium sulfosuccinate, dihexyl ester of sodium sulfosuccinate, dioctyl ester of sodium sulfosuccinate, and mixtures thereof.

[0245] The one or more active agents may include a sulfonate surfactant, which may be selected from the group consisting of alpha-olefin sulfonates, linear alkylbenzene sulfonates, sodium lauryl glucoside hydroxypropyl sulfonate, and mixtures thereof.

[0246] The one or more surfactants may include a sulfoacetate surfactant, which may be selected from the group consisting of sodium lauryl sulfoacetate, ammonium lauryl sulfoacetate, and mixtures thereof.

[0247] The one or more active agents may include a glucose carboxylate surfactant, which may be selected from the group consisting of sodium lauryl glucoside carboxylate, sodium cocoyl glucoside carboxylate, and mixtures thereof.

[0248] The one or more active agents may include an alkyl ether carboxylate surfactant, which may be selected from the group consisting of sodium laureth-4 carboxylate, laureth-5 carboxylate, laureth-13 carboxylate, sodium C12-13 pareth-8 carboxylate, sodium C12-15 pareth-8 carboxylate, and mixtures thereof.

[0249] The one or more active agents may include a taurate surfactant, which may be selected from the group consisting of sodium methyl cocoyl taurate, sodium methyl lauroyl taurate, sodium methyl oleoyl taurate, and mixtures thereof.

[0250] The total concentration of the non-glutamate anionic surfactant present in the fiber element forming composition, the fiber elements, the particles, and / or the fiber structure made therefrom may be from about 0.5% to about 20% by weight, and / or from about 0.5% to about 15% by weight, and / or from about 1% to about 10% by weight of the fiber element forming composition, the fiber elements and / or the particles, and / or the fiber structure made therefrom.

[0251] Non-limiting examples of suitable anionic surfactants include alkyl sulfates, alkyl ether sulfates, branched alkyl sulfates, branched alkyl alkoxylates, branched alkoxylate sulfates, mid-chain branched alkyl aryl sulfonates, sulfated monoglycerides, sulfonated olefins, alkyl aryl sulfonates, primary or secondary alkane sulfonates, alkyl sulfosuccinates, acyltaurates, acyl isethionates, alkyl glyceryl ether sulfonates, sulfonated methyl esters, sulfonated fatty acids, alkyl phosphates, acyl glutamates, acyl sarcosinates, alkyl sulfoacetates, acylated peptides, alkyl ether carboxylates, acyl lactylates, anionic fluorosurfactants, sodium lauroyl glutamate, and combinations thereof.

[0252] Suitable alkyl sulfates and alkyl ether sulfates for use herein include those having the corresponding formula ROSO3M and RO(C2H4O) x Included are materials having the formula SO3M, where R is an alkyl or alkenyl of about 8 to about 24 carbon atoms, x is 1 to 10, and M is a water-soluble cation, such as ammonium, sodium, potassium, and triethanolamine. Other suitable anionic surfactants are described in McCutcheon's Detergents and Emulsifiers, North American Edition (1986), Allured Publishing Corp. and McCutcheon's, Functional Materials, North American Edition (1992), Allured Publishing Corp.

[0253] In one embodiment, anionic surfactants useful in the fiber elements and / or particles of the present invention include C9 to C 15 Alkylbenzene sulfonate (LAS), C8~C 20 Alkyl ether sulfates, such as alkyl poly(ethoxy) sulfates, C8-C 20 Other anionic surfactants include methyl ester sulfonates (MES), secondary alkane sulfonates, methyl ester ethoxylates (MEE), sulfonated estolides, and mixtures thereof.

[0254] In another embodiment, the anionic surfactant is 11 ~C 18 Alkylbenzene sulfonates ("LAS") and primary branched and random C 10 ~C 20 Alkyl sulfate ("AS"), formula CH3(CH2) x (CHOSO3- M + )CH3 and CH3(CH2) y (CHOSO3 - M + )CH2CH3, where x and (y+1) are integers of at least about 7, preferably at least about 9, and M is a water-soluble cation, particularly an unsaturated sulfate such as oleyl sulfate. 10 ~C 18 Secondary (2,3) alkyl sulfate, C 10 ~C 18 α-Sulfonated fatty acid ester, C 10 ~C 18 Sulfated alkyl polyglycosides, C 10 ~C 18 Alkyl alkoxy sulfate (AE x S"), where x is 1 to 30, and C 10 ~C 18 Alkyl alkoxy carboxylates, such as mid-chain branched alkyl sulfates containing 1 to 5 ethoxy units as described in U.S. Pat. Nos. 6,020,303 and 6,060,443; mid-chain branched alkyl alkoxy sulfates as described in U.S. Pat. Nos. 6,008,181 and 6,020,303; modified alkyl benzene sulfonates (MLAS) as described in WO 99 / 05243, WO 99 / 05242, and WO 99 / 05244; methyl ester sulfonates (MES), and alpha-olefin sulfonates (AOS).

[0255] In one embodiment, the anionic surfactant is selected from the group consisting of sulfate-containing anionic surfactants and sulfate-free anionic surfactants, and mixtures thereof.

[0256] b. Cationic surfactants Non-limiting examples of suitable cationic surfactants include those represented by the following formula (I):

[0257] [ka] [In the formula, R 1 , R 2 , R 3 , and R 4 are each independently selected from (a) an aliphatic group of 1 to 26 carbon atoms, or (b) an aromatic, alkoxy, polyoxyalkylene, alkylcarboxy, alkylamido, hydroxyalkyl, aryl, or alkylaryl group containing up to 22 carbon atoms, and X is a salt-forming anion, such as one selected from a halogen radical (e.g., chloride, bromide), acetate radical, citrate radical, lactate radical, glycolate radical, phosphate radical, nitrate radical, sulfate radical, and alkylsulfate radical. In one embodiment, the alkylsulfate radical is methosulfate and / or ethosulfate.

[0258] Suitable quaternary ammonium cationic surfactants of general formula (I) include cetyltrimethylammonium chloride, behenyltrimethylammonium chloride (BTAC), stearyltrimethylammonium chloride, cetylpyridinium chloride, octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octyldimethylbenzylammonium chloride, decyldimethylbenzylammonium chloride, stearyldimethylbenzylammonium chloride, didodecyldimethylammonium chloride, didecyldimethylammonium chloride, dioctadecyldimethylammonium chloride, Included are distearyl dimethyl ammonium chloride, tallow trimethyl ammonium chloride, coco trimethyl ammonium chloride, 2-ethylhexylstearyl dimethyl ammonium chloride, dipalmitoyl ethyl dimethyl ammonium chloride, ditallowoyl ethyl dimethyl ammonium chloride, distearoyl dimethyl ammonium methosulfate, PEG-2 oleyl ammonium chloride, and salts thereof, where the chloride is replaced by a halogen (e.g., bromine), acetate, citrate, lactate, glycolate, phosphate nitrate, sulfate, or alkyl sulfate.

[0259] Non-limiting examples of suitable cationic surfactants are commercially available from Akzo Nobel Surfactants (Chicago, IL) under the trade name ARQUAD®.

[0260] In one embodiment, suitable cationic surfactants include quaternary ammonium surfactants having up to 26 carbon atoms, such as alkoxylate quaternary ammonium surfactants, such as those described in U.S. Pat. No. 6,136,769. dimethylhydroxyethyl lauryl ammonium chloride; polyamine cationic surfactants such as those discussed in WO 98 / 35002, WO 98 / 35003, WO 98 / 35004, WO 98 / 35005, and WO 98 / 35006; cationic ester surfactants such as those described in U.S. Pat. Nos. 4,228,042, 4,239,660, 4,260,529, and 6,022,844; and amino surfactants such as amido propyldimethyl amine (APA), such as those described in U.S. Pat. No. 6,221,825 and WO 00 / 47708.

[0261] In one embodiment, the cationic ester surfactant is hydrolyzable under laundry wash conditions.

[0262] C. Nonionic surfactants The one or more active agents may include a non-ionic surfactant. The non-ionic surfactant may be selected from the group consisting of alkyl polyglucosides (also referred to as alkyl glycosides), acyl glucamides, and mixtures thereof. With respect to the non-ionic surfactants, "alkyl" is defined as a saturated or unsaturated, linear or branched alkyl chain having 6-30 and / or 8-22 and / or 9-18 carbon atoms, and "acyl" is defined as a group of formula RC(O)-, where R is a saturated or unsaturated, linear or branched alkyl or alkenyl, e.g., an alkyl group having 6-30 and / or 8-22 and / or 9-18 carbon atoms.

[0263] Non-limiting examples of alkyl polyglucosides include alkyl polyglucosides selected from the group consisting of decyl glucoside, cocoyl glucoside, lauroyl glucoside, and mixtures thereof.

[0264] Non-limiting examples of acyl glucamides include acyl glucamides selected from the group consisting of lauroyl / myristoyl methyl glucamide, capryloyl / capryloyl methyl glucamide, cocoyl methyl glucamide, and mixtures thereof.

[0265] Non-limiting examples of non-ionic surfactants include non-ionic surfactants selected from the group consisting of cocoamide monoethanolamine, lauroamide monoethanolamine, cocoyl glucoside, lauroyl glucoside, decyl glucoside, and mixtures thereof.

[0266] The total concentration of nonionic surfactant present in the fiber element forming composition, fiber elements, particles, and / or fiber structures made therefrom may be from about 0.1% to about 10% by weight, and / or from about 0.1% to about 5% by weight, and / or from about 0.5% to about 3% by weight of the fiber element forming composition present in the fiber element forming composition, fiber elements, particles, and / or fiber structures made therefrom.

[0267] Non-limiting examples of suitable nonionic surfactants include alkoxylated alcohols (AE) and alkylphenols, polyhydroxy fatty acid amides (PFAA), alkyl polyglycosides (APG), C 10 ~C 18 glycerol ether and the like.

[0268] In one embodiment, non-limiting examples of nonionic surfactants useful in the present invention include C 12 ~C 18Alkyl ethoxylates, such as NEODOL® nonionic surfactants from Shell; C6-C 12 Alkylphenol alkoxylates (where the alkoxylate units are a mixture of ethyleneoxy and propyleneoxy units); C with ethylene oxide / propylene oxide block alkyl polyamine ethoxylates 12 ~C 18 Alcohol condensation products and C6-C 12 Condensates (such as PLURONIC® (BASF)); C 14 ~C 22 Mid-chain branched alcohols (BA); C 11 as discussed in U.S. Pat. Nos. 6,153,577, 6,020,303 and 6,093,856 14 ~C 22 Medium Chain Branched Alkyl Alkoxylate, BAE x (where x is 1 to 30); the alkyl polysaccharides described in U.S. Pat. No. 4,565,647 (Llenado), issued Jan. 26, 1986; and in particular the alkyl polyglycosides described in U.S. Pat. Nos. 4,483,780 and 4,483,779; the polyhydroxy detergent acid amides described in U.S. Pat. No. 5,332,528; and the ether end-capped poly(oxyalkylated) alcohol surfactants described in U.S. Pat. No. 6,482,994 and WO 01 / 42408.

[0269] An example of a commercially available non-ionic surfactant suitable for the present invention is Tergitol® 15-S-9 (C 11 ~C 15 (Condensation product of linear alcohol with 9 moles of ethylene oxide) and Tergitol® 24-L-6NMW (6 moles of ethylene oxide with narrow molecular weight distribution and C 12 ~C 14 Condensation products of primary alcohols) (both sold by Dow Chemical Company); Neodol® 45-9 (C 14 ~C 15Condensation product of linear alcohol with 9 moles of ethylene oxide), Neodol® 23-3 (C 12 ~C 13 Condensation product of linear alcohol with 3 moles of ethylene oxide), Neodol® 45-7 (C 14 ~C 15 Condensation product of linear alcohol with 7 moles of ethylene oxide), Neodol® 45-5 (C 14 ~C 15 Condensation products of linear alcohols with 5 moles of ethylene oxide (sold by Shell Chemical Company); Kyro® EOB (C 13 ~C 15 (condensation product of alcohol with 9 moles of ethylene oxide) (sold by The Procter & Gamble Company); and Genapol LA O3O or O5O (C 12 ~C 14 Condensation products of alcohols with 3 or 5 moles of ethylene oxide (sold by Clariant). The nonionic surfactants may exhibit an HLB ranging from about 8 to about 17, and / or from about 8 to about 14. Condensates with propylene oxide and / or butylene oxide may also be used.

[0270] Polyethylene, polypropylene, and polybutylene oxide condensates of alkylphenols are also suitable for use as nonionic surfactants in the present invention. These compounds include the condensation products of alkylphenols having alkyl groups containing from about 6 to about 14 carbon atoms, in either a linear or branched configuration, with alkylene oxide. Commercially available nonionic surfactants of this type include Igepal® CO-630 (available from Solvay-Rhodia), and Triton® X-45, X-114, X-100, and X-102 (all available from Dow Chemical Company).

[0271] In one embodiment, non-limiting examples of surfactants for use as hair care actives, for example, can include nonionic surfactants suitable for use in the structured aqueous cleansing phase, including condensation products of alkylene oxide groups (hydrophilic in nature) with organic hydrophobic compounds, which can be aliphatic or alkylaromatic in nature.

[0272] In automatic dishwashing applications, low foaming nonionic surfactants may be used. Suitable low foaming nonionic surfactants are disclosed in U.S. Patent No. 7,271,138 at column 7, line 10 to column 7, line 60.

[0273] Examples of other suitable non-ionic surfactants are the commercially available Pluronic® surfactants (sold by BASF), the commercially available Tetronic® compounds (sold by BASF), and the commercially available Plurafac® surfactants (sold by BASF).

[0274] D. Zwitterionic surfactants Non-limiting examples of zwitterionic surfactants include derivatives of aliphatic quaternary ammonium, quaternary phosphonium, or tertiary sulfonium compounds. For examples of zwitterionic surfactants, see U.S. Pat. No. 3,929,678, column 19, line 38 to column 22, line 48. Betaines, including alkyl dimethyl betaines and cocodimethylamidopropyl betaine, C8-C 18 (For example, C 10 ~C 18 Or C 12 ~C 18 ) amine oxides, and sulfo and hydroxy betaines such as N-alkyl-N,N-dimethylamino-1-propanesulfonates, where the alkyl group is C8 to C 18 and in certain embodiments C 10 ~C 14 may be).

[0275] Zwitterionic surfactants suitable for use alone or as co-surfactants can include those broadly described as derivatives of aliphatic quaternary ammonium, phosphonium, and sulfonium compounds, in which the aliphatic radical can be straight or branched chain, one of the aliphatic substituents can contain from 8 to 18 carbon atoms, and one can contain an anionic group, such as carboxy, sulfonate, phosphate, or phosphonate.

[0276] The zwitterionic surfactant may include a betaine zwitterionic surfactant. Non-limiting examples of betaine zwitterionic surfactants may be selected from the group consisting of cocodimethyl carboxymethyl betaine, cocoamidopropyl betaine (CAPB), coco-betaine, lauryl amidopropyl betaine (LAPB), oleyl betaine, lauryl dimethyl carboxymethyl betaine, lauryl dimethyl alpha-carboxyethyl betaine, cetyl dimethyl carboxymethyl betaine, lauryl bis-(2-hydroxyethyl) carboxymethyl betaine, stearyl bis-(2-hydroxypropyl) carboxymethyl betaine, oleyl dimethyl gamma-carboxypropyl betaine, lauryl bis-(2-hydroxypropyl) alpha-carboxyethyl betaine, and mixtures thereof. Examples of sulfobetaines may include cocodimethyl sulfopropyl betaine, stearyl dimethyl sulfopropyl betaine, lauryl dimethyl sulfoethyl betaine, lauryl bis-(2-hydroxyethyl) sulfopropyl betaine, and mixtures thereof.

[0277] In one embodiment, non-limiting examples of surfactants for use as, for example, hair care actives include coco dimethyl carboxymethyl betaine, coco amidopropyl betaine, coco betaine, lauryl amidopropyl betaine, oleyl betaine, lauryl dimethyl carboxymethyl betaine, lauryl dimethyl alpha carboxyethyl betaine, cetyl dimethyl carboxymethyl betaine, lauryl bis-(2-hydroxyethyl) carboxyl methyl betaine, stearyl bis-(2-hydroxypropyl) carboxymethyl betaine, oleyl dimethyl gamma carboxypropyl betaine, and betaines, including higher alkyl betaines such as coco dimethyl sulfopropyl betaine, stearyl dimethyl sulfopropyl betaine, lauryl dimethyl sulfoethyl betaine, lauryl bis-(2-hydroxyethyl) sulfopropyl betaine, amido betaines, and amido sulfobetaines, such as those in which the RCONH(CH2)3 radical in amido betaines and amido sulfobetaines is attached to the nitrogen atom of the betaine; and mixtures thereof.

[0278] e. Amphoteric surfactants Non-limiting examples of amphoteric surfactants include aliphatic derivatives of secondary or tertiary amines, or aliphatic derivatives of heterocyclic secondary and tertiary amines, where the aliphatic radicals can be linear or branched, and mixtures thereof. One of the aliphatic substituents may contain at least about 8 carbon atoms, such as about 8 to about 18 carbon atoms, and at least one contains an anionic water-solubilizing group, such as carboxy, sulfonate, sulfate. For suitable examples of amphoteric surfactants, see U.S. Pat. No. 3,929,678, column 19, lines 18-35.

[0279] Amphoteric surfactants may include those that can be broadly described as derivatives of aliphatic secondary and tertiary amines, in which the aliphatic radical can be linear or branched, and the aliphatic substituent can contain 8 to 18 carbon atoms, such that one carbon atom can contain an anionic water-soluble group, such as carboxy, sulfonate, phosphate, or phosphonate.Examples of compounds that fit this definition may be sodium 3-dodecylaminopropionate, sodium 3-dodecylaminopropanesulfonate, N-alkyltaurines, such as those prepared by reacting dodecylamine with sodium isethionate according to the teachings of U.S. Patent No. 2,658,072, N-higher alkylaspartic acids, such as those produced according to the teachings of U.S. Patent No. 2,438,091, and the products described in U.S. Patent No. 2,528,378.

[0280] The amphoteric surfactants described herein may preferably be selected from the group consisting of sodium lauroamphoacetate, sodium cocoamphoacetate, disodium lauroamphodiacetate, disodium cocodiamphoacetate, and mixtures thereof.

[0281] Suitable amphoteric or zwitterionic surfactants may include those described in US Pat. No. 5,104,646 and US Pat. No. 5,106,609.

[0282] Thus, the one or more surfactants of the one or more active agents may comprise at least an amphoteric or zwitterionic surfactant selected from the group consisting of cocamidopropyl betaine, lauramidopropyl betaine, coco betaine, lauryl betaine, lauryl hydroxysultaine, cocamidopropyl hydroxysultaine, coco hydroxysultaine, coco sultaine, lauryl sultaine, sodium cocoamphoacetate, disodium cocoamphodiacetate, sodium lauroamphoacetate, disodium lauroamphodiacetate, lauramine oxide, and mixtures thereof.

[0283] In one embodiment, for example, non-limiting examples of surfactants for use as hair care actives can be selected from the group consisting of cocoamphoacetate, cocoamphodiacetate, lauroamphoacetate, lauroamphodiacetate, and mixtures thereof.

[0284] In one embodiment, for example, non-limiting examples of surfactants for use as hair care actives can be selected from the group consisting of amphoacetates and diamphoacetates. Non-limiting examples of suitable amphoacetates and diamphoacetates can include sodium lauroamphoacetate, sodium cocoamphoacetate, disodium lauroamphoacetate, and disodium cocodiamphoacetate, and mixtures thereof.

[0285] fragrance One or more perfumes and / or perfume raw materials, such as accords and / or notes, may be incorporated into one or more of the fiber elements and / or particles of the present invention. The perfume may comprise a perfume ingredient selected from the group consisting of aldehyde perfume ingredients, ketone perfume ingredients, and mixtures thereof.

[0286] One or more perfumes and / or perfume ingredients may be included in the fiber elements and / or particles of the present invention. A wide range of natural and synthetic chemical ingredients useful as perfumes and / or perfume ingredients include, but are not limited to, aldehydes, ketones, esters, and mixtures thereof. Also included are various natural extracts and essences, which may include complex mixtures of ingredients such as orange oil, lemon oil, rose extract, lavender, musk, patchouli, balsam extract, sandalwood oil, pine oil, cedar, and the like. The final perfume may include a very complex mixture of such ingredients. In one embodiment, the finished perfume typically comprises about 0.01% to about 2% by weight based on the dry fiber elements and / or dry particles and / or dry fiber structure.

[0287] Antibacterial, antibacterial, and antifungal agents In one embodiment, pyridinethione particles are suitable antimicrobial active agents for use in the present invention. In another embodiment, the antimicrobial active agent is a 1-hydroxy-2-pyridinethione salt, in particulate form. In another embodiment, the concentration of pyridinethione particles ranges from about 0.01% to about 5%, or from about 0.1% to about 3%, or from about 0.1% to about 2% by weight of the dry fiber elements and / or dry particles and / or dry fiber structures of the present invention. In another embodiment, the pyridinethione salt is formed from heavy metals such as zinc, tin, cadmium, magnesium, aluminum, and zirconium, typically zinc, and is typically the zinc salt of 1-hydroxy-2-pyridinethione (known as "zinc pyridinethione" or "zinc pyridinethione, ZPT"), usually in the form of platelet particles. In another embodiment, the platelet particle form of 1-hydroxy-2-pyridinethione salt has an average particle size of about 20 micrometers or less, or about 5 micrometers or less, or about 2.5 micrometers or less, as measured according to the particle size distribution test method described herein.Salts formed from other cations (e.g., sodium) may also be suitable.Pyridinethione actives are described, for example, in U.S. Patent Nos. 2,809,971, 3,236,733, 3,753,196, 3,761,418, 4,345,080, 4,323,683, 4,379,753, and 4,470,982.

[0288] In another embodiment, the antibacterial agent is selected from triclosan, triclocarban, chlorhexidine, metronidazole, and mixtures thereof.

[0289] In another embodiment, in addition to an antimicrobial active selected from polyvalent metal salts of pyrithione, the composition may further comprise one or more antifungal and / or antimicrobial actives. In another embodiment, the antimicrobial active is selected from the group consisting of coal tar, sulfur, azoles, selenium sulfide, sulfur particles, keratolytic agents, charcoal, Whitfield's ointment, Castellani liniment, aluminum chloride, gentian violet, octopirox (piroctone olamine), ciclopirox olamine, undecylenic acid and its metal salts, potassium permanganate, selenium sulfide, sodium thiosulfate, propylene glycol, orange peel oil, urea preparations, griseofulvin, 8-hydroxyquinoline ciloquinol, thiobendazole, thiocarbamates, haloprogin, polyenes, hydroxypyridones, morpholines, benzylamines, allylamines (such as terbinafine), tea tree oil, clove leaf oil, coriander, palmarosa, berberine, thyme red, cinnamon oil, cinnamaldehyde, citronellic acid, hinokitol, ichthyol pale, Sensiva SC-50, Elestab The active ingredient is selected from the group consisting of HP-100, azelaic acid, lyticase, iodopropynyl butylcarbamate (IPBC), isothiazarinones such as octylisothiazarinone, and azoles, and mixtures thereof.

[0290] Bleach The fiber elements and / or particles of the present invention may include one or more bleaching agents. Non-limiting examples of suitable bleaching agents include peroxyacids (e.g., phthalimidoperoxyhexanoic acid (PAP)), perborates, percarbonates, chlorine bleaches, oxygen bleaches, hypohalous bleaches, bleach precursors, bleach activators, bleach catalysts, hydrogen peroxide, bleach boosters, photobleaches, bleaching enzymes, free radical initiators, peroxygen bleaches, and mixtures thereof.

[0291] The one or more bleaching agents that may be included in the fiber elements and / or particles of the present invention may be included in a concentration of about 0.05% to about 30% and / or about 1% to about 20% by weight based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure. If present, bleach activators may be present in the fiber elements and / or particles of the present invention in a concentration of about 0.1% to about 60% and / or about 0.5% to about 40% by weight based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure.

[0292] Non-limiting examples of bleaching agents include oxygen bleaches, perborate bleaches, percarboxylic acid bleaches and their salts, peroxygen bleaches, persulfate bleaches, percarbonate bleaches, and mixtures thereof. Further non-limiting examples of bleaching agents are disclosed in U.S. Pat. No. 4,483,781, U.S. Pat. Application No. 740,446, European Pat. Application No. 0133354, U.S. Pat. No. 4,412,934, and U.S. Pat. No. 4,634,551.

[0293] Non-limiting examples of bleach activators (eg, acyllactam activators) are disclosed in U.S. Patent Nos. 4,915,854, 4,412,934, 4,634,551, and 4,966,723.

[0294] In one embodiment, the bleaching agent may comprise a transition metal bleach catalyst, which may be encapsulated. The transition metal bleach catalyst typically comprises a transition metal ion, for example from a transition metal selected from the group consisting of Mn(II), Mn(III), Mn(IV), Mn(V), Fe(II), Fe(III), Fe(IV), Co(I), Co(II), Co(III), Ni(I), Ni(II), Ni(III), Cu(I), Cu(II), Cu(III), Cr(II), Cr(III), Cr(IV), Cr(V), Cr(VI), V(III), V(IV), V(V), Mo(IV), Mo(V), Mo(VI), W(IV), W(V), W(VI), Pd(II), Ru(II), Ru(III), and Ru(IV). In one embodiment, the transition metal is selected from the group consisting of Mn(II), Mn(III), Mn(IV), Fe(II), Fe(III), Cr(II), Cr(III), Cr(IV), Cr(V), and Cr(VI). The transition metal bleach catalyst typically comprises a ligand, for example a macropolycyclic ligand, such as a bridged macropolycyclic ligand. The transition metal ion may be coordinated to the ligand. Additionally, the ligand may comprise at least four donor atoms, at least two of which are bridgehead donor atoms. Non-limiting examples of suitable transition metal bleach catalysts are described in U.S. Pat. Nos. 5,580,485, 4,430,243, 4,728,455, 5,246,621, 5,244,594, 5,284,944, 5,194,416, 5,246,612, 5,256,779, 5,280, Nos. 5,117, 5,274,147, 5,153,161, 5,227,084, 5,114,606, 5,114,611, EP 549,271(A1); EP 544,490(A1), 549,272(A1), and 544,440(A2). In one embodiment, suitable transition metal bleach catalysts include manganese-based catalysts, such as those disclosed in U.S. Pat. No. 5,576,282. In another embodiment, suitable cobalt bleach catalysts are described in U.S. Pat. Nos. 5,597,936 and 5,595,967.Such cobalt catalysts are readily made by known procedures, for example, as taught in U.S. Patent Nos. 5,597,936 and 5,595,967. Still further, suitable transition metal bleach catalysts include transition metal complexes of ligands such as bispidones as described in WO 05 / 042532 A1.

[0295] Non-limiting examples of bleach catalysts include catalyst systems containing transition metal cations such as copper, iron, titanium, ruthenium, tungsten, molybdenum, or manganese cations with defined bleach catalytic activity, auxiliary metal cations such as zinc or aluminum cations with little or no bleach catalytic activity, and sequestering agents with defined stability constants for the catalyst and auxiliary metal cations, particularly ethylenediaminetetraacetic acid, ethylenediaminetetra(methylenephosphonic acid) and their water-soluble salts. Such catalysts are described in U.S. Pat. No. 4,430,243. Other types of bleach catalysts include manganese-based complexes disclosed in U.S. Pat. Nos. 5,246,621 and 5,244,594. Preferred examples of these catalysts include Mn IV 2(uO)3(1,4,7-trimethyl-1,4,7-triazacyclononane)2-(PF6)2 ("MnTACN"), Mn III 2(uO)1(u-OAc)2(1,4,7-trimethyl-1,4,7-triazacyclononane)2-(ClO4)2, Mn IV 4(uO)6(1,4,7-triazacyclononane)4-(ClO4)2, Mn III Mn IV4(uO)1(u-OAc)2-(1,4,7-trimethyl-1,4,7-triazacyclononane)2-(ClO4)3, and mixtures thereof. See also EP 549,272. Other suitable ligands for use herein include 1,5,9-trimethyl-1,5,9-triazacyclododecane, 2-methyl-1,4,7-triazacyclononane, 2-methyl-1,4,7-triazacyclononane, and mixtures thereof. Bleaching catalysts useful in automatic dishwashing compositions and concentrated powder detergent compositions can be appropriately selected for the present invention. Examples of suitable bleaching catalysts can be seen in U.S. Pat. Nos. 4,246,612 and 5,227,084. See also U.S. Pat. No. 5,194,416, which teaches mononuclear manganese(IV) complexes such as Mn(1,4,7-trimethyl-1,4,7-triazacyclononane (OCH3)3 (PF6). Yet another class of bleach catalysts, as disclosed in U.S. Pat. No. 5,114,606, are water-soluble complexes of manganese(II), (III), and / or (UV) with ligands that are non-carboxylate polyhydroxy compounds having at least three consecutive C-OH groups. Preferred ligands include sorbitol, iditol, dulcitol, and tetrahydrofuran. Examples of suitable ligands include glycerol, mannitol, xylitol, arabitol, adonitol, mesoerythritol, mesoinositol, lactose, and mixtures thereof. U.S. Patent No. 5,114,611 teaches bleach catalysts comprising complexes of transition metals such as Mn, Co, Fe, or Cu with non-(macro)-cyclic ligands. Non-limiting examples of ligands include pyridine, pyridazine, pyrimidine, pyrazine, imidazole, pyrazole, and triazole rings. In one embodiment, the ligand is 2,2'-bispyridylamine.In one embodiment, the bleaching catalyst includes Co, Cu, Mn, Fe,-bispyridylmethane and bispyridylamine complexes such as Co(2,2'-bispyridylamine)Cl2, di(isothiocyanato)bispyridylamine-cobalt(II), trispyridylamine-cobalt(II) perchlorate, Co(2,2-bispyridylamine)2O2ClO4, bis-(2,2'-bispyridylamine)copper(II) perchlorate, tris(di-2-pyridylamine)iron(II) perchlorate, and mixtures thereof. Other examples of bleaching catalysts include Mn gluconate, Mn(CF3SO3)2, Co(NH3)5Cl, and N4Mn(III)(uO)2Mn(IV)N4). + and dinuclear Mn complexed with N-tetradentate and N-bidentate ligands, including [Bipy2Mn(III)(uO)2Mn(IV)bipy2]-(ClO4)3.

[0296] The bleach catalyst may also be prepared by combining a water-soluble ligand with a water-soluble manganese salt in an aqueous medium and concentrating the resulting mixture by evaporation. Any convenient water-soluble salt of manganese may be used herein. Manganese (II), (III), (IV) and / or (V) are readily available on a commercial scale. In some cases, sufficient manganese may be present in the wash liquor, but it is generally preferred that the Mn cation of the detergent composition is present in the composition to ensure that it is present in a catalytically effective amount. Thus, the ligand and a sodium salt of a member selected from the group consisting of MnSO4, Mn(ClO4)2, or MnCl2 (not desirable) are dissolved in water at a neutral or slightly alkaline pH in a molar ratio of ligand:Mn ranging from about 1:4 to 4:1. The water may first be deoxygenated by boiling and cooled by sparging with nitrogen. The resulting solution is evaporated (under N2 if desired) and the resulting solid is used in the bleaching and detergent compositions herein without further purification.

[0297] In an alternative mode, a water-soluble manganese source such as MnSO4 is added to the bleach / cleaning composition or to the aqueous bleach / cleaning bath containing the ligand. Some species of complex are apparently formed in situ to ensure improved bleaching performance. In such an in situ process, it is advantageous to use a significant molar excess of the ligand over manganese, with the ligand:Mn molar ratio typically being between 3:1 and 15:1. Additional ligands can also be utilized to scavenge labile metal ions such as iron and copper, thereby protecting the bleach from degradation. One possible such system is described in EP 549,271.

[0298] Although the structures of the bleach catalytic manganese complexes useful in the present invention have not been elucidated, they may be assumed to include chelates or other hydrated coordination complexes resulting from the interaction of the carboxyl and nitrogen atoms of the ligand with the manganese cation. Similarly, the oxidation state of the manganese cation during the catalytic process is not known with certainty and may be in the (+II), (+III), (+IV) or (+V) valence state. Due to the six possible points of binding of the ligand to the manganese cation, it may be reasonably assumed that polynuclear species and / or "cage" structures may exist in the aqueous bleaching medium. Whatever the form of the active Mn-ligand species actually present, it clearly functions catalytically to provide improved bleaching performance for tough stains such as tea, ketchup, coffee, wine, juice, etc.

[0299] Other bleach catalysts are described, for example, in EP 408,131 (cobalt complex catalysts), EP 384,503 and EP 306,089 (metalloporphyrin catalysts), U.S. Pat. No. 4,728,455 (manganese / multidentate ligand catalysts), U.S. Pat. No. 4,711,748 and EP 224,952 (manganese absorbed on aluminosilicate catalysts), U.S. Pat. No. 4,601,845 (aluminosilicate catalysts containing manganese and zinc or magnesium salts), and U.S. Pat. No. 4,119,557 (ferric complex catalysts), German Patent No. 2,054,019 (cobalt chelate catalysts), Canadian Patent No. 866,191 (transition metal containing salts), U.S. Patent No. 4,430,243 (chelating agents having manganese cations and non-catalytic metal cations), and U.S. Patent No. 4,728,455 (manganese gluconate catalysts).

[0300] In one embodiment, the bleach catalyst has the formula [Co(NH3)5Cl]Y y , particularly cobalt pentaamine chloride salts having [Co(NH3)5Cl]CI2. Other cobalt bleach catalysts useful herein are described, for example, in ML Tobe, "Base Hydrolysis of Transition-Metal Complexes", Adv. Inorg. Bioinorg. Mech., (1983), 2, pages 1-94, along with their base hydrolysis rates. For example, Table 1 on page 17 lists the base hydrolysis rates (referred to as k in the table) for cobalt pentaamine catalyst complexed with oxalate, formate, and acetate. OH A non-limiting example of a cobalt catalyst useful herein is represented by the formula [Co(NH3)5OAc]T y where OAc represents the acetate moiety, particularly cobalt pentaamine acetate chloride, [Co(NH3)5OAc]Cl2; and [Co(NH3)5OAc](OAc)2; [Co(NH3)5OAc](PF6); [Co(NH3)5OAc](SO4); [Co(NH3)5OAc](BF4)2; and [Co(NH3)5OAc](NO3)2.

[0301] These bleach catalysts may be readily prepared by known procedures as taught, for example, in Diakun et al, issued Mar. 7, 1989, J. Chem. Ed. (1989), 66(12), 1043-45; The Synthesis and Characterization of Inorganic Compounds, W. L. Jolly (Prentice-Hall; 1970), pp. 461-3; Inorg. Chem., 18, 1497-1502 (1979); Inorg. Chem., 21, 2881-2885 (1982); Inorg. Chem., 18, 2023-2025 (1979); Inorg. Synthesis, 173-176 (1960); and Journal of Physical Chemistry 56, 22-25 (1952), which are references to the Tobe article and U.S. Pat. No. 4,810,410 cited therein. These bleach catalysts may also be co-processed with auxiliary materials to reduce color impact if desired for product aesthetics, or may be included in enzyme-containing particles as exemplified below, or the composition may be manufactured to contain catalytic "speckles."

[0302] Bleaching agents other than oxygen bleaches are also known in the art and may be used herein (e.g., photoactivated bleaches such as sulfonated zinc and / or aluminum phthalocyanines (U.S. Pat. No. 4,033,718, incorporated herein by reference), and / or preformed organic peracids, such as peroxycarboxylic acids or salts thereof, and / or peroxysulfonic acids or salts thereof. In one embodiment, a suitable organic peracid comprises phthaloyl imidoperoxycaproic acid or salts thereof. When present, a photoactivated bleach initiator (e.g., sulfonated zinc phthalocyanine) may be present in the fibrous elements, particles, and / or fibrous structures of the present invention at a concentration of about 0.025% to about 1.25% by weight, based on the dry fibrous elements, and / or on the dry particles, and / or on the dry fibrous structures.

[0303] Non-limiting examples of bleach activators are selected from the group consisting of tetraacetyl ethylene diamine (TAED), benzoylcaprolactam (BzCL), 4-nitrobenzoylcaprolactam, 3-chlorobenzoylcaprolactam, benzoyloxybenzenesulphonate (BOBS), nonanoyloxybenzene-sulphonate (NOBS), phenylbenzoate (PhBz), decanoyloxybenzenesulphonate (C.sub.10-OBS), benzoylvalerolactam (BZVL), octanoyloxybenzenesulphonate (C.sub.8-OBS), perhydrolyzable esters, and mixtures thereof, most preferably benzoylcaprolactam and benzoylvalerolactam. Particularly preferred bleach activators in the pH range of about 8 to about 9.5 are selected from those having an OBS or VL leaving group. Quaternary substituted bleach activators (quaternary substituted bleach activators (QSBA) or quaternary substituted peracids (QSP)) may also be included.

[0304] Non-limiting examples of organic peroxides, such as diacyl peroxides, are described extensively in Kirk Othmer, Encyclopedia of Chemical Technology, Vol. 17, John Wiley and Sons, 1982, pages 27-90, especially pages 63-72, all of which are incorporated herein by reference. If a diacyl peroxide is used, it may be one that minimizes adverse effects on spotting / filming.

[0305] Dye transfer inhibitor The fiber elements and / or particles of the present invention may include one or more dye transfer inhibitors. Suitable polymeric dye transfer inhibitors include, but are not limited to, polyvinylpyrrolidone polymers, polyamine N-oxide polymers, copolymers of N-vinylpyrrolidone and N-vinylimidazole, polyvinyloxazolidones, and polyvinylimidazoles, or mixtures thereof. The dye transfer inhibitors may be present in the fiber elements and / or particles and / or fiber structure products of the present invention at a concentration of about 0.0001% to about 10%, about 0.01% to about 5%, or even about 0.1% to about 3% by weight based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure.

[0306] Brightener The fibre elements and / or particles of the present invention may contain active agents such as brighteners, for example fluorescent brighteners. Such brighteners may impart a tint to the article being washed.

[0307] The fiber elements and / or particles may include CI fluorescent brightener 260 in the α-crystalline form having the following structure:

[0308] [ka]

[0309] In one embodiment, the brightener is a cold water soluble brightener such as CI Fluorescent Brightener 260 in the α-crystalline form.

[0310] In one embodiment, the brightener is predominantly in the α-crystalline form, which typically means that at least 50% by weight, at least 75% by weight, at least 90% by weight, at least 99% by weight, or even substantially all of the CI fluorescent brightener 260 is in the α-crystalline form.

[0311] The polishing agent may typically be in finely divided particulate form having a weight average primary particle size of from 3 to 30 μm, from 3 to 20 μm, or from 3 to 10 μm, as measured in accordance with the Particle Size Distribution Test Method.

[0312] The composition may include CI fluorescent brightener 260 in the β-crystalline form, and the weight ratio of (i) CI fluorescent brightener 260 in the α-crystalline form to (ii) CI fluorescent brightener 260 in the β-crystalline form may be at least 0.1, or at least 0.6.

[0313] Belgian Patent No. 680847 relates to a process for producing CI fluorescent brightener 260 in α-crystalline form.

[0314] Commercially available fluorescent brighteners that may be useful in the present invention can be divided into subgroups that include, but are not necessarily limited to, derivatives of stilbenes, pyrazolines, coumarins, carboxylic acids, methine cyanines, dibenzothiophene-5,5-dioxides, azoles, 5- and 6-membered heterocycles, and various other agents. Examples of such brighteners are disclosed in "The Production and Application of Fluorescent Brightening Agents", M. Zahradnik, Published by John Wiley & Sons, New York (1982). Specific non-limiting examples of fluorescent brighteners that are useful in the present compositions are those identified in U.S. Pat. Nos. 4,790,856 and 3,646,015.

[0315] Further suitable brighteners have the following structure:

[0316] [ka]

[0317] Suitable fluorescent brightener concentrations include lower limits of about 0.01, about 0.05, about 0.1 or even about 0.2% by weight, to upper limits of 0.5 or even 0.75% by weight.

[0318] In one embodiment, the glaze may be loaded onto the clay to form particles.

[0319] Hueing Agent The composition may include a hueing agent. Suitable hueing agents include dyes, dye clay complexes, and pigments. Suitable dyes include small molecule dyes and polymeric dyes. Suitable small molecule dyes include small molecule dyes selected from the group consisting of dyes classified under the Color Index (CI) classification of direct blue, direct red, direct violet, acid blue, acid red, acid violet, basic blue, basic violet, and basic red, or mixtures thereof.

[0320] In another embodiment, suitable small molecule dyes include, by Color Index (Society of Dyers and Colourists, Bradford, UK) numbers, Direct Violet 9, Direct Violet 35, Direct Violet 48, Direct Violet 51, Direct Violet 66, Direct Violet 99, Direct Blue 1, Direct Blue 71, Direct Blue 80, Direct Blue 279, Acid Red 17, Acid Red 73, Acid Red 88, Acid Red 150, Acid Violet 15, Acid Violet 17, Acid Violet 24, Acid Violet 43, Acid Red 52, Acid Violet 49, Acid Violet 50, Acid Blue 1 5, Acid Blue 17, Acid Blue 25, Acid Blue 29, Acid Blue 40, Acid Blue 45, Acid Blue 75, Acid Blue 80, Acid Blue 83, Acid Blue 90, and Acid Blue 113, Acid Black 1, Basic Violet 1, Basic Violet 3, Basic Violet 4, Basic Violet 10, Basic Violet 35, Basic Blue 3, Basic Blue 16, Basic Blue 22, Basic Blue 47, Basic Blue 66, Basic Blue 75, Basic Blue 159, and mixtures thereof. In another aspect, suitable small molecule dyes include small molecule dyes selected from the group consisting of the Colour Index (Society of Dyers and Colourists, Bradford, UK) numbers Acid Violet 17, Acid Violet 43, Acid Red 52, Acid Red 73, Acid Red 88, Acid Red 150, Acid Blue 25, Acid Blue 29, Acid Blue 45, Acid Blue 113, Acid Black 1, Direct Blue 1, Direct Blue 71, Direct Violet 51, and mixtures thereof.In another aspect, suitable small molecule dyes include small molecule dyes selected from the group consisting of the Colour Index (Society of Dyers and Colourists, Bradford, UK) numbers Acid Violet 17, Direct Blue 71, Direct Violet 51, Direct Blue 1, Acid Red 88, Acid Red 150, Acid Blue 29, Acid Blue 113, or mixtures thereof.

[0321] Suitable polymeric dyes include those selected from the group consisting of polymers containing conjugated chromogens (dye-polymer conjugates), polymers having chromogens copolymerized into the backbone of the polymer, and mixtures thereof.

[0322] In another embodiment, suitable polymeric dyes include polymeric dyes selected from the group consisting of surface substantive colorants sold under the name Liquitint® (Milliken, Spartanburg, South Carolina, USA); dye-polymer conjugates formed from at least one reactive dye and a polymer selected from the group consisting of polymers comprising a moiety selected from the group consisting of a hydroxyl moiety, a primary amine moiety, a secondary amine moiety, a thiol moiety, and mixtures thereof. In yet another aspect, suitable polymeric dyes include polymeric dyes selected from the group consisting of Liquitint® (Milliken, Spartanburg, South Carolina, USA) Violet CT; carboxymethyl cellulose (CMC) conjugated with a reactive blue, reactive violet, or reactive red dye, such as CMC conjugated with CI Reactive Blue 19 sold under the trade name AZO-CM-CELLULOSE, product code S-ACMC by Megazyme (Wicklow, Ireland); alkoxylated triphenyl-methane polymeric colorants; alkoxylated thiophene polymeric colorants; and mixtures thereof.

[0323] Preferred hueing dyes include the brighteners found in WO 08 / 87497 A1. These brighteners may be characterized by the following structure (I):

[0324] [ka]

[0325] In formula (I), R1 and R2 may be independently selected from the following a) to d). a) [(CH2CR'HO) x (CH2CR''HO) y H] [Wherein, R' is H, CH3, CH2O(CH2CH2O) z H, and mixtures thereof, R″ is selected from the group consisting of H, CH2O(CH2CH2O) z H, and mixtures thereof, where x+y≦5, y≧1, and z=0-5; b) R1 = alkyl, aryl or arylalkyl, and R2 = [(CH2CR'HO) x (CH2CR''HO) y H] [Wherein, R' is H, CH3, CH2O(CH2CH2O) z H, and mixtures thereof, R″ is selected from the group consisting of H, CH2O(CH2CH2O) z H, and mixtures thereof, wherein x+y≦10, y≧1, and z=0-5; c) R1 = [CH2CH2(OR3)CH2OR4] and R2 = [CH2CH2(OR3)CH2OR4] [Wherein, R3 is H, (CH2CH2O) z H, and mixtures thereof, where z=0-10; R4 is (C1~C 16 ) selected from the group consisting of alkyl groups, aryl groups, and mixtures thereof; and d) R1 and R2 can be independently selected from amino addition products of styrene oxide, glycidyl methyl ether, isobutyl glycidyl ether, isopropyl glycidyl ether, t-butyl glycidyl ether, 2-ethylhexyl glycidyl ether, and glycidyl hexadecyl ether with 1 to 10 alkylene oxide units.

[0326] A preferred brightener of the present invention has the following structure (II):

[0327] [ka] [Wherein, R' is H, CH3, CH2O(CH2CH2O) z H, and mixtures thereof, R″ is selected from the group consisting of H, CH2O(CH2CH2O) z H, and mixtures thereof, wherein x+y≦5, y≧1, and z=0-5.

[0328] A more preferred brightener of the present invention has the following structure (III):

[0329] [ka] It may be characterized by:

[0330] This polish is commonly referred to as "Violet DD". Violet DD is typically a mixture having a total of 5 EO groups. This structure is achieved by the following selection in Structure I of the following pendant groups shown in "part a" above:

[0331] [Table 5]

[0332] Further brightening agents include those described in US Patent Application Publication No. 2008 / 34511(A1) (Unilever). A preferred agent is "Violet 13".

[0333] Suitable dye clay complexes include dye clay complexes selected from the group consisting of at least one cationic / basic dye and smectite clay, and mixtures thereof. In another embodiment, suitable dye clay complexes include dye clay complexes selected from the group consisting of one cationic / basic dye selected from the group consisting of CI Basic Yellow 1-108, CI Basic Orange 1-69, CI Basic Red 1-118, CI Basic Violet 1-51, CI Basic Blue 1-164, CI Basic Green 1-14, CI Basic Brown 1-23, CI Basic Black 1-11, and a clay selected from the group consisting of montmorillonite clay, hectorite clay, saponite clay, and mixtures thereof. In yet another embodiment, suitable dye-clay complexes include Montmorillonite Basic Blue B7 CI42595 complex, Montmorillonite Basic Blue B9 CI52015 complex, Montmorillonite Basic Violet V3 CI42555 complex, Montmorillonite Basic Green G1 CI42040 complex, Montmorillonite Basic Red R1 CI45160 complex, Montmorillonite CI Basic Black 2 complex, Hectorite Basic Blue B7 CI42595 complex, Hectorite Basic Blue B9 CI52015 complex, Hectorite Basic Violet V3 CI42555 complex, Hectorite Basic Green G1 CI42040 complex, Hectorite Basic Red R1 CI45160 complex, Hectorite CI Basic Black 2 complex, Saponite Basic Blue B7 CI42595 complex, Saponite Basic Blue B9 CI52015 complex, Saponite Basic Violet V3 CI 42555 Complex, Saponite Basic Green G1 CI 42040 Complex, Saponite Basic Red R1 CI 45160 Complex, Saponite CI Basic Black 2 Complex, and mixtures thereof.

[0334] Suitable pigments include pigments selected from the group consisting of flavanthrone, indanthrone, chlorinated indanthrone containing 1 to 4 chlorine atoms, pyranthrone, dichloropyranthrone, monobromodichloropyranthrone, dibromodichloropyranthrone, tetrabromopyranthrone, perylene-3,4,9,10-tetracarboxylic acid diimide (the imide group may be unsubstituted or substituted by C1-C3-alkyl or phenyl or heterocyclic radicals, the phenyl and heterocyclic radicals may further carry substituents that do not impart water solubility), anthrapyrimidine carboxylic acid amide, violanthrone, isoviolanthrone, dioxazine pigments, copper phthalocyanines which may contain up to 2 chlorine atoms per molecule, polychloro- or polybromochloro-copper phthalocyanines containing up to 14 bromine atoms per molecule, and mixtures thereof.

[0335] In another embodiment, suitable pigments include pigments selected from the group consisting of Ultramarine Blue (CI Pigment Blue 29), Ultramarine Violet (CI Pigment Violet 15), and mixtures thereof.

[0336] The above-mentioned fabric hueing agents may be used in combination (any mixture of fabric hueing agents may be used).Suitable fabric hueing agents can be purchased from Aldrich, Milwaukee, Wisconsin, USA; Ciba Specialty Chemicals, Basel, Switzerland; BASF, Ludwigshafen, Germany; Dayglo Color Corporation, Mumbai, India; Organic Dyestufos Corp., East Providence, Rhode Island, USA; Dystar, Frankfurt, Germany; Lanxess, Leverkusen, Germany; Megazyme, Wicklow, Ireland; Clariant, Muttenz, Switzerland; Avecia, Manchester, UK and / or made according to the examples contained herein.Suitable hueing agents are described in more detail in U.S. Patent No. 7,208,459 (B2).

[0337] enzyme One or more enzymes may be present in the fiber elements and / or particles of the present invention. Non-limiting examples of suitable enzymes include proteases, amylases, lipases, cellulases, carbohydrases including mannanases and endoglucanases, pectinases, hemicellulases, peroxidases, xylanases, phospholipases, esterases, cutinases, keratanases, reductases, oxidases, phenoloxidases, lipoxygenases, ligninases, pullulanases, tannases, pentosanases, malanases, glucanases, arabinosidases, hyaluronidases, chondroitinases, laccases, and mixtures thereof.

[0338] Enzymes can be included in the fiber elements and / or particles of the present invention for a wide variety of purposes, including, but not limited to, removal of protein-based, carbohydrate-based, or triglyceride-based stains from substrates, prevention of dye migration from released dyes during fabric laundering, and fabric repair. In one embodiment, the fiber elements and / or particles of the present invention can include proteases, amylases, lipases, cellulases, peroxidases, and mixtures thereof from any suitable origin, such as vegetable, animal, bacterial, fungal, and yeast origin. The choice of enzymes used is influenced by factors such as pH activity and / or stability optimum, thermal stability, and stability relative to other additives such as activators (e.g., builders) present in the fiber elements and / or particles. In one embodiment, the enzymes are selected from the group consisting of bacterial enzymes (e.g., bacterial amylases and / or bacterial proteases), fungal enzymes (e.g., fungal cellulases), and mixtures thereof.

[0339] When present in the textile elements and / or particles of the invention, the enzymes may be present in a concentration sufficient to provide a "cleaning effective amount". The term "cleaning effective amount" refers to any amount capable of producing a cleaning, stain removing, soil removing, whitening, deodorizing, or fresh feeling effect on a substrate, such as fabrics, dishware, flooring, ceramics, metal surfaces, and the like. As a practical matter for current commercial formulations, a typical amount of active enzyme is up to about 5 mg by weight, more typically 0.01 mg to 3 mg, per gram of textile elements and / or particles of the invention. When specifically specified, textile elements and / or particles of the invention typically comprise from about 0.001% to about 5% by weight, and / or from about 0.01% to about 3% by weight, and / or from about 0.01% to about 1% by weight, based on the dry textile elements and / or dry particles and / or dry textile structures.

[0340] After the fiber elements and / or particles have been produced, one or more enzymes may be applied to the fiber elements and / or particles.

[0341] A range of enzyme materials and means of incorporating enzyme materials into the filament-forming composition of the present disclosure (which may also be a synthetic detergent composition) are disclosed in WO 9307263(A), WO 9307260(A), WO 8908694(A), U.S. Pat. Nos. 3,553,139, 4,101,457 and 4,507,219.

[0342] Enzyme Stabilization System When enzymes are present in the fiber elements and / or particles of the present invention, an enzyme stabilization system may also be included in the fiber elements and / or particles. The enzymes can be stabilized by a variety of techniques. Non-limiting examples of enzyme stabilization techniques are disclosed and exemplified in U.S. Pat. Nos. 3,600,319 and 3,519,570; European Patent Nos. 199,405 and 200,586; and WO 9401532(A).

[0343] In one embodiment, the enzyme stabilization system may include calcium ions and / or magnesium ions.

[0344] The enzyme stabilization system may be included in the fiber elements and / or particles of the present invention at a concentration of about 0.001% to about 10% by weight, and / or about 0.005% to about 8% by weight, and / or about 0.01% to about 6% by weight based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure. The enzyme stabilization system may be any stabilization system that is compatible with the enzymes present in the fiber elements and / or particles. Such enzyme stabilization systems may be inherently provided by other formulated actives or may be added separately, for example, by the enzyme formulator or manufacturer. Such enzyme stabilization systems may include, for example, calcium ions, magnesium ions, boric acid, propylene glycol, short chain carboxylic acids, boronic acids, and mixtures thereof, and are designed to address different stabilization problems.

[0345] Thermoforming Agent The fiber elements and / or particles of the present invention may contain a thermoforming agent. The thermoforming agent is formulated to generate heat in the presence of water and / or oxygen (e.g., oxygen in air, etc.), thereby accelerating the degradation rate of the fiber structure in the presence of water and / or oxygen and / or increasing the effectiveness of one or more of the active substances in the fiber element. Additionally or alternatively, the thermoforming agent may be used to accelerate the release rate of one or more active substances from the fiber structure. The thermoforming agent is formulated to undergo an exothermic reaction when exposed to oxygen (i.e., oxygen in air, oxygen in water, etc.). Many different materials and combinations of materials may be used as thermoforming agents. Non-limiting thermoforming agents that can be used in the fibrous structure include electrolyte salts (e.g., aluminum chloride, calcium chloride, calcium sulfate, cupric chloride, cuprous chloride, ferrous sulfate, magnesium chloride, magnesium sulfate, manganese chloride, manganese sulfate, potassium chloride, potassium sulfate, sodium acetate, sodium chloride, sodium carbonate, potassium sulfate, etc.), glycols (e.g., propylene glycol, dipropylene glycol, etc.), lime (e.g., quicklime, hydrated lime, etc.), metals (e.g., chromium, copper, iron, magnesium, manganese, etc.), metal oxides (e.g., aluminum oxide, iron oxide, etc.), polyalkyleneamines, polyalkyleneimines, polyvinylamines, zeolites, glycerin, 1,3, propanediol, polysorbate esters (e.g., Tweens 20, 60, 85, 80), and / or polyglycerol esters (e.g., Noobe, Drewpol, and Drewmulze from Stepan). Thermoforming agents can be formed from one or more materials. For example, magnesium sulfate alone may form the thermoformer. In another non-limiting example, a combination of about 2-25% by weight of activated carbon, about 30-70% by weight of iron powder, and about 1-10% by weight of a metal salt may form the thermoformer. As will be appreciated, other or additional materials may be used alone or in combination with other materials to form the thermoformer. Non-limiting examples of materials that may be used to form the thermoformer used in the fibrous structure are disclosed in U.S. Patent Nos. 5,674,270 and 6,020,040, and U.S. Patent Application Publication Nos. 2008 / 0132438 and 2011 / 0301070.

[0346] Decomposition accelerator The fiber elements and / or particles of the present invention may contain a degradation accelerator used to accelerate the rate at which the fiber structure degrades in the presence of water and / or oxygen. When used, the degradation accelerator is generally designed to release a gas when exposed to water and / or oxygen, which then agitates the area around the fiber structure to accelerate the degradation of the carrier film of the fiber structure. Additionally or alternatively, the degradation accelerator, when used, may be used to accelerate the release rate of one or more active substances from the fiber structure. However, this is not required. Additionally or alternatively, the degradation accelerator, when used, may be used to increase the effectiveness of one or more of the active substances in the fiber structure. However, this is not required. The degradation accelerator may include one or more materials, including but not limited to, alkali metal carbonates (e.g., sodium carbonate, potassium carbonate, etc.), alkali metal bicarbonates (e.g., sodium bicarbonate, potassium bicarbonate, etc.), ammonium carbonate, etc. The water-soluble strip may optionally include one or more activators used to activate or increase the activation rate of one or more degradation accelerators in the fiber structure. As can be understood, one or more activators may be included in the fibrous structure even when the degradation accelerator is not present in the fibrous structure. However, this is not required. For example, the activator may include an acidic or basic compound, which may be used as an adjunct to one or more active substances in the fibrous structure when or when the degradation accelerator is not included in the fibrous structure. When used, non-limiting examples of activators that may be included in the fibrous structure include organic acids (e.g., hydroxy-carboxylic acids [citric acid, tartaric acid, malic acid, lactic acid, gluconic acid, etc.], saturated aliphatic carboxylic acids [acetic acid, succinic acid, etc.], unsaturated aliphatic carboxylic acids [e.g., fumaric acid, etc.]. Non-limiting examples of degradation accelerators and materials that may be used to form the activators used in the fibrous structure are disclosed in U.S. Patent Application Publication No. 2011 / 0301070.

[0347] Active agent release One or more active agents may be released from the fiber elements and / or particles and / or fiber structures when the fiber elements and / or particles and / or fiber structures are exposed to a triggering condition. In one embodiment, one or more active agents may be released from the fiber elements and / or particles and / or fiber structures, or a portion thereof, when the fiber elements and / or particles and / or fiber structures lose their identity, in other words, lose their physical structure. For example, the fiber elements and / or particles and / or fiber structures lose their physical structure when the filament-forming material melts, dissolves, or undergoes some other transformation process such that the structure is lost. In one embodiment, one or more active agents are released from the fiber elements and / or particles and / or fiber structures when the morphology of the fiber elements and / or the morphology of the particles and / or the morphology of the fiber structures changes.

[0348] In another embodiment, one or more active agents may be released from the fibrous elements and / or particles and / or fibrous structures, or portions thereof, when the identity of the fibrous elements and / or particles and / or fibrous structures, or portions thereof, changes, in other words, when the physical structure of the fibrous elements and / or particles and / or fibrous structures changes, rather than losing, its physical structure. For example, the fibrous elements and / or particles and / or fibrous structures change their physical structure but retain their filament-forming properties when the filament-forming material expands, contracts, stretches and / or shortens.

[0349] In another embodiment, one or more active agents may be released from the fibrous elements and / or particles and / or fibrous structures without changing their morphology (without losing or changing their physical structure).

[0350] In one embodiment, the fibrous elements and / or particles and / or fibrous structures may release an active agent when exposed to triggering conditions that cause the fibrous elements and / or particles and / or fibrous structures to release the active agent, for example by causing the fibrous elements and / or particles and / or fibrous structures to lose or change their identity as described above. Non-limiting examples of triggering conditions include exposing the fiber elements, particles, and / or fibrous structures to solvents, polar solvents (such as alcohol and / or water), and / or non-polar solvents (which may be done sequentially depending on whether the filament-forming material includes polar solvent-soluble materials and / or non-polar solvent-soluble materials); exposing the fiber elements, particles, and / or fibrous structures to heat, for example, up to a temperature of greater than 75° F., and / or greater than 100° F., and / or greater than 150° F., and / or greater than 200° F., and / or greater than 212° F.; exposing the fiber elements, particles, and / or fibrous structures to cold, for example, up to a temperature of less than 40° F., and / or less than 32° F., and / or less than 0° F.; exposing the fiber elements, particles, and / or fibrous structures to a force, for example, a stretching force applied by a consumer using the fiber elements, particles, and / or fibrous structures; exposing the fiber elements and / or particles and / or fiber structures to a chemical reaction; exposing the fiber elements and / or particles and / or fiber structures to conditions that cause a phase change; exposing the fiber elements and / or particles and / or fiber structures to a pH change and / or a pressure change and / or a temperature change; exposing the fiber elements and / or particles and / or fiber structures to one or more chemicals that result in the fiber elements and / or particles and / or fiber structures releasing one or more of their active agents; exposing the fiber elements and / or particles and / or fiber structures to ultrasound; exposing the fiber elements and / or particles and / or fiber structures to light and / or specific wavelengths; exposing the fiber elements and / or particles and / or fiber structures to various ionic strengths; and / or exposing the fiber elements and / or particles and / or fiber structures to an active agent that is released from another fiber element and / or particle and / or fiber structure.

[0351] In one embodiment, one or more active agents may be released from the fiber elements and / or particles of the present invention when a fiber structure product comprising the fiber elements and / or particles is exposed to an inducing step selected from the group consisting of: pretreating a stain on a fabric article with the fiber structure product; forming a wash liquor by contacting the fiber structure product with water; spinning the fiber structure product in a dryer; heating the fiber structure product in a dryer; and combinations thereof.

[0352] Fiber element forming composition The fiber element of the present invention is made from a fiber element forming composition, such as a filament forming composition. The fiber element forming composition is a polar solvent-based composition. In one embodiment, the fiber element forming composition is an aqueous composition that includes one or more fiber element forming materials and one or more active agents.

[0353] The fiber element forming composition of the present invention has a shear viscosity of 3,000 s when measured according to the shear viscosity test method described herein. -1 At a shear rate of about 1 Pa·s to about 25 Pa·s, and / or about 2 Pa·s to about 20 Pa·s, and / or about 3 Pa·s to about 10 Pa·s at a processing temperature of 50°C to 100°C.

[0354] The fiber element forming composition of the present invention may exhibit a viscosity (rotational rheometer viscosity) of from about 0.01 Pa·s to about 1.2 Pa·s and / or from about 0.02 Pa·s to about 1.0 Pa·s when measured according to the rotational rheometer test method described herein.

[0355] The fiber element forming composition may be processed at a temperature of about 50°C to about 100°C, and / or about 65°C to about 95°C, and / or about 70°C to about 90°C when producing fiber elements from the fiber element forming composition.

[0356] In one embodiment, the fiber element forming composition may comprise at least 20% by weight, and / or at least 30% by weight, and / or at least 40% by weight, and / or at least 45% by weight, and / or at least 50% by weight up to about 90% by weight, or up to about 85% by weight, or up to about 80% by weight, or up to about 75% by weight of one or more fiber element forming materials, one or more active agents, and mixtures thereof. The fiber element forming composition may comprise from about 10% by weight to about 80% by weight of a polar solvent, such as water.

[0357] In one embodiment, the non-volatile components of the fiber element forming composition may comprise from about 20% by weight, and / or from about 30% by weight, and / or from about 40% by weight, and / or from about 45% by weight, and / or from about 50% by weight, and / or from about 75% by weight, and / or from about 80% by weight, and / or from about 85% by weight, and / or from about 90% by weight, based on the total weight of the fiber element forming composition. The non-volatile components may comprise the fiber element forming composition such as the backbone polymer, the active agent, and combinations thereof. The non-volatile components of the fiber element forming composition may comprise the remaining percentage, ranging from 10% by weight to 80% by weight, based on the total weight of the fiber element forming composition.

[0358] In the spinning process of fiber elements, the fiber elements need to have initial stability when they exit the spinning die. The capillary number is used to characterize this initial stability criterion. At the die conditions, the capillary number should be at least 1, and / or at least 3, and / or at least 4, and / or at least 5.

[0359] In one embodiment, the fiber element forming composition exhibits a capillary number of at least 1 and up to about 50, and / or at least 3 and up to about 50, and / or at least 5 and up to about 30, such that the fiber element forming composition can be effectively polymer processed into fiber elements.

[0360] As used herein, "polymer processing" refers to any spinning operation and / or spinning process in which fiber elements comprising processed fiber element forming material are formed from a fiber element forming composition. The spinning operation and / or process may include spunbond, meltblown, electrospinning, rotary spinning, continuous filament production, and / or tow fiber manufacturing operations / processes. As used herein, "processed fiber element forming material" refers to any fiber element forming material that has been subjected to melt processing operations and subsequent polymer processing operations into fiber elements.

[0361] The capillary number is a dimensionless number used to characterize the break-off potential of the droplet. A larger capillary number indicates greater fluid stability upon exiting the die. The capillary number is defined as:

[0362]

number

[0363] The capillary number is defined for the conditions at the exit of the die. The fluid velocity is the average velocity of the fluid passing through the holes in the die. The average velocity is defined as:

[0364]

number

[0365] If the die holes are circular holes, the fluid velocity can be defined as:

[0366]

number

[0367] Fluid viscosity is temperature dependent and can be shear rate dependent. The definition of a shear thinning fluid includes a dependence on shear rate. Surface tension is dependent on the composition of the fluid and the temperature of the fluid.

[0368] In one embodiment, the fiber element forming composition can include one or more release agents and / or lubricants. Non-limiting examples of suitable release agents and / or lubricants include fatty acids, fatty acid salts, fatty alcohols, fatty esters, sulfonated fatty acid esters, fatty amine acetates, and fatty acid amides, silicones, amino silicones, fluoropolymers, and mixtures thereof.

[0369] In one embodiment, the fiber element forming composition may include one or more antiblocking and / or detackifying agents. Non-limiting examples of suitable antiblocking and / or detackifying agents include starch, modified starch, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica.

[0370] The active agent of the present invention may be added to the fiber element forming composition before and / or during fiber element formation, and / or may be added to the fiber element after fiber element formation. For example, a perfume active may be applied to the fiber element and / or fiber structure comprising the fiber element after forming the fiber element and / or fiber structure according to the present invention. In another example, an enzyme active may be applied to the fiber element and / or fiber structure comprising the fiber element after forming the fiber element and / or fiber structure according to the present invention. In yet another example, one or more particles (which may not be suitable for passing through a spinning process to make the fiber element) may be applied to the fiber element and / or fiber structure comprising the fiber element after forming the fiber element and / or fiber structure according to the present invention.

[0371] Elongation aid In one embodiment, the fiber elements include an elongation aid, non-limiting examples of which may include polymers, other elongation aids, and combinations thereof.

[0372] In one embodiment, the elongation aid has a weight average molecular weight of at least about 500,000 Da. In another embodiment, the weight average molecular weight of the elongation aid is from about 500,000 to about 25,000,000, in another embodiment, from about 800,000 to about 22,000,000, in yet another embodiment, from about 1,000,000 to about 20,000,000, and in another embodiment, from about 2,000,000 to about 15,000,000. Higher molecular weight elongation aids are preferred in some embodiments of the present invention due to their ability to increase elongational melt viscosity and reduce melt fracture.

[0373] The elongation aid, when used in a meltblowing process, is added to the compositions of the present invention in an amount effective to appreciably reduce melt and capillary breakage of the fibers during the spinning process, allowing for the melt spinning of substantially continuous fibers having a relatively consistent diameter. Regardless of the process used to produce the fiber elements and / or particles, the elongation aid, when used, can be present in one embodiment from about 0.001% to about 10% by weight based on the dry fiber elements and / or dry particles and / or dry fiber structure, in another embodiment from about 0.005% to about 5% by weight based on the dry fiber elements and / or dry particles and / or dry fiber structure, in yet another embodiment from about 0.01% to about 1% by weight based on the dry fiber elements and / or dry particles and / or dry fiber structure, and in another embodiment from about 0.05% to about 0.5% by weight based on the dry fiber elements and / or dry particles and / or dry fiber structure.

[0374] Non-limiting examples of polymers that can be used as elongation aids can include alginates, carrageenans, pectins, chitin, guar gum, xanthan gum, agar, gum arabic, karaya gum, tragacanth gum, locust bean gum, alkyl celluloses, hydroxyalkyl celluloses, carboxyalkyl celluloses, and mixtures thereof.

[0375] Non-limiting examples of other elongation aids may include modified and unmodified polyacrylamide, polyacrylic acid, polymethacrylic acid, polyvinyl alcohol, polyvinyl acetate, polyvinylpyrrolidone, polyethylene vinyl acetate, polyethyleneimine, polyamides, polyalkylene oxides (including polyethylene oxide, polypropylene oxide, polyethylene propylene oxide), and mixtures thereof.

[0376] Method for manufacturing a textile element The fiber elements of the present invention may be made by any suitable process. Non-limiting examples of suitable processes for making the fiber elements of the present invention are described below.

[0377] In one embodiment, as shown in FIGS. 5 and 6, a method 28 for making a fiber element 14, such as a natural polymer-based fiber element, according to the present invention includes: a. providing a fiber element forming composition 30 comprising one or more fiber element forming materials, e.g., one or more natural polymer-based fiber element forming materials, e.g., one or more natural polymer-based fiber element forming materials including modified polysaccharides, e.g., modified starches, e.g., acetylated starches, and optionally one or more active agents; b. spinning the fiber element forming composition 30 through a spinning die 32, such as a multi-row capillary die, such as a multi-row meltblown capillary die, into one or more fiber elements 14, such as natural polymer-based fiber elements according to the present invention, such as filaments, comprising one or more fiber element forming materials and optionally one or more active agents. The one or more active agents may be releasable from the fiber elements when exposed to intended use conditions. The total concentration of one or more fibrous element forming materials present in the fibrous element 14 and / or the plurality of fibrous elements 14, e.g., the plurality of fibrous elements in a fibrous structure, when an active agent is present therein, may be less than 80% by weight, and / or less than 70% by weight, and / or less than 65% by weight, and / or less than 60% by weight, and / or less than 50% by weight, based on the dry fibrous element and / or on the dry fibrous structure, and the total concentration of one or more active agents present in the fibrous element 14 and / or the plurality of fibrous elements 14, e.g., the plurality of fibrous elements in a fibrous structure, may be greater than 20% by weight, and / or greater than 30% by weight, and / or greater than 35% by weight, and / or greater than 40% by weight, and / or 50% by weight or more, and / or 65% by weight or more, and / or 80% by weight or more, based on the dry fibrous element and / or on the dry fibrous structure.

[0378] As shown in FIG. 6 , the spinning die 32 may include a plurality of fiber element forming cavities 34 including melt capillaries 36 surrounded by concentric attenuation fluid holes 38 through which a fluid, such as air, passes as it exits the fiber element forming cavities 34 to facilitate attenuation of the filament forming composition 30 into fiber elements 14.

[0379] In one embodiment, during the spinning process, any volatile solvent, e.g., water, present in the filament-forming composition 30 is removed, such as by drying, as the fiber elements 14 are formed. In one embodiment, more than 30% by weight, and / or more than 40% by weight, and / or more than 50% by weight of the volatile solvent, e.g., water, of the fiber element-forming composition is removed during the spinning process, such as by drying the resulting fiber elements.

[0380] The fiber element forming composition may contain any suitable total concentration of fiber element forming material and any suitable concentration of active agent, so long as the fiber element produced from the fiber element forming composition contains, in the fiber element and / or multiple fiber elements, e.g., multiple fiber elements in a fibrous structure, a total concentration of fiber element forming material of about 5% to 50% by weight or less, on a dry fiber element basis and / or a dry particle basis and / or a dry fiber structure basis, and in the fiber element and / or multiple fiber elements, e.g., multiple fiber elements in a fibrous structure, a total concentration of active agent of 50% to about 95% by weight, on a dry fiber element basis and / or a dry particle basis and / or a dry fiber structure basis.

[0381] In one embodiment, the fiber element forming composition may contain any suitable total concentration of fiber element forming material and any suitable concentration of active agent, so long as the fiber elements produced from the fiber element forming composition contain, in the fiber elements and / or particles, a total concentration of fiber element forming material of about 5% to 50% by weight or less on a dry fiber element basis and / or dry particle basis and / or dry fiber structure basis, and a total concentration of active agent of 50% to about 95% by weight on a dry fiber element basis and / or dry particle basis and / or dry fiber structure basis, and the weight ratio of the total concentration of fiber element forming material to active agent is 1 or less.

[0382] In one embodiment, the fiber element forming composition comprises from about 1% and / or from about 5% and / or from about 10% to about 50%, or from about 40% to about 30%, or from about 20% by weight of the fiber element forming composition of fiber element forming material, from about 1% and / or from about 5% and / or from about 10% to about 50%, or from about 40% to about 30%, or from about 20% by weight of the fiber element forming composition of active agent, and from about 20% and / or from about 25% and / or from about 30% and / or from about 40% to about 80%, or from about 70% to about 60% and / or to about 50% by weight of the fiber element forming composition of volatile solvent, such as water. The fiber element forming composition may contain small amounts of other active agents, for example less than 10% by weight of the fiber element forming composition, and / or less than 5% by weight, and / or less than 3% by weight, and / or less than 1% by weight of plasticizers, pH adjusters, and other active agents.

[0383] The fiber element forming composition is spun into one or more fiber elements and / or particles by any suitable spinning process, such as meltblowing, spunbonding, electrospinning, and / or rotary spinning. In one embodiment, the fiber element forming composition is spun into a plurality of fiber elements and / or particles by meltblowing. For example, the fiber element forming composition may be pumped from a tank to a meltblowing spinneret. Upon exiting one or more of the fiber element forming holes in the spinneret, the fiber element forming composition is attenuated by air to form one or more fiber elements and / or particles. The fiber elements and / or particles may then be dried to remove any residual solvent (e.g., water) used for spinning.

[0384] The fibrous elements and / or particles of the present invention may be collected on a belt (eg, a patterned belt) to form a fibrous structure comprising the fibrous elements and / or particles.

[0385] Non-Limiting Examples of Fiber Element Forming Compositions for Making Fiber Elements Two non-limiting examples (Samples A and B) of fiber element forming compositions of the present invention suitable for making fiber elements and / or ultimately fiber structures of the present invention are provided in Table 5 below.

[0386] [Table 6] 1 Rotational Rheometer Viscosity Measured According to the Rotational Rheometer Viscosity Test Method Described herein

[0387] particle The particles may be water-soluble or water-insoluble. In one embodiment, some particles may be water-soluble and other particles may be water-insoluble. In another embodiment, the particles may include one or more active agents (in other words, the particles may include active agent-containing particles). In yet another embodiment, the particles may consist essentially of and / or consist of one or more active agents (in other words, the particles may include 100% or about 100% by weight of one or more active agents on a dry particle basis). In yet another embodiment, the particles may include water-soluble particles. In yet another embodiment, the particles may include water-soluble active agent-containing particles.

[0388] In one embodiment, the particles comprise agglomerates of different sub-particles of different materials, e.g., one or more effervescent salt particles, e.g., sodium bicarbonate, one or more effervescent acid particles, e.g., citric acid, one or more builder particles, e.g., zeolites, etc., which may be coated with a surfactant, e.g., a sulfate-free surfactant, e.g., DSCG, and optionally one or more polymers, e.g., a foam stabilizer, e.g., polyvinylpyrrolidone.

[0389] In one embodiment, the fibrous structure and / or fibrous structure product of the present invention comprises a plurality of particles and a plurality of fibrous elements, e.g., filaments, in a weight ratio of particles to fibrous elements of from about 3:1 to about 20:1, and / or from about 5:1 to about 15:1, and / or from about 5:1 to about 12:1, and / or from about 7:1 to about 12:1.

[0390] Method for producing a fiber structure In one embodiment of the present invention shown in Figure 7, a fibrous structure 10 of the present invention can be made by spinning a fiber element forming composition 30 from a spinning die 32 to form a plurality of fiber elements 14, such as a plurality of natural polymer-based fiber elements, such as filaments, as shown in Figures 5 and 6, and then combining one or more particles 18 provided by a particle source 40, such as a sifter or airlaid forming head. The particles 18 can be dispersed within the fiber elements 14. The mixture of particles 18 and fiber elements 14 can be collected on a collection belt 42, such as a patterned collection belt, that imparts a texture, such as a three-dimensional texture, to at least one surface of the fibrous structure 10.

[0391] Figure 8 shows another example of a method for making the fibrous structure 10 according to Figure 2. The method includes forming a first layer 12 of a plurality of fibrous elements 14 such that pockets 20 are formed on a surface of the first layer 12. One or more particles 18 are deposited in the pockets 20 from a particle source 40. A second layer 16 including a plurality of fibrous elements 14 produced from a spinning die 32 is then formed on the surface of the first layer 12 such that the particles 18 are enclosed in the pockets 20.

[0392] Figure 9 shows yet another example of a method for making the fibrous structure 10 according to Figure 1. The method includes forming a first layer 12 of a plurality of fibrous elements 14. One or more particles 18 are deposited on a surface of the first layer 12 from a particle source 40. A second layer 16 including a plurality of fibrous elements 14 produced from a spinning die 32 is then formed on the particles 18 such that the particles 18 are located between the first layer 12 and the second layer 16.

[0393] Non-Limiting Examples for Making Fiber Constructs The addition of particles can be accomplished during the formation of the nascent fibers or after collection of the nascent fibers on the patterned belt. Three methods are disclosed where the addition of particles results in the particles being entrapped in the structure.

[0394] As shown in Figures 5 and 6, the fiber element 14 of the present invention can be manufactured as follows. The fiber element 14 can be formed by a small-scale apparatus, the schematic diagram of which is shown in Figures 5 and 6. A pressurized tank 44 suitable for batch operation is filled with a fiber element forming composition 30 suitable for spinning. A pump 46, such as a Zenith® PEP II model manufactured by Zenith Pumps division of Parker Hannifin Corporation (Sanford, NC, USA) having a capacity of 5.0 cubic centimeters per revolution (cc / rev), can be used to facilitate the transport of the fiber element forming composition to the spinning die 32. The flow rate of fiber element forming material, e.g., fiber element forming composition 30 including fiber element forming material, from the pressurized tank 44 to the spinning die 32 can be controlled by adjusting the revolutions per minute (rpm) of the pump 46. A pipe 48 can be used to connect the pressurized tank 44, the pump 46, and the spinning die 32.

[0395] The spinning die 32 shown in FIG. 6 has several rows of circular extrusion nozzles (fiber element forming holes 34) spaced apart from one another with a pitch P of about 0.060 inches. The nozzles have individual inner diameters of about 0.012 inches and individual outer diameters of about 0.032 inches. Each individual nozzle is surrounded by an annular, branched, flared orifice (concentric attenuation fluid holes 38) for supplying attenuation air to each individual melt capillary 36 ("multiple row capillary die"). The filament-forming composition 30 extruded through the nozzles is surrounded and attenuated by a generally cylindrical stream of moist air supplied through the orifices.

[0396] Attenuated air may be provided by heating compressed air from a supply with an electric resistance heater, such as a heater manufactured by Chromalox, Division of Emerson Electric (Pittsburgh, Pa., USA). A suitable amount of steam was added to saturate or nearly saturate the heated air at conditions in the electrically heated, thermostatically controlled delivery pipe. Condensate was removed in an electrically heated, thermostatically controlled separator.

[0397] The embryonic fiber elements are dried by a drying air stream having a temperature of about 149° C. (about 300° F.) to about 315° C. (about 600° F.) by electrical resistance heaters (not shown) fed through a drying nozzle and emitted at an angle of about 90 degrees relative to the general orientation of the extruded non-thermoplastic embryonic fibers. The dried embryonic fiber elements are collected on a collection device (e.g., a movable foraminous belt or a patterned collection belt, etc.). A vacuum source may be added beneath the formation zone to aid in fiber recovery.

[0398] A suitable particle source 40, e.g., a feeder, for supplying a flow of particles 18 may be located directly above the drying area of ​​the fiber elements 14, as shown in FIG. 7. In this case, a vibrating feeder manufactured by Retsch® (Haan, Germany) is used. To aid in consistent distribution of particles in the cross direction, the particles are fed into a tray starting at the width of the feeder and ending at the same width as the spinning die face, ensuring that the particles are delivered to all areas of the forming fiber elements. The tray is completely enclosed except for the outlet to minimize disruption of the particle feed.

[0399] While the initial fiber elements are being formed, the feeder is switched on and particles are introduced into the flow of fiber elements. In this case, Green Zero (Green Speckle Granules) from Genencor International® (Leiden, The Netherlands) are used as particles. The particles that are to be combined and / or mixed with the fiber elements are collected together on a collection belt.

[0400] Once the precursor fibrous structure is formed, it may be subjected to a perforation process, i.e., a process that imparts one or more apertures to the fibrous structure to produce an apertured fibrous structure. Non-limiting examples of such perforation processes include embossing, lodging, rotary knife perforation, pinning, die cutting, die punching, needle punching, knurling, pneumatic forming, hydroforming, laser cutting, and tufting.

[0401] In one embodiment, the precursor fiber structure is subjected to a rotary knife perforation operation as outlined in U.S. Pat. No. 8,679,391. In another embodiment, the precursor fiber structure is subjected to a pinning operation as described below. In one embodiment, the precursor fiber structure is passed through a nip formed between two opposing pin rollers arranged in an intermeshing configuration such that the pins of one roller pass through the spaces between the pins on the opposing roller in the nip. A typical configuration may use two rollers with the same pin design and arrangement. However, the opposing rollers may have different pin designs and arrangements, or may instead have other fiber structure support members rather than pins, or may be a solid surface made of a flexible material that allows interference between the pins of the pinned rollers and the flexible surface. The degree of interference between the imaginary cylinders represented by the tips of the pins is described as the entanglement depth. As the fiber structure passes through the nip formed between the opposing rollers, the pins of each pinned roller engage with the fiber structure and penetrate the fiber structure to a depth that is roughly determined by the entanglement depth between the rollers and the nominal thickness of the fiber structure.

[0402] An example of a fibrous structure product 50, e.g., a usable unit for use by a consumer for its intended purpose, is shown in Figures 10A and 10B. As shown in Figures 10A and 10B, in one embodiment, the fibrous structure product 50 includes a multi-ply fibrous structure including one or more, in this case two plies of fibrous structures 10 (a first fibrous structure ply 52 and a second fibrous structure ply 54), which may or may not be fibrous structures themselves, but are components of the fibrous structure product 50 that are bonded together to form a multi-ply fibrous structure. In one embodiment shown in Figure 10B, the fibrous structure 10 includes a plurality of fibrous elements 14 that include a natural polymer-based fibrous element forming material, such as a modified polysaccharide, and an active agent, including a surfactant or surfactant mixture, present within the fibrous elements 14. A plurality of particles 18, e.g., water-soluble active agent-containing particles, e.g., aggregates, including a surfactant, are disposed (sandwiched) between the two fibrous structures 10. The two plies of the fibrous structure 10 (the first fibrous structure ply 52 and the second fibrous structure ply 54) may be joined at their edges by an edge seam 56, which may be formed by compressing the two plies of the fibrous structure 10 together along their edges to form a pouch containing the particles 18 until at least partial dissolution of the multi-ply fibrous structure or one or more of the plies of the fibrous structure 10 occurs during use.

[0403] In one embodiment, the fibrous structure may independently exhibit any suitable basis weight, for example, from about 100 gsm to about 5000 gsm, and / or from about 250 gsm to about 3000 gsm, and / or from about 500 gsm to about 2000 gsm. In one embodiment, the fibrous elements within the fibrous structure may independently be present within the fibrous structure at any suitable basis weight, for example, from about 10 to about 1000 gsm, and / or from about 10 gsm to about 500 gsm, and / or from about 20 gsm to about 400 gsm, and / or from about 100 gsm to about 300 gsm. In one embodiment, the particles, when present within the fibrous structure, may independently be present within the fibrous structure at any suitable basis weight, for example, from about 100 gsm to about 4000 gsm, and / or from about 250 gsm to about 3000 gsm, and / or from about 500 gsm to about 2000 gsm.

[0404] In one embodiment, other particles, including other active agents, may be added to and / or between the fibrous structures. For example, a perfume may be placed between two fibrous structures before the fibrous structures are bonded together. In one embodiment, the fibrous structures of the present invention are free or substantially free of foam suppressors and similar active agents that prevent and / or suppress foam production (and do not adversely affect foam production by the fibrous structures).

[0405] In one embodiment, a method of making a fibrous structure of the present invention includes: a. providing a fiber element forming composition comprising one or more fiber element forming materials, such as a natural polymer-based fiber element forming material including a modified polysaccharide, and one or more active agents, at least one of the active agents comprising a surfactant or surfactant mixture, and the surfactant or surfactant mixture and the modified polysaccharide are present in the fiber element forming composition in a weight ratio of about 0.25:1 to about 5:1; b. spinning the fiber element-forming composition into a plurality of fiber elements comprising the modified polysaccharide and the surfactant or surfactant mixture; and c. collecting the plurality of fibrous elements to form a fibrous structure on a collecting device, such as a belt.

[0406] In one embodiment, the method of making a fibrous structure of the present invention further comprises cutting one or more products from the fibrous structure, for example, die cutting one or more products from the fibrous structure.

[0407] In one embodiment, the method of making a fibrous structure of the present invention further comprises packaging one or more products in a package.

[0408] In one embodiment, a package comprises one or more of the fibrous structures of the present invention.

[0409] In one embodiment, the package contains one or more of the products of the present invention.

[0410] In one embodiment, the packaging material of the present invention is substantially natural and / or of natural origin and / or of biological origin and / or recyclable and / or exhibits a biodegradability of at least 5%, and / or at least 10%, and / or at least 15%, and / or at least 20%, and / or at least 25%, and / or at least 30%, and / or at least 35%, and / or at least 40%, and / or at least 45%, and / or at least 50%, and / or at least 55%, and / or about 60%, and / or at least 5% to about 60% at day 60 of the test period as determined by the OECD 301B Ready Biodegradable CO2 Evolution Test Method. When determined by the 301B Ready Biodegradable CO2 Evolution Test Method, the product exhibits a biodegradability of at least 5%, and / or at least 10%, and / or at least 15%, and / or at least 20%, and / or at least 25%, and / or at least 30%, and / or at least 35%, and / or at least 40%, and / or at least 45%, and / or at least 50%, and / or at least 55%, and / or at least 60%, and / or at least 65%, and / or at least 70%, and / or at least 75%, and / or about 80%, and / or at least 5% to about 80% on the 90th day of the test period.

[0411] Test Method Unless otherwise specified, all tests described herein, including those described in the definitions section, and the following test methods are performed on samples that have been conditioned for a minimum of 2 hours prior to testing in a room conditioned at a temperature of 23°C ± 1.0°C and a relative humidity of 50 ± 2%. The samples tested are "usable units". As used herein, "usable units" refers to e.g., unit dose articles / products that are used by the consumer for their intended purpose. All tests are performed under the same environmental conditions and in a room conditioned in this way. Samples with defects such as wrinkles, tears, etc. are not tested. Samples conditioned as described herein are considered to be dry samples (e.g., "dry filament") for testing purposes. All instruments are calibrated according to manufacturer's specifications.

[0412] Basis Weight Test Method Basis Weight is defined as the weight in g / m2 of the sample being tested. It is determined by accurately weighing a known area of ​​a conditioned sample using a suitable balance, recording the weight and area of ​​the sample tested, applying the appropriate conversion factor, and finally calculating the basis weight of the sample in g / m2.

[0413] Basis weight is measured by cutting a sample from a single web, a stack of webs, or other suitable stacked or consumer saleable unit and weighing the sample using a top-dish analytical balance with a resolution of ±0.001 g. Samples must be equilibrated at a temperature of 73°±2°F (23°±1°C) and a relative humidity of 50% (±2%) for a minimum of two hours prior to cutting the sample. During weighing, the balance is protected from air currents and other disturbances with a draft shield. All samples are prepared using a precision cutting die measuring 1.625 x 1.625 in. (41.275 x 41.275 mm). Select a usable sample area that is clean and free of holes, tears, wrinkles, and other defects.

[0414] For each sample, use the die cutter described above to cut the sample, weigh the mass of the sample, and record the mass result to the nearest 0.001 g.

[0415] The basis weight in g / m2 is as follows: 2 Calculate with: Basis Weight = (mass of sample) / (area of ​​sample).

[0416] Or specifically, Basis weight (g / m 2 ) = (mass of sample (g)) / (0.001704m 2 ).

[0417] The result is 0.1 g / m 2 The basis weight is reported in units. Sample size can be altered or varied using a similar precision cutter as described above. When sample size is reduced, several samples should be measured and the average value should be reported as the basis weight.

[0418] Moisture content test method The moisture (moisture) content present in the fibrous elements, and / or particles, and / or fibrous structures is measured using the following moisture content test method. The fibrous elements, and / or particles, and / or fibrous structures in the form of pre-cut sheets, or portions thereof ("samples"), are placed in a room conditioned to a temperature of 23°C ± 1.0°C and a relative humidity of 50% ± 2% for at least 24 hours prior to testing. Each fibrous structure sample has an area of ​​at least 4 square inches, but is small enough in size to fit adequately on the weighing pan of a balance. Under the above temperature and humidity conditions, using a balance capable of measuring to at least 4 decimal places, the weight of the sample is recorded every 5 minutes until the weight changes by less than 0.5% from the previous (measured) weight within 10 minutes. The final weight is recorded as the "equilibrated weight". Within 10 minutes, the sample is placed on foil in a forced air oven for drying at 70°C ± 2°C and a relative humidity of 4% ± 2% for 24 hours. After 24 hours of drying, the sample is removed and its weight is measured within 15 seconds - this weight is called the "dry weight" of the sample.

[0419] Calculate the moisture (water) content of the sample as follows:

[0420]

number

[0421] The % moisture (moisture) in the sample for the three replicates is averaged and reported as the % moisture (moisture) in the sample. Results are reported to one decimal place (0.1%).

[0422] Diameter Test Method A scanning electron microscope (SEM) or optical microscope and image analysis software are used to measure the diameter of discrete fiber elements or fiber elements in a fiber structure. A magnification between 200 and 10,000 times is selected to adequately magnify the fiber elements for measurement. When using an SEM, the sample is sputtered with gold or palladium compounds to avoid charging and vibration of the fiber elements in the electron beam. A manual procedure is used to measure the diameter of the fiber elements from the image (on the monitor screen) obtained with the SEM or optical microscope. The mouse and cursor tool are used to locate the edge of a randomly selected fiber element and then measure across its width (i.e. perpendicular to the orientation of the fiber element at that point) to the other edge of the fiber element. A calibrated image analysis tool with scale provides a scale to obtain the actual reading in μm. For fiber elements in a fiber structure, a few fiber elements are randomly selected from the entire fiber structure sample using the SEM or optical microscope. At least two portions of the fiber structure are cut and tested in this manner. A total of at least 100 such measurements are performed and all data is then recorded for statistical analysis. The recorded data is used to calculate the mean (average) fiber element diameter, the standard deviation of the fiber element diameter, and the median fiber element diameter.

[0423] Another useful statistic is the calculation of the amount of fiber element population smaller than a particular upper limit. To determine this statistic, the software is programmed to count the number of fiber element diameter results smaller than the upper limit, and the count (divided by the total number of data and multiplied by 100%) is recorded as a percentage, i.e., percent smaller than the upper limit (e.g., percent less than 1 micrometer or submicron %). We refer to the measured diameter (μm) of an individual circular fiber element as di.

[0424] If the fiber element has a non-circular cross section, the diameter of the fiber element is measured as the hydraulic diameter and set equal to the hydraulic diameter, which is the cross-sectional area of ​​the fiber element multiplied by four divided by the perimeter of the cross section of the fiber element (or the perimeter in the case of hollow fiber elements). The number-average diameter, or mean diameter, is calculated as follows:

[0425]

number

[0426] Weight average molecular weight The Mw and Mw distribution of materials, such as fiber element forming materials, such as modified polysaccharides, such as modified starches, such as starch acetate, are analyzed by GPC-MALS (Gel Permeation Chromatography combined Multi Angle Light Scattering). Analysis of fiber element forming material samples is performed by dissolving the fiber element forming material in DMSO containing 0.1% LiBr. The fiber element forming material solution is then separated and analyzed in a set of three StyraGel HT columns from Waters Corporation, using a separation module 2695e or equivalent from Waters Corporation, in conjunction with a laser photometer DAWN HELEOS, 658 nm or equivalent from Wyatt Technology, and a refractive index detector 2414 or equivalent from Waters Corporation. For starch acetate samples, the samples were saponified with 1N NaOH solution at 40° C. The samples were then precipitated in MeOH, washed, and gently dried. Mw is reported as g / mol.

[0427] Fiber element forming material compatibility test method A fiber element forming material, such as a natural polymer-based fiber element forming material, such as a modified polysaccharide, such as a modified starch, such as acetylated starch (starch acetate), is heated in deionized water at 95° C. and cooled to 80° C. to form a fiber element forming material solution. A surfactant paste (sodium linear alkylbenzene sulfonate (NaLAS) at 30% solids) is added to the fiber element forming material solution in a surfactant to fiber element forming material weight ratio of 2:1. The surfactant / fiber element forming material solution is then stirred for 15 minutes, after which the solution is placed in an oven at 80° C. overnight. The solution is then placed in a 15 mL vial and a visual inspection is performed to determine whether the solution exhibits a single phase (one phase or clear / no phase separation) and passes this test method (sufficient miscibility=suitable) or phase separation occurs (two phases) and fails this test method (sufficient miscibility=unsuitable).

[0428] Dissolution Test Method Apparatus and materials (see also Figures 11 to 13): 600mL beaker 58 Magnetic Stirrer 60 (Labline Model 1250 or equivalent) Magnetic Stirring Rod 62 (5cm) Thermometer (1~100℃+ / -1℃) Punching Die - Stainless steel punching die measuring 3.8cm x 3.2cm Timer (0-3,600 seconds or 1 hour), accurate to the second. The timer used must have a total time measurement range sufficient for samples that show dissolution times greater than 3,600 seconds. However, the timer must be accurate to the second. Polaroid 35 mm Slide 64 (available from Polaroid Corporation or equivalent) 35mm Slide Holder 66 (or equivalent) Cincinnati city tap water or equivalent having the following characteristics: total hardness = 155 mg / L (as CaCO3); calcium content = 33.2 mg / L; magnesium content = 17.5 mg / L; phosphate content = 0.0462.

[0429] Testing Protocol Equilibrate the sample for at least 2 hours in a constant temperature and humidity environment of 23°C ± 1.0°C and 50% RH ± 2%. Measure the basis weight of the fibrous structure sample to be measured using the basis weight test method defined herein. Cut three dissolution test specimens from the fibrous structure sample using a punch die to fit within a 35 mm slide 64 with opening area dimensions of 24 x 36 mm (3.8 cm x 3.2 cm). Fix each specimen to a separate 35 mm slide 64. Place a magnetic stirring rod 62 in a 600 mL beaker 58. Turn on tap water (or equivalent) and measure the water temperature with a thermometer, adjusting with hot or cold water as necessary to maintain the test temperature. The test temperature is water at 15°C ± 1°C. Once the test temperature is reached, fill the beaker 58 with 500 mL ± 5 mL of tap water at 15°C ± 1°C. The filled beaker 58 is placed on the magnetic stirrer 60, the stirrer 62 is turned on, and the stirring speed is adjusted until a vortex is created and the bottom of the vortex reaches the 400 mL mark of the beaker 58. The 35 mm slide base 64 is secured to the alligator clamp 68 of the 35 mm slide base holder 66 so that the long end 70 of the slide base 64 is parallel to the water surface. The alligator clamp 68 should be centered on the long end 70 of the slide base 64. The depth adjuster 72 of the holder 66 should be set so that the distance between the bottom of the depth adjuster 72 and the bottom of the alligator clamp 68 is approximately 11 + / - 0.125 inches. This positioning positions the sample surface perpendicular to the water flow. In one motion, lower the secured slide and clamp into the water and start the timer. The sample is lowered so that it is in the center of the beaker. Disintegration occurs when the nonwoven structure breaks apart. This is recorded as the disintegration time. Once all visible nonwoven structure has been released from the slide platform, the slide is removed from the water while continuing to monitor the solution for undissolved nonwoven structure fragments. Dissolution has occurred when all nonwoven structure fragments are no longer visible in the water. This is recorded as the dissolution time.

[0430] Three replicates of each sample are tested and the average disintegration and dissolution times are recorded. The average disintegration and dissolution times are in seconds.

[0431] The average disintegration and dissolution times are normalized for basis weight by dividing each by the sample basis weight as determined by the Basis Weight Method defined herein. The basis weight normalized disintegration and dissolution times are expressed in seconds / gsm of sample (s / (g / m 2 ) is a unit of mass.

[0432] Thickness Method The thickness of the fibrous structure is measured by cutting five samples from the fibrous structure sample such that each cut sample is larger than the load foot mounting surface of a VIR Electronic Thickness Tester Model II (available from Thwing-Albert Instrument Company, Philadelphia, PA). Typically, the load foot mounting surface has a circular surface area of ​​about 3.14 square inches. The sample is clamped between a horizontal flat surface and the load foot mounting surface. The load foot mounting surface has a surface area of ​​15.5 g / cm. 2 A confining pressure of 0.001 mm is applied to the specimen. The thickness of each specimen is the resulting gap between the flat surface and the load foot mounting surface. The thickness is calculated as the average thickness of the five specimens. Results are reported in millimeters (mm).

[0433] Shear Viscosity Test Method The shear viscosity of the filament-forming composition of the present invention is measured using a capillary rheometer, a Goettfert Rheograph 6000 manufactured by Goettfert USA (Rock Hill SC, USA). Measurements are performed using a capillary die having a diameter D of 1.0 mm and a length L of 30 mm (i.e. L / D=30). The die is attached to the lower end of the 20 mm barrel of the rheometer and held at a die test temperature of 75° C. A 60 g sample of the filament-forming composition, preheated to the die test temperature, is loaded into the barrel region of the rheometer. Any trapped air is removed from the sample. A series of selected speeds from 1,000 to 10,000 seconds is run. -1The sample is extruded from the barrel through the capillary die at . The apparent shear viscosity can be calculated using the rheometer software from the pressure drop across the sample as it travels from the barrel through the capillary die and the flow rate of the sample through the capillary die. Log(apparent shear viscosity) can be plotted against log(shear rate) and this plot can be expressed by the equation η=Kγ n-1 where K is the viscosity constant of the material, n is the thinning exponent of the material, and γ is the shear rate. The reported apparent shear viscosities of the filament-forming compositions herein can be fitted using a power law relationship at a shear rate of 3,000 s -1 It is calculated from the interpolation to

[0434] Rotational Rheometer Test Method The shear viscosity of the compositions is measured using an AR-G2 rotational rheometer from TA Instruments or similar equipment. A cone-plate geometry of 40 mm diameter, 2.007° angle, and 57 mm truncation gap was used with a Peltier plate for temperature control. Step flow shear rates of 0.1 / s to 100 / s are applied with a 10 second residence time at 25° C. The shear viscosity at 10 / s is reported.

[0435] Fiber element composition test method To prepare the fiber elements for fiber element composition measurement, the fiber elements are conditioned by removing any removable coating compositions and / or materials present on the exterior surface of the fiber element. An example of how to do this is to wash the fiber element three times with a suitable solvent that removes the exterior coating without altering the fiber element. The fiber element is then air-dried at a temperature of 23° C.±1.0° C. until the moisture content of the fiber element is less than 10%. Chemical analysis of the conditioned fiber element is then performed to determine the compositional makeup of the fiber element with respect to filament-forming materials and active agents, as well as the levels of filament-forming materials and active agents present in the fiber element.

[0436] The composition of the fiber element forming materials and active agents may also be determined by completing a cross-sectional analysis using TOF-SIMS or SEM. Yet another method for determining the composition of the fiber elements uses fluorescent dyes as markers. Furthermore, as always, manufacturers of fiber elements must know the composition of their fiber elements.

[0437] Particle size distribution test method Particle size distribution testing is performed to determine the characteristic size of particles, which may be discrete particles, foam stabilizer coated effervescent acid particles or foam stabilizer coated effervescent salt particles, and / or aggregates (e.g., discrete particles bound together by foam stabilizers). This is performed using ASTM D 502-89 "Standard Test Method for Particle Size of Soaps and Other Detergents," approved May 26, 1989, with further specifications for sieve sizes and sieve times used in the analysis. According to Section 7 "Procedure using machine-sieving method", clean and dry nest of sieves including American standard (ASTM E 11) sieves #4 (4.75 mm), #6 (3.35 mm), #8 (2.36 mm), #12 (1.7 mm), #16 (1.18 mm), #20 (850 micrometers), #30 (600 micrometers), #40 (425 micrometers), #50 (300 micrometers), #70 (212 micrometers), #100 (150 micrometers), #170 (90 micrometers), #325 (44 micrometers) and pans are required to cover the particle size ranges mentioned herein. The prescribed mechanical sieving method is used with the nested sieves mentioned above. A suitable sieve shaker is available from WS Thiler Company (Ohio, USA). The sieve shake test sample is approximately 100 grams and is shaken for 5 minutes.

[0438] The data are plotted on a semi-log plot with the micrometer size opening of each sieve plotted on the log abscissa and the cumulative mass percent finer (CMPF) plotted on the linear ordinate. An example of such data representation is given in Figure A.4 of ISO 9276-1:1998, "Representation of results of particle size analysis-Part 1:Graphical Representation". The characteristic particle size (Dx, x=10, 50, 90) is defined for the purposes of this invention as the abscissa value at the point where the cumulative mass percent is equal to x percent, according to the following formula: Dx=10^[Log(Da)-(Log(Da)-Log(Db))×(Qa-x%) / (Qa-Qb)] where Log is the base 10 logarithm, Qa and Qb are the cumulative mass percentile values ​​of the measured data just above and just below the x percentile, respectively, and Da and Db are the micrometer sieve size values ​​that correspond to these data.

[0439] Example data and calculations:

[0440] [Table 7]

[0441] For D10 (x=10), the micrometer screen size just above the 10% CMPF (Da) is 300 micrometers and just below (Db) is 212 micrometers. The cumulative mass just above the 10% (Qa) is 15.2% and just below (Qb) is 6.8%. D10=10^[Log(300)-(Log(300)-Log(212))×(15.2%-10%) / (15.2%-6.8%)]=242 micrometers.

[0442] For D90 (x=90), the micrometer screen size (Da) just above where the CMPF is 90% is 1180 micrometers, and the screen just below (Db) is 850 micrometers. The cumulative mass (Qa) just above the 90% is 99.3% and just below (Qb) is 89.0%. D90=10^[Log(1180)-(Log(1180)-Log(850))×(99.3%-90%) / (99.3%-89.0%)]=878 micrometers.

[0443] For D50 (x=50), the micrometer screen size just above CMPF 50% (Da) is 600 micrometers and just below (Db) is 425 micrometers. The cumulative mass just above 50% (Qa) is 60.3% and just below (Qb) is 32.4%. D50=10^[Log(600)-(Log(600)-Log(425))×(60.3%-50%) / (60.3%-32.4%)]=528 micrometers.

[0444] Fedors Law The solubility parameter numbers of natural polymer-based fiber element forming materials, such as modified polysaccharides, such as modified starches, such as starch acetate, are calculated using the Fedors method.

[0445] Below are examples of calculations of the solubility parameters of various fiber element forming materials.

[0446] The solubility parameter can be calculated from Equation 1 in the Fedors method (repeated here as Equation 1). (Fedors formula 1) Formula 1:

[0447]

number

[0448] Examples of this calculation are given for polyvinyl alcohol, polyvinyl acetate, starch, and starch acetate (DS=1).

[0449] [Table 8]

[0450] [Table 9]

[0451] [Table 10]

[0452] [Table 11]

[0453] The copolymer solubility parameter is calculated by summing the mole fraction weighted homopolymer solubility parameters as shown in Equation 4. Formula 4: δ コポリマー =X A δ A +X B δ B (In the formula, X A and δ A are the mole fraction of homopolymer A and the homopolymer solubility parameter, respectively, and X B and δ B are the mole fraction and homopolymer solubility parameter of homopolymer B, respectively, so that the sum of the mole fractions equals 1. If additional termonomer is added, additional terms for the mole fraction and homopolymer solubility parameter are added to the equation so that the sum of all the mole fractions equals 1.

[0454] [Table 12]

[0455] Charge Density Test Method If the fiber element forming material in the fiber element, e.g., a natural polymer-based fiber element forming material, is identified or known, the charge density of the fiber element forming material can be determined by using a Mutek PCD-04 particle charge detector available from BTG or an equivalent instrument. Use the following guidelines provided by BTG. Obviously, manufacturers of fiber elements that include fiber element forming materials will know which fiber element forming materials are included in the fiber element. Thus, manufacturers of such fiber elements can determine the charge density of the fiber element forming material.

[0456] 1. Start with a 0.1% solution (0.1 g fiber element forming material + 99.9 g deionized water). Increase or decrease the fiber element forming material content depending on the titrant consumption. The solution pH is adjusted before the final dilution, since the charge density of many additives depends on the solution pH. A pH of 4.5 is used here. 2. Place 20 mL of sample into the PCD measurement cell and insert the piston. 3. Push the measuring cell with the piston to sample into the PCD, with the electrodes facing the back side. Slide the cell along the guide until it touches the back side. 4. Pull the piston upward and rotate counterclockwise to lock the piston in place. 5. Switch on the motor. The streaming potential will be indicated on the touch panel. Wait 2 minutes for the signal to stabilize. 6. Use an oppositely charged titrant (e.g. for cationic samples with positive streaming potential: use an anionic titrant) Titrants are available from BTG and consist of 0.001N PVSK or 0.001N PolyDADMAC. 7. Utilize the autotitrator available from BTG. After selecting the appropriate titrant, set up the titrator and rinse the tubing by dispensing 10 mL, insuring that all air bubbles have been purged. 8. Place the tip of the tube under the surface of the sample and begin the titration. Set the autotitrator to automatically stop when the potential reaches 0 mV. 9. Record the consumption of titrant. Ideally, the consumption of titrant should be between 0.2mL and 10mL, otherwise it will decrease or increase the content of fiber element forming material. 10. Repeat the titration of a second 20 mL aliquot of the fiber element forming material sample. 11. Calculate the charge demand (solution) or charge demand (solid);

[0457]

number

[0458] The charge density (charge demand) of the materials forming the fiber elements is reported in units of meq / g.

[0459] Dimensions and values ​​disclosed herein should not be understood as being strictly limited to the exact numerical values ​​recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."

[0460] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety, unless expressly stated to the contrary. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose any such invention, either alone or in combination with any other reference(s). Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.

[0461] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.

Claims

1. A fiber structure including a plurality of fiber elements, The plurality of fiber elements includes one or more fiber element forming materials; At least one of the one or more fiber element forming materials comprises a modified polysaccharide and one or more active agents; the one or more active agents include a surfactant; said surfactant and said modified polysaccharide are present in said plurality of fibrous elements in a weight ratio of from 0.15:1 to 6:1; The modified polysaccharide has a solubility parameter of greater than 14.00 and less than 16.25, as measured according to the Fedors method. A fiber structure characterized by:

2. The fibrous structure of claim 1 , wherein the plurality of fibrous elements comprises a plurality of filaments.

3. 2. The fiber structure according to claim 1, wherein the modified polysaccharide exhibits a weight average molecular weight of more than 50,000 g / mol to less than 40,000,000 g / mol, as measured according to the Weight Average Molecular Weight Test Method.

4. 2. The fiber structure according to claim 1, wherein the modified polysaccharide is a nonionic modified polysaccharide.

5. 2. The fiber structure according to claim 1, wherein the modified polysaccharide is an acetyl-substituted polysaccharide.

6. The fibrous structure of claim 5, wherein the acetyl-substituted polysaccharide exhibits a degree of substitution (DS) of at least 0.3 to 1.

0.

7. The fibrous structure of claim 1 , characterized in that the modified polysaccharide is derived from starch.

8. The fibrous structure of claim 1, wherein the plurality of fibrous elements comprises the modified polysaccharide at a total concentration of less than 80% by weight of the dry fibrous elements and the surfactant at a total concentration of more than 20% by weight of the dry fibrous elements.

9. 2. The fibrous structure of claim 1, wherein the modified polysaccharide and the surfactant are present in the dry fibrous element in a weight ratio of modified polysaccharide to surfactant of 1 or less.

10. 10. The fibrous structure of claim 1, wherein the one or more actives further comprise at least one additional non-surfactant active selected from the group consisting of skin care actives, medicaments, lotions, fabric care actives, dishwashing actives, carpet care actives, surface care actives, hair care actives, air care actives, dental care actives, and mixtures thereof.

11. The modified polysaccharide is a readily biodegradable polysaccharide according to OECD 301B 2 10. The fibrous structure of claim 1, characterized in that it exhibits at least 5% biodegradability at 28 days of the test period as determined by the Developmental Test Method.

12. A package comprising one or more fibrous structures according to claim 1.

13. A method for making the fibrous structure of claim 1, comprising the steps of: providing a fiber element forming composition comprising one or more fiber element forming materials, the fiber element forming composition comprising a modified polysaccharide and one or more active agents, at least one of the active agents comprising a surfactant, the surfactant and the modified polysaccharide being present in the fiber element forming composition in a weight ratio of 0.15:1 to 6:1, the modified polysaccharide having a solubility parameter, as measured according to the Fedors method, of greater than 14.00 and less than 16.25; b. spinning the fiber element-forming composition into a plurality of fiber elements comprising the modified polysaccharide and the surfactant; c) collecting the plurality of fiber elements to form a fiber structure; The method according to claim 1, further comprising:

14. A fiber element forming composition comprising a polar solvent and one or more fiber element forming materials, At least one of the one or more fiber element forming materials comprises a modified polysaccharide and one or more active agents; the one or more active agents include a surfactant; said surfactant and said modified polysaccharide are present in the fiber element forming composition in a weight ratio of from 0.15:1 to 6:1; The modified polysaccharide has a solubility parameter of greater than 14.00 and less than 16.25, as measured according to the Fedors method. A fiber element forming composition comprising:

15. The fiber element forming composition of claim 14, wherein the polar solvent is water.

16. 15. The fiber element forming composition of claim 14, wherein the modified polysaccharide comprises a modified starch.

17. 17. The fiber element forming composition of claim 16, wherein the modified starch comprises an acetylated starch.

18. 15. The fiber element forming composition of claim 14, wherein the one or more actives further comprise an additional non-surface active, the additional active being selected from the group consisting of skin care actives, medicaments, lotions, fabric care actives, dishwashing actives, carpet care actives, surface care actives, hair care actives, air care actives, dental care actives, and mixtures thereof.

Citation Information

Patent Citations

  • Acetate fiber and production thereof

    JP1991193909A

  • Filament containing an activator nonwoven web and method for manufacturing the same

    JP2013505375A

  • Foamable composition for producing stable foam and method of manufacturing same

    JP2022543254A